Optimizing MaxEnt to project habitat shifts of Idesia polycarpa var. vestita Diels, a bioenergy tree, in China under climate change scenarios - Yixuan Peng; Longcheng Jiang; Jin Wang; Rou Ma; Hua Lin; Evgeny Lopatin; Yangzhou Xiang; Hongyan Yang; Yuan Li (Biomass and Bioenergy, 2027)

A Multi-Index decision framework of optimal gasket selection for tunnel segmental joints: Integrating variable weight and extension cloud model - Huai-Na Wu; Hua-Yong Li; De-Sai Guo; Yu Li; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Mechanism and engineering evaluation of multi-element removal in lead-bismuth fast reactor concentrate using commercial ion exchange resins - Shiyang Peng; Jiayu Li; Shuang Li; Ning Zhang; Kaiyuan Jiang; Hua Xie (Annals of Nuclear Energy, 2026)

A critical review on microalgae-driven wastewater treatment: Dual focus on high-value bioproducts recovery and emerging contaminants removal - Shuli Liu; Jiajun Hua; Yuhong Zhang; Yatong Gao; Xiaohong Han; Yali Liu; Glen T. Daigger; Qi Li; Ning Guo; Zhixin Song; Peng Zhang; Xiane Zhang; et al. (Journal of Environmental Sciences, 2026)

Associations of prenatal per- and polyfluoroalkyl substance exposure with neonatal birth weight z-scores: The potential mediating role of maternal glucose homeostasis - Chun-Yong Wang; Zhen-Hua Li; Hai-Yang Weng; Xiao-Yu Zhao; Shao-Lei Pu; Meng-Na Zhu; Rui He; Xia-Juan Lu; Yu-Long Kan; Kai Huang; Guo-Peng Gao; Mao-Lin Chen; et al. (Environmental Pollution, 2026)

Associations between early pregnancy essential metals and birth outcomes: Exploration of effect modification by maternal thyroid hormones - Xiao-Yu Zhao; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

From bisphenol A to its analogues: Shifts in occurrence and risk in wastewater treatment plants - Ke Zhao; Ze-hua Liu; Jian Gong; Bi-qing Li; Peng-jie Huang; Eddy Y. Zeng (Environmental Pollution, 2026)

Ambient electrochemical synthesis of crystalline iron–silicate frameworks via silicate role-inversion for ultra-stable lattice-trapping of uranium - Qinwen Yao; Zhaowen Cheng; Dun Wei; Qiong Tian; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Chemical Engineering Journal, 2026)

Mixed conducting interlayer with self-regulating electronic/ionic conductivity for Li-metal solid state batteries - Ziwei Cai; Yang Li; Nan Zhang; Hua Jiang; Hai Zhong; Tao Peng; Jiangdong Fan; Xingjiang Liu; Andreu Cabot; Yaohua Mai (Chemical Engineering Journal, 2026)

Urbanization facilitates colonization and reshapes strangler-host networks: the fate of strangler figs in a tropical urban landscape and implications for management - Yu-Xuan Mo; Huang Zou; Hai-Xia Hu; Josep Peñuelas; Zhi-Peng Wang; Bang-Xiao Zheng; Xian-Meng Shi; Su Li; Sujan Balami; Hua-Zheng Lu; Liang Song (Urban Forestry & Urban Greening, 2026)

Caged xanthones with cytotoxic activity from the leaves and twigs of Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Si-Yu Wang; Jin-Yuan Yang; Hao-Nan Li; Bin Lin; Hui-Ming Hua; Da-Hong Li (Phytochemistry, 2026)

Multi-scale evolutionary forces shape the phylogeography of an Old World disjunct plant genus Girardinia (Urticaceae) - Zhi-Peng Li; Hai-Ling Qi; Fu-lv Liu; Ying Zhao; Alexandre K. Monro; Abdullah; Xiao-Yu Song; Yue-Hua Wang; Zeng-Yuan Wu; Jie Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Foraminiferal composition of the early Oligocene Globigerinid-rich limestone in the Baiyun Sag, Pearl River Mouth Basin, and its paleo-environmental significance - Guang-Rong Peng; Cui Shi; Xiao-Ping Li; Xin-Yu Liu; Le-Yi Xu; Kai Zhang; Qi-Mei Guo; Bao-Hua Li (Palaeoworld, 2026)

Tracing hydrothermal fluid evolution of the Tongshankou skarn–porphyry Cu–Mo–W deposit (Eastern China) using integrated infrared spectroscopic characteristics and magnetic susceptibility - Shili Peng; Shitao Zhang; Hao Xu; Gaobin Chu; Longfei He; Yu Zhang; Hua Zhang; Rucao Li; Yihui Lyu; Di Ding; Siyuan Zhang; Haisen Huang (Journal of Asian Earth Sciences, 2026)

A pH-responsive bilayer film based on PHBV/ZnO and polyvinyl alcohol/carboxymethyl konjac glucomannan/alizarin was developed for monitoring and maintaining pork freshness - Qiu-Yu Peng; Meng Wang; Song Chen; Long-Hua Zou; Yun-Cheng Li; Fan-Bing Meng (Food Chemistry, 2026)

Corrigendum to “Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system” [Estuar. Coast Shelf Sci. 340 (2026) 110113] - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Multiple environmental drivers shape zooplankton community structure in a subtropical-tropical transitional coastal system - Zhao-Lang Huang; Shuang Liu; Yan-Guo Wang; Pu-Qing Song; Rou-Xin Sun; Bing-Peng Xing; Su-Min Wang; Jian-Hua Kang; Geng-Ming Lin; Ping Li (Estuarine, Coastal and Shelf Science, 2026)

Hierarchically structured superamphiphobic radiative cooling fabric for personal thermal management - Wen-Jing Zhao; Chao-Hua Xue; Xiao-Jing Guo; Jing-Jing Peng; Li Wan; Yan Yang; Shi-Hang Lv; Jin-Yu Wang; Teng-Xin Wang; Ming-Wei Chang (Chemical Engineering Journal, 2026)

Phenothiazine-based self-assembled monolayer enabling high-efficiency and scalable inverted perovskite solar cells - Huilin Xie; Mingxin Wang; Xiaofeng He; Peng Wang; Miaoxin Li; Cheng Zhong; Qunliang Song; Yong Hua; Fei Wu; Linna Zhu (Chemical Engineering Journal, 2026)

“Precursors-in-action” nanoreactor: Coordination-activated self-assembly of cu/Fe bimetallic multifunctional metalloenzyme mimics for cascade-amplified breast cancer therapy - Peng Wang; Xin-Yi Zhang; Ying-Ying Han; Zhi-Yuan Li; Qing-Hua Shen; Long-Bo Yu; Cai-Ping Tan (Chemical Engineering Journal, 2026)

Stress determination of multi-wire steel strands using acoustoelastic effect of ultrasonic guided waves - Hua-Peng Chen; Hao-Hua Li; Chen-Xi Kang; Guo-Ying Zhang (Wave Motion, 2026)

Si–O isotopes and trace elements of detrital zircons record magmatic sources and environments of the early continental crust - Kai Lei; Hao Wang; Peng Liou; Jilian Jiang; Jinghui Guo; Xian-Hua Li (Precambrian Research, 2026)

Placental transfer efficiencies of multiple metals: Patterns, and influence factors - Yu Li; Xianglian Peng; Nian Liu; Hua Guo; Yurong Jia; Wenjing Li; Ziyin Liang; Po Tang; Guohuan Zhang; Qinfei Zhou; Yong Liang; Ligang Hu; et al. (Journal of Environmental Sciences, 2026)

Nature and timing of W-Sn mineralization in the Xin’anzi Deposit, Nanling Region: constraints from LA-ICP-MS cassiterite U-Pb geochronology and trace element composition - Gen-Wen He; Pei Ni; Wen-Sheng Li; Lin-Lin Peng; Gua-Hua Wang; Xin-Yue Liang; Jia-Hui Yan; Kai-Han Zhang; Li-Na Zhao (Journal of Asian Earth Sciences, 2026)

A glucose–inulin composite carbon source increases the final viable cell count of Lacticaseibacillus paracasei ProSci-92 and is associated with stage-dependent transcriptomic and metabolomic responses - Hua Wang; Peng Liu; Shijia Shen; Xuan Li; Shuaisen Gao; Jie Yu (Food Bioscience, 2026)

TBK1 associates with TRIF and TRAF3 related IRF3, IRF7, and type I IFN signaling in large yellow croaker Larimichthys crocea - Ying Li; Wen Qi Zha; Wen Feng Cui; Meng Jia Li; Yan Mi Na Chen; Qiu Ye Huang; Qiao Yun Yang; Ying Jia Shen; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Superphosphate-driven low-pH regime reduces greenhouse gas emissions during manure composting - Yuchen Yang; Huijie Li; Pan Wu; Shuang Peng; Qingqing Hua; Beibei Zhou; Yiming Wang; Xiangui Lin (Bioresource Technology, 2026)

Drought sensitivity and tree growth attributes regulate growth resilience of Southeast Asian pines under extreme drought - Rao-Qiong Yang; Pei-Li Fu; Zaw Zaw; Pieter A. Zuidema; Xiu-Chen Wu; Guang-You Hao; Shankar Panthi; Xin-Hua Peng; Tong-Liang Xu; Hui Zhang; Jia-Yan Shen; Achim Bräuning; et al. (Agricultural and Forest Meteorology, 2026)

Evolving frontiers in drinking water membrane technology: a 25-year bibliometric and antifouling perspective - Zhen-Hua Tian; Ting Yang; Meng-Qi Tian; Peng-Fei Li (Biofouling, 2026)

Reverse Time Migration Imaging of Array GPR Data Based on a 2D CMWCNN Network-Driven Interpolation Strategy - Peng-Yu Li; Hong-Hua Wang; Hong-Zhao Meng; Zhi Zhang (Applied Geophysics, 2026)

PTPσ mediates the integration of grafted neuronal tissueoids with host neural pathways after complete spinal cord injury - Rui Mao; Yuan-Huan Ma; Jin-Yuan Xiao; Qing-Shuai Wei; Yin-Chun Zhao; Qi-Xing Hu; Hou-Ge Li; Ke-Jun Zhang; Lai-Jian Wang; Hui-Juan Shi; Li-Zhi Peng; Jun-Hua Wang; et al. (Science China Life Sciences, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Isolation, structural elucidation, and activities evaluation of proaporphine alkaloids from Thalictrum baicalense - Meng-Yue Yang; Jing-Jing Xue; Zhao-Jing Chen; Xiao-Peng Guo; Shi-Meng Qin; Han-Gao Yang; Fang-Shen Liu; Zhan-Lin Li; Da-Hong Li; Ya-Ting Sun; Hui-Ming Hua (Phytochemistry, 2026)

Long-term groundwater arsenic exposure is associated with altered arsenic methylation capacity and gut microbiota composition in a rural Chinese population - Tingchao He; Jing Liu; Yanyan Li; Nobutaka Ohgami; Xiaoyong Wei; Tingting Peng; Xiaojia Zhang; Ruijun Zhang; Juan Du; Yuqi Deng; Hua Jiang; Ping Zhang; et al. (Journal of Hazardous Materials, 2026)

Fe/Mg-LDH modified biochar for heavy metal soil remediation: Effects on microbial community structure and metabolic activity - Yingchao Li; Qianyu Wang; Zuhao Zhu; Peng Li; Changfeng Qu; Xiaofang Ouyang; Peng Ju; Hua Yin (Journal of Hazardous Materials, 2026)

Decades-long distribution of per- and polyfluoroalkyl substances (PFASs) in global surface waters: Spatiotemporal variability and future trends - Zu-lin Hua; Chang Gao; Peng Guo; Xiao-qing Li; Li Gu (Journal of Hazardous Materials, 2026)

Foliar ammonium nitrogen at booting stage enhances 2-acetyl-1-pyrroline, modulates functional compounds, antioxidant activity, and head rice yield in fragrant rice - Guanhao Huang; Na Chen; Yingling Wu; Fukang Li; Xinyu Chen; Jiemei Peng; Zhilong Chen; Hua Tian; Zhaowen Mo (Food Research International, 2026)

Functional characterization of STING in large yellow croaker (Larimichthys crocea), a pivotal regulator associated with TRIF, TRAF3, IRF3, and IRF7 in modulating antiviral signaling - Yi Lin Li; Jia Xi Zhang; Jun Chun Tang; Ying Li; Xuan Zhu; Jian Zhong Han; Yong Hua Jiang; Yi Lei Wang; Peng Fei Zou (Fish & Shellfish Immunology, 2026)

Associations of prenatal individual and mixture per- and polyfluoroalkyl substances (PFAS) exposures with fetal growth trajectories: Modifying effects of maternal micronutrient status - Zhen-Hua Li; Hai-Yang Weng; Chun-Yong Wang; Xiao-Yu Zhao; Guo-Peng Gao; Kai Huang; Mao-Lin Chen; Fang-Biao Tao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2026)

Identifying critical windows and sex-specific effects of periconceptional exposure to fine particulate matter and temperature on fetal growth trajectories: A longitudinal birth cohort study - Si-Wei Dai; Zhen-Hua Li; Kai Huang; Si-Yu Zhang; Xiao-Yu Zhao; Chun-Yong Wang; Hai-Yang Weng; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Machine learning for uranium separation prediction in smart capacitive deionization: A feasibility review - Zhurui Shao; Xiaoyan Wu; Manlu Cao; Xiaoyun Li; Zhaowen Cheng; Qiong Tian; Dun Wei; Xiaowen Zhang; Yilong Hua; Qi Fang; Ying Peng; Chengzhi Geng; et al. (Desalination, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Intensive management shifts litter decomposition from mycorrhizal to root-dominated pathway in a subtropical bamboo plantation - Wenhao Jin; Jiahe Wang; Jiangfei Ge; Xingcong Ma; Qifeng Wu; Shuai Shao; Chenfei Liang; Liyuan Peng; Xiaomin Ma; Yuchuan Fan; Yongfu Li; Junhui Chen; et al. (Applied Soil Ecology, 2026)

A Cross-Domain Mamba Network with joint spatial-frequency learning for robust SAR oil spill detection - Pu Song; Peng Yu; Xiaojing Zhong; Lihua Wang; Yuanrong He; Guangchun Li; Zhanyang Qi; Hua Su (Marine Pollution Bulletin, 2026)

Effects of Dietary Macleaya cordata Extract on Growth Performance, Antioxidant Capacity, Immunity, and Stress Resistance in Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Fan-Le Jia; Yao-Peng Lu; Ze-Long Zhang; Xiu-Xia Zhang; Pei-Hua Zheng; Jun-Tao Li; Ying-Hui Liang; Dan Mu; Jian-An Xian (Fishes, 2026)
High-density, intensive aquaculture has led to the deterioration of the aquatic environment, which compromises the survival, immune function and disease resistance of aquatic animals. This study investigated the effects of dietary supplementation with different levels of Macleaya cordata extract (MCE) on growth performance, muscle composition, antioxidant capacity, immune function, and stress resistance in red claw crayfish (Cherax quadricarinatus). Juvenile crayfish with an initial body weight of 0.22 ± 0.02 g were fed diets supplemented with 0 (Diet 1, Control), 0.01 (Diet 2), 0.02 (Diet 3), 0.04 (Diet 4), 0.08 (Diet 5), and 0.15 (Diet 6) g/kg MCE for eight weeks. Results showed that dietary MCE supplementation had no significant effect on the growth performance or muscle composition of crayfish. Conversely, supplementation with 0.02–0.04 g/kg MCE significantly increased the activities of superoxide dismutase (SOD), glutathione peroxidase (GPx), phenoloxidase (PO), and the total antioxidant capacity (T-AOC) in the hepatopancreas and plasma, while significantly reducing malondialdehyde (MDA) levels. Specifically, supplementation with 0.04 g/kg MCE significantly upregulated the hepatopancreatic mRNA expression levels of SOD, hemocyanin, GPx, and selenium-dependent glutathione peroxidase (Se-GPx). Furthermore, the challenge test demonstrated that supplementation with 0.04 g/kg MCE significantly improved crayfish survival under microcystin-LR (MC-LR) stress. Overall, supplementation with 0.04 g/kg MCE significantly improved the antioxidant capacity, immunity, and stress resistance of crayfish, suggesting its potential as an environmentally friendly immunostimulatory feed additive to protect against MC-LR stress in crayfish.

Linking the dietary inflammation index to sarcopenia in diabetes: mediation by body roundness index and evidence from complementary analyses - Yang Yang; Ren-hua Lv; Peng-min Liu; Yan-qiu Sun; Lu-ping Wang; Yu Yu; Li-mei Zhang; Xin-yang Zhang (European Journal of Applied Physiology, 2026)

UAV-based crop pest and disease monitoring: A review of multi-source sensing and intelligent methods - Jie Guo; Jin-Hai Li; Le Dong; Shun-Yu Wang; Guang-Yue Wu; Yu-Peng Zhang; Chang-Yong Tao; De-Hua Gao; Shu-Ming Yang; Yu-Tan Wang (Computers and Electronics in Agriculture, 2026)

A single-cell transcriptomic atlas of the spotted scat testis reveals two Sertoli cell subclusters with differential dmrt1Y expression - Yu Li; Mou-Yan Jiang; Shan-Ni Cao; You-Xing Peng; Yuan-Qing Huang; Hong-Juan Shi; Hua-Pu Chen; Tian-Li Wu; Dong-Neng Jiang (Aquaculture, 2026)

Decoding molecular switches mediating uranium speciation transition in iron-based mineral dynamic phase evolution - Bin Xie; Dun Wei; Qiong Tian; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Journal of Hazardous Materials, 2026)

Artificial grassland establishment alters soil metabolomes by reshaping multi-domain microbial networks - Bo Wang; Chao Peng; Hua Li; Zhuo Duan; Jianan Li; Xue Yang; Xiaoyun Wang; Tao Wang; Chuangxin Wang; Jiande Li; Wenliang Li; Guoying Zhou (Journal of Environmental Management, 2026)

A novel mitochondrial OMA1-DELE1-HRI axis mediates polystyrene microplastics-induced blood-testis barrier dysfunction - Rong Wang; Zhen Tian; Chen Chen; Ming-Ming Zhang; Ding-Qiang Peng; Ke-Xin Liu; Yu-Tong Ren; Shuai Lin; Qiang Hong; Yan-Li Ji; Yuan-Hua Chen (Journal of Environmental Sciences, 2026)

Insights into the impact of electron beam irradiation on the quality of red adzuki beans and the characteristics of their isolated starch - Shanshan He; Min Li; Sifan Yang; Naiwei Peng; Yanyan Zhang; Hongwei Wang; Xingli Liu; Huishan Shen; Hua Zhang (Food Chemistry, 2026)

Deciphering the molecular regulatory mechanism underlying behavioral disorders and cardiac damage in Eriocheir sinensis under saline-alkaline environment - Meiyao Wang; Pao Xu; Jianlin Li; Guoan Hua; Bo Peng; Yuqing Wu; Jun Zhou; Yongkai Tang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A multi-functional passive fixation lead for diagnosis and treatment of cardiac diseases - Xuandi Deng; Yiran Hu; Puqing Yao; Chunhong Yu; Juwei Yang; Ruizeng Luo; Sijing Cheng; Hao Huang; Peng Cheng; Lei Jia; Xingyao Lv; Menghan Li; et al. (Chemical Engineering Journal, 2026)

A layered approach to secure the safety and therapeutic efficacy of hiPSC-derived functionalized neuronal tissueoid for repair after complete spinal cord lnjury in rats - Qing-shuai Wei; Quan-ying Xing; Yuan-huan Ma; Ke-jun Zhang; Wen-tao Ma; Mei-ling Zhang; Hui-juan Shi; Li-zhi Peng; Jun-hua Wang; Qi-xing Hu; Hou-ge Li; Ying Liu; et al. (Chemical Engineering Journal, 2026)

Biomimetic platform integrating therapeutic exosomes and stretch reverses lumbar disc herniation through multi-targeting accurate regulation - Yang Xu; Yu-Da Liu; Jia-Wen Zhan; Hao-Bin Wang; Xiao-Feng Li; Li-Guo Zhu; Li-Hua Peng (Chemical Engineering Journal, 2026)

Independent and joint effects of ambient temperature and relative humidity on fetal distress: effect modification by air pollutants - Hua Xiao; Yi Wang; Zongli Qi; Ziwei Ye; Liping Li; Li Mao; Peng Hu; Yuefei Li; Haoyun Zhang; Yao Cheng; Hao Wang; Ping Chen; et al. (International Journal of Biometeorology, 2026)

Water-quality responses and management-oriented spatial thresholds in a complex river-estuary continuum - Jiang Wu; Tang Liu; Dian-Bao Li; Li-Juan Zhang; Hua-Peng Qin; Wei-Ling Sun; Nan Xu (Water Research, 2026)

Chemical constituents from the stem of Nauclea officinalis and their anti-inflammatory activities - Bo Wen Wan; Ting Wang; Xiong Bo Zhu; Rui Hua Xu; Hao Fu Dai; Wen Li Mei; Fei Wu; Xiao Ying Peng; Sheng Zhuo Huang (Phytochemistry Letters, 2026)

Case study: Metagenomic analysis of microbial restructuring and nitrogen metabolism under probiotic and Chinese herb applications during post-antibiotic-ban shrimp farming - Yingjie Li; Peng Li; Hua Li; Linlan Zhuang; Lushan Wang (Journal of Environmental Management, 2026)

Finite-strain modelling of PVD-assisted consolidation in clayey soils using a novel elastic–viscoplastic model with destructuration based on the equivalent time concept - Peng-Lin Li; Zhen-Yu Yin; Ze-Jian Chen; Jian-Hua Yin (Geotextiles and Geomembranes, 2026)

Breaking oxidative interference: Electro-induced uranium incorporation into magnetite for nitrate‑uranium co-contaminated wastewater remediation - Dixiao Xu; Qiong Tian; Dun Wei; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Desalination, 2026)

Transparent superhydrophobic high-emissivity coatings for synergistic self-cleaning and passive cooling of photovoltaics - Li Wan; Yan Yang; Chao-Hua Xue; Xiao-Jing Guo; Pan Lu; Jing-Jing Peng (Chemical Engineering Journal, 2026)

Bioactive electrospun membrane with DHBA/Zn-MOF for enhancing neurovascular coupling in diabetic wound healing - Manjuan Li; Peng Hua; Linsa Zhou; Lexuan Fang; Pingping Ma; Zixuan Wang; Shicui Jiang; Qiang Zhou; Gaowen Li; Xudong Zheng; Chi Zhang; Litai Jin; et al. (Chemical Engineering Journal, 2026)

Nanocellulose-reinforced deep eutectic solvent-based smart hydrogel sensor for adaptive window regulation and machine learning-assisted low-temperature motion monitoring - Zhenchun Li; Yucong Sun; Jiarui Shen; Rongfeng Ge; Jieli Hua; Zhiyuan Zhao; Ning Li; Yunqi Peng; Jiaqi Hou; Hong Zhang; Lei Wang (Chemical Engineering Journal, 2026)

Construction and Application of Traditional Chinese Medicine Knowledge Graph Based on Large Language Model - Bo Zhang; Ruifang Li; Kedong Yin; Shuo Hua; Shiyu Li; Mengwan Jiang; Haoping An; Peng Li (Interdisciplinary Sciences: Computational Life Sciences, 2026)

Coupled Saline Lacustrine OM Enrichment Difference Response to the Sedimentary Environment: Evidence from Elements, Sedimentary Biomarkers and Isotopes - Biao Sun; Xiaoping Liu; Xiaoguang Li; Murray Gingras; Yongcheng Chen; Chang Chen; Tian Liu; Yu Yuan; Wendi Peng; Zuxian Hua (Journal of Earth Science, 2026)

Enhancing photosynthesis and stress tolerance of the cyanobacterium Nostoc sphaeroides by adaptive laboratory evolution via dry-wet cycles - Zhen Chen; Rui Liu; Yu-Qing Peng; Zhang-Zhuo-Ya Wang; Yong-Qi Yin; Sheng Du; Yu-Jie Jin; Kui Xu; Fei-Fei Li; Wei-Zhi Li; Shan Zhang; Hua-Hua Yue; et al. (Algal Research, 2026)

Genetic analysis and reproductive interventions in families affected by congenital cataracts: a study of 107 cases - Yun-hao Li; Qi Wang; Yao Peng; Juan Du; Liang Hu; Zhen-hua Tan; Feng Gu; Hao Hu; Qian-jun Zhang; Ge Lin; Guang-xiu Lu; Yue-Qiu Tan; et al. (Journal of Applied Genetics, 2026)

Targeting flagellar-mediated virulence: The lipopeptide PW-1 suppresses pathogenicity in Ralstonia solanacearum - Hua Wang; Shili Li; Tao Liu; Lei He; Ruiyu Yang; Xiaoshuang Peng; Meng Liu; Nima Qiongda; Xiaoqi Wu; Qian Li; Jian Zhang; Huidi Liu; et al. (Pesticide Biochemistry and Physiology, 2026)

Risk assessment and exposure patterns of hydroxypolycyclic aromatic hydrocarbons in elderly population: Insights from urinary metabolite levels and dietary habits - Yafei Gao; Biwen Wang; Liting Hua; Juanhua Li; Junqi Liu; Yang Peng; Lu Cheng; Hongkai Zhu; Hongwen Sun; Han Li; Hongzhi Zhao (Journal of Environmental Sciences, 2026)

Windows of susceptibility and the modifying role of residential greenness in the association between prenatal exposure to non-optimal temperatures and infant BMIZ trajectories - Zhen-Hua Li; Si-Wei Dai; Chun-Yong Wang; Hai-Yang Weng; Xiao-Yu Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Pollution, 2026)

Machine learning-driven lipase engineering for highly enantioselective synthesis of chiral florfenicol intermediate via enzymatic resolution-chemical racemization coupling system - Jing-Peng Li; Hui-Hang Zhang; Zeng-Hua He; Jun-Bo Tian; Ren-Chao Zheng; Xiao-Ling Tang; Yu-Guo Zheng (Chemical Engineering Journal, 2026)

Determinants of the variability of PGPB effects on zinc biofortification and crop yield: a meta-analysis - Hua He; Lu Peng; Jinzhi Liu; Fangchi Yang; Xiu Li; Qin Lan; Xiaoyan Tang; Yanyan Zhang; Bing Li; Changquan Wang; Yingjie Wu (Plant and Soil, 2026)

Model-based insights into temperature-driven declines in groundwater recharge under global warming in Michigan’s Lower Peninsula - Jing Zhang; Si-Chen Wu; Shu-Guang Li; Hua-Sheng Liao; Shi-Tao Peng; Jian-Min Zhang (Hydrological Sciences Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Mechanistic insights into uranium release during long-term structural evolution of uranium-doped magnetite - Wei Xu; Qiong Tian; Dun Wei; Dan Huang; Zhaowen Cheng; Xiaoyan Wu; Yilong Hua; Ying Peng; Xiaowen Zhang; Mi Li (Journal of Environmental Sciences, 2026)

Therapeutic effects of Gardenia jasminoides Ellis on salpingitis in laying hens: mechanisms of inflammatory regulation and egg quality improvement - Ruo-Yi Zhang; Hua-Lin Peng; Wei Zhang; Rong-Qiang Li; Hong-Jie Cui; Jian Li (Veterinary Research Communications, 2026)

Research on a complex start-up control strategy for power-shift tractors based on rule mapping and multi-mode model predictive control - Li-Quan Lu; Ze-Peng Zhang; Guang-Lin Zhang; Hao-Ran Yang; Zhong-Xiang Zhu; Zheng-He Song; Zhi-Qiang Zhai; Jian-Hua Wang; Chuan-Chuan Zhang (Computers and Electronics in Agriculture, 2026)

In vitro screening and in vivo evaluation of anti-virulence herbal compounds against Streptococcus agalactiae in tilapia (Oreochromis niloticus) - Ming-Li Xiang; Zi-Chen Zhao; Gui-Hua Li; Wei Tang; En-Peng Chen; Shui-Feng Qin; Yan Wang; Heng-Wei Deng; Zhi-Hong Zhong; Yun Sun; Wei-Liang Guo; Yong-Can Zhou (Aquaculture, 2026)

High-resolution stalagmite records from Southwest China reveal a North Atlantic link to the 8.2 ka event - Xiao-Hua Shao; Xiao-Hong Zhao; Peng-Fa Li; Kan Zhao; Xing-Gong Kong; Yong-Jin Wang; Hai Cheng (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Genomic insights into stepwise selection reshaping fruit traits and male-biased selection driving hermaphroditism in papayas - Changmian Ji; Ruizong Jia; Yuliang Zhang; Xiaoxi Du; Xueying Huang; Huiliang Li; He Dai; Yu Wang; Qian Jiang; Zhengnan Xie; Shanshan Huo; Yang Cao; et al. (Molecular Plant, 2026)

A study on the susceptibility of Helice tientsinensis to infectious hypodermal and hematopoietic necrosis virus (IHHNV) - Meifeng Wang; Xiuhua Wang; Jie Huang; Chen Li; Qingli Zhang; Xinyu Lian; Ruoxuan Lu; Hua Xu; Xinyi Fu; Ziyue Gou; Peng Jia; Bing Yang (Journal of Invertebrate Pathology, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

Study on the mechanism evolution of carbon structure during blending coal coking - Hanwen Zhu; Peng Yu; Xinni Zhao; Lu Tian; Hua Li; Xingxing Chen; Jinxiao Dou; Jianglong Yu (Fuel, 2026)

Geographic variation in ginger-derived nanovesicle lipids identifies chiral protein recognition as a determinant of B-cell internalization - Zhuo Chen; Qiang Liu; Hua Feng; Xinyi Zhang; Liuliu Luo; Pingduo Chen; Jinnian Peng; Fangfang Min; Yunpeng Shen; Jingjing Li; Yongning Wu; Hongbing Chen (Food Research International, 2026)

Competition release dominates growth recovery of four subtropical broadleaved tree species following an extreme snow event - Tong-Liang Xu; Rao-Qiong Yang; Zaw Zaw; Shankar Panthi; Xin-Hua Peng; Ju-Mei Zhang; Pei-Li Fu; Ke-Yan Fang; Ze-Xin Fan (Forest Ecology and Management, 2026)

Long-term incorporation of straw and organic fertilizer can achieve agricultural sustainability by improving wheat productivity and reducing environmental pollution - Peng Wu; Chuankang Yang; Linshuai Li; Zeyu Liu; Jinyu Yu; Hua Huang; Tie Cai; Zhikuan Jia; Zhiqiang Gao; Peng Zhang (Field Crops Research, 2026)

Prenatal and postpartum residential greenness and behavioral development in early Childhood: Findings from a birth cohort - Wen-Chi Chao; Ming-Lun Zou; Chih-Da Wu; Jian-Pei Huang; Heng-Kien Au; Chen-Li Lin; Shih-Peng Mao; Hsing-Jasmine Chao; Ling-Chu Chien; Hsueh-Wen Hsu; Pilyoung Kim; Yi-Hua Chen (Environmental Research, 2026)

In-situ ferrous oxalate coating strategy activates nano zero-valent iron for enhanced U(VI) Removal: Efficacy and reaction mechanism - Yanan Xiao; Xiaowen Zhang; Huiran Tang; Siyu Zhang; Xiaoyan Wu; Yilong Hua; Zhaowen Cheng; Mi Li; Ying Peng (Desalination, 2026)

Bio-template synthesis of graphitized carbon-decorated Fe2O3 hierarchical tubes for high-response and low-temperature H2S detection - Ming-Yan Cao; Hui-Nan Lei; Hui-Ye Jiang; Ya-Nan Li; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2026)

Flexible thiol–ene crosslinked reduced graphene oxide-functionalized styrene-butadiene-styrene films with enhanced thermal conductivity and electromagnetic interference shielding efficiency - Xinyu Liu; Xiaohui Lv; Chuang Peng; Linzhe He; Yibo Zhang; Song Lei; Guo-Hua Hu; Zhehong Lu; Tao Ding; Xiaohong Li; Zhijun Zhang (Chemical Engineering Journal, 2026)

Seismic Data Reconstruction and Noise Suppression Based on an Improved Weighted Fast Projection onto Convex Sets Algorithm - Gao-peng Cheng; Hua Zhang; Hong-xing Li; Yu Song; Ming Yue; Kai-dong Zhang (Applied Geophysics, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

Pathogenicity of Porcine reproductive and respiratory syndrome virus in the reproductive system of female piglets: Pathological damage to the uterine horns and developmental arrest - Yi-Xin Yan; Ying Guan; Lei Zhao; Han-Yu Li; Tong Xu; Li-Na Shao; Si-Yuan Lai; Yi Qing; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; et al. (Veterinary Microbiology, 2026)

Long-term waterproof performance of EPDM sealing gaskets considering aging-induced stress relaxation - Hua-Yong Li; Huai-Na Wu; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Phragmalin-type limonoid orthoesters from the twigs and leaves of Khaya ivorensis and their cytotoxic activities - Zong-Yi Zhang; Jia-Nan Wang; Peng Sun; Xiao-Cui Shi; Yi-Dian Xiao; Kai-Long Ji; Chun-Fen Xiao; Xiao-Nian Li; You-Kai Xu; Dong-Hua Cao (Phytochemistry, 2026)

A single-cell-resolution spatial transcriptomic atlas decodes wheat spike development and yield potential - Xiang Zhang; Yi Peng Wang; Xiehai Song; Liang-Zi Zhou; Haixia Yu; Lei Yang; Yan Kai Wang; Xin Yu Wang; Xin Yan Wan; Yongqi Liu; Yan Shi; Zhiliang Yue; et al. (Molecular Plant, 2026)

Enhanced removal of anionic Per- and polyfluoroalkyl substances (PFAS) by electrically assisted nanofiltration: Operational parameter optimization and mechanistic insights - YuTing Hua; Yu Li; Peng-Fei Li; BeiBei Chai; ZhiXuan Zhou; JingYi Wu (Journal of Hazardous Materials, 2026)

Intelligent control of food waste composting based on PID and LSTM: analysis and comparison of strategies - Jufei Wang; Xuesong Peng; Wenbin Tang; Xueru Zhu; Chao Li; Shilong Qiu; Hanpeng Liao; Chen Liu; Samuel Mbugua Nyambura; Yao Wu; Hua Li; Shuhe Zheng (Journal of Cleaner Production, 2026)

From phosphate adsorption to soil remediation: utilizing spent Fe/Mg-LDH-biochar for concurrent heavy metal immobilization and phosphorus supply - Yingchao Li; Juntan Wang; Zhanyu Guo; Xiaofang Ouyang; Peng Ju; Hua Yin (Journal of Environmental Chemical Engineering, 2026)

Intelligent control for food waste composting using observation–assessment–decision–action cycles: From technical landscape to economic stability analysis - Jufei Wang; Xuesong Peng; Wenbin Tang; Xueru Zhu; Chao Li; Hanpeng Liao; Chen Liu; Wuxiong Weng; Zheming Cui; Shuhe Zheng; Hua Li (Journal of Environmental Management, 2026)

Machine learning combined with the PMF model reveals the sources and driving factors of PAHs and Cl-PAHs in urban runoff - Li Li; Hai Huang; Pei Hua; Tao Chen; Jin Zhang; Peng Deng; Zongxi Zhao; Bo Yan (Journal of Environmental Sciences, 2026)

Dual efficient X-ray scintillation and strong second harmonic generation in a single cubic alkane Cu4I4 cluster achieved through organic-inorganic synergistic effect - Bao-Yi Li; Jun-Zhe Li; Wen-Fei Wang; Peng-Kun Wang; Rong Li; Shuai-Hua Wang; Fa-Kun Zheng; Guo-Cong Guo (Chemical Engineering Journal, 2026)

Tailoring Pd2+-2Z sites in Pd/SSZ-13 via Mn ion incorporation to enable NO passive adsorption transition - Hao Li; Zhen Hua; Chao Zhang; Wenming Liu; Jian Ji; Guobo Li; Honggen Peng (Chemical Engineering Journal, 2026)

YIP: optimized YOLOv11-seg for accurate intramuscular fat percentage prediction in pigs using non-invasive ultrasound imaging - Junhao Zhang; Hang Jiao; Genyuan Li; Hanhan Li; Chenglin Li; Pengsheng Dong; Yan Liu; Bo Jiang; Peng Shang; Feng Yang; Chunli Li; Xinjian Li; et al. (Science China Life Sciences, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Cataract Aggravates Alzheimer-Like Pathologies and Cognitive Deficits in an APP/PS1 Mouse Model - Zhao Geng; Zhong-Yuan Yu; Jun Tan; Xuan-Yue Wang; Gui-Hua Zeng; Jiang-Hui Li; Yu-Di Bai; Xiao-Qin Zeng; Yu-Peng Zhu; Cheng-Rong Tan; An-Yu Shi; Yu-Hui Liu; et al. (Neuroscience Bulletin, 2026)
Clinical investigations have suggested a potential link between cataracts and Alzheimer’s disease (AD). However, whether cataract has an impact on the progression of AD remains unclear. The objective of this research was to determine the relationship between cataracts and AD. A cataract model was established in APP/PS1 [mutant amyloid precursor protein (APP) and a mutant presenilin-1 (PS1) gene] mice via lens puncture. Behavioural assays were used to evaluate cognitive function. Immunohistochemistry, immunofluorescence, and enzyme-linked immunosorbent assays (ELISA) were applied to detect AD-related pathology. Visual signals were markedly obstructed following surgery to induce cataracts, and these mice presented an increased cerebral amyloid-beta (Aβ) load, while no significant alterations in the levels of enzymes associated with Aβ metabolism were detected. In addition, compared with control mice, cataract model mice presented increased astrogliosis and microgliosis, along with elevated levels of proinflammatory factors. Moreover, cataract model mice presented more pronounced cognitive impairments than did control mice. Our study offers experimental confirmation that cataract considerably contributes to the pathogenesis of AD, thereby emphasizing the importance of visual signals in maintaining cognitive well-being.

Enhanced carbohydrate metabolism in subdominant microbes drives rice straw decomposition under nitrogen addition: A four-month study in winter - Na Zhang; Longtao Li; Chunhua Dong; Zhongxiu Rao; Hua Peng; Fengqiu Huang (Applied Soil Ecology, 2026)

Fluid chemistry and isotopes for interpreting the formation of geothermal systems in the southern Qinghai-Xizang Plateau - Xingze Li; Yuankang Zhong; Peng Zhou; Gongxi Liu; Hua Wu; Ying Wang; Xiaoyan Zhao; Xingcheng Yuan; Jinhang Huang; Yunhui Zhang (Applied Geochemistry, 2026)

Enhancing oil-water separation via droplet coalescence regulated by particle self-rotation in swirling fields - Wei Zhao; Ao-song Wei; Shu Zhu; Tong Zhang; Peng-bo Fu; Jian-ping Li; Xue-jing Yang; Hua-lin Wang (Water Research, 2026)

Prediction on the waterproof performance of EPDM gaskets in shield tunnels considering the stress state of compression and tension - Ren Wu; Huai-Na Wu; Hua-Yong Li; Xin-Xin Yang; Dong-Lin Feng; Hong Cao; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2026)

Current population status, challenges and prospects of the endangered white-lipped deer endemic to the Qinghai-Tibet Plateau - Yuangang Yang; Yu Zhao; Hua Li; Peng Luo; Bin Li; Tongzuo Zhang; Hao Liu; Zhangqiang You (Journal for Nature Conservation, 2026)

Anti-diabetic properties of yellowfin tuna protein hydrolysates and identification and screening of novel anti-diabetic peptides against α-amylase and DPP-IV - Xiangtan Zhao; Peng Wan; Deke Chen; Bingna Cai; Hua Chen; Jun Li; Si Li; Ailing Duan; Ru Li; Si Zhang; Jianyu Pan (Food Chemistry, 2026)

Characterization of monoclonal antibody against IgM and phagocytic function of IgM+ B cells in snakehead (Channa argus) - Peng Fei Mu; Zhe Wang; Qi Li; Qiu Hua Li; Lan Hao Liu; Pin Nie (Fish & Shellfish Immunology, 2026)

Glycogen Synthase Kinase-3β Inhibition Ameliorates Synaptic and Mitochondrial Dysfunction in a Sporadic Alzheimer’s Disease–Like Model - Ya-Han Wang; Peng-Li Ding; Hao Qin; Kai-Xin Zhang; Jin-Wen Ge; Da-Hua Wu; Le Xie; Kun Liang (Molecular Neurobiology, 2026)

QTL analysis of single-segment substitution lines dissected from a rice CSSL-Z668 and fine-mapping of qGL3.4 for grain length - Si-Qian Xiang; Yu-Zhu Tao; Zhao-Peng Yu; Zhuo-Wen Zhao; Han Zhang; Qiao-Long Li; Lu Li; Ao-Ni Xiang; Jing-Hong Xu; Fan Zhang; Xu Yan; Zheng-Lin Yang; et al. (Euphytica, 2026)

Cloning, heterologus expression and characterization of a thermophilic and salt tolerant GH11 xylanase from Allostreptomyces psammosilenae YIM DR4008T - Xin-Wei Li; Dan Zhu; Lei Li; Run-Feng Yang; Shi-Yuan Fan; Zhi-Hua Lv; Meng-Di Rao; Rong-Huang Song; Peng Sang; Yi-Rui Yin; Li-Quan Yang (Antonie van Leeuwenhoek, 2026)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

C-glycosylated and alkylated flavonoids with potent anti-inflammatory activity from the whole plants of Drymaria cordata - Lan-Yi Lu; Yan-Hua Wu; Peng Zhang; Li-Yan Wang (Phytochemistry, 2025)

Coupling distributed hydrological model with spatially discrete altimetry data for distributed prediction in ungauged basins - Mengran Tang; Lihua Xiong; Hua Chen; Jie Chen; Peng Shu; Shuang Li; Yunye Feng (Journal of Hydrology, 2025)

Endangered dhole in China: Population status, conservation predicament and future direction - Yuangang Yang; Yu Zhao; Hua Li; Peng Luo; Zhangqiang You (Journal for Nature Conservation, 2025)

Antioxidant and xanthine oxidase inhibitory theoretically evaluation of ferulic acid oligomers: Tetramers as outstanding dual-functional candidates - Qing-Hua Lu; Bai-Ze Liu; Jun Lu; Han Gao; Guo-Ze Wang; Jun-Li Lv; Xiao-Jun Li; Hui-Ying Peng (Food Bioscience, 2025)

Functional characterization of two Caspase-1 transcripts that associated with ASC and NLRC3 in apoptosis and inflammatory response in large yellow croaker Larimichthys crocea - Qiu Yu Hu; Kun Huang Han; Qiu Ye Huang; Wen Feng Cui; Qiao Yun Yang; Yi Dan Liu; Shang Qi Zhao; Xian Yuan Zeng; Ying Li; Wen Qi Zha; Yi Lei Wang; Yong Hua Jiang; et al. (Fish & Shellfish Immunology, 2025)

An innovative intimately coupled photocatalysis and biodegradation system for simultaneous removal of emerging contaminants and nitrate - Shi-Ming Niu; Thangavel Sangeetha; Xue-Dong Zhang; Wei-Mon Yan; Peng-Fei Li; Jiří Ryšavý; Jakub Čespiva; Min-Hua Cui (Chemical Engineering Journal, 2025)

Genome-Wide Identification and Expression Analysis of β-Ketoacyl-CoA Synthase Family in Sugarcane (Saccharum spontaneum) - An-zi Li; Xin Peng; Yuan Huang; Zhao-fu Bi; Ming-jing Liao; Mu-qing Zhang; Sheng-hua Xiao (Tropical Plant Biology, 2025)

Single-cell RNA sequencing of neonatal cortical astrocytes reveals versatile cell clusters during astrocyte-neuron conversion - Jiaxue Cha; Peng Zeng; Hui Zong; Jiayi Zhao; Jiayao Chen; Haowei Zuo; Bowen Zhang; Changjie Shi; Jing Li; Qiuhong Hua; Zixin Wang; Yujun Hou; et al. (Molecular Biology Reports, 2025)

Correction: Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Optimizing phosphorus management in subtropical red soil sloping croplands: The synergistic effects of contour cultivation and straw return - Ying Zhang; Ji Liu; Longtao Li; Changjun Li; Pofei Wang; Zhongxiang He; Peng Cheng; Jianjun Luo; Hua Peng; Jian Zhu (Agriculture, Ecosystems & Environment, 2025)

Research on the Reinforcement Effect of the Elephant-Foot Method in Aeolian Sand Tunnels - Ji-hua Qin; Xi-peng Li; Ya Wang; Xiao-li Cao; Dong Li; Yi-guo Xue; Fan-meng Kong; Hui-min Gong; Bang-xiang Li; Chao Lu; Guang-kun Li (Applied Geophysics, 2025)

Comprehensive Geophysical Characteristics and Exploration Significance of the Xiarihamu Super-Large Copper-Nickel Deposit in the East Kunlun Metallogenic Belt - Ji-en Dong; Bao-chun Li; Tao Wang; Yu-long Li; Xiao-jun Dong; Fu-chun Wang; Hai-kui Tong; Zhen-hua Zheng; Hua Li; Peng Wang (Applied Geophysics, 2025)

Application of a deep learning model with physical model constraints and attention mechanism for state prediction in high-power power-shift tractors - Li-quan Lu; Ze-peng Zhang; Guang-lin Zhang; Bing Han; Hao-ran Yang; Zhong-xiang Zhu; Zheng-he Song; Zhi-qiang Zhai; Jian-hua Wang; Chuan-chuan Zhang (Computers and Electronics in Agriculture, 2025)

Understanding clouds and precipitation over the Mount Qomolangma: how does the aerosol activation effect exist? - Xiangde Xu; Wenyue Cai; Tianliang Zhao; Hua Zhang; Xueliang Guo; Wenqing Liu; Tianshu Zhang; Runze Zhao; Chong Wu; Yueqing Li; Lei Wang; Peng Yan; et al. (Science Bulletin, 2025)

Edge-detection-driven first-arrival picking method for borehole radial velocity imaging - Peng Li; Zhilong Fang; Hua Wang (Journal of Applied Geophysics, 2025)

Characterization of vB_SaRS_FS19–1, a newly isolated broad-host-range and virulent bacteriophage infecting Staphylococcus aureus and its application in foods - Xinyan Yao; Chaoxiang Jia; Ting Qin; Dai Peng; Linlin Huang; Yi Liu; Saiyu Zhang; Yingqian Han; Yanbin Yang; Heping Li; Hua Wu; Guoyu Yang; et al. (Food Chemistry, 2025)

Bifunctional metal-organic framework Nanozymes with flexibly tunable valence states for dual-mode detection of organophosphorus pesticides - Mai Luo; Yao Peng; Jihai Cai; Tiantian Jiang; Sheng Gong; Shiyao Hua; Ting Wang; Sijia Wu; Shuangpeng Wang; Jinchao Wei; Peng Li (Food Chemistry, 2025)

Orthogonal functional group tagging combined with computational retention time prediction for discovering furan fatty acids in plant oils - Hua-Ming Xiao; Xiao-Hui Peng; Shuai Zhao; Dilshad Hussain; Qin-Feng Zhang; Jian-Li Chen; Dan Luo; Fang Wei; Xian Wang (Food Chemistry, 2025)

Associations between prenatal exposure to air pollution and infant growth trajectories in the first two years: Exploring potential sexual dimorphism and sensitive windows - Zhen-Hua Li; Si-Wei Dai; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; Xiu-Jun Zhang (Environmental Research, 2025)

Platinum-copper nanocubezyme facilitate spinal cord recovery via synchronously alleviating oxidative stress and mitigating BNIP3-mediated mitochondrial dysfunction - Xiangge Liu; Cheng Peng; Huiyi Yang; Jiajun Deng; Ping Wu; Yongchun Xiao; Li Wan; Ke Wang; Guowei Zhang; Hua Yang; Jianyu Zou; Judun Zheng; et al. (Chemical Engineering Journal, 2025)

Eco-friendly taro stem-sourced cellulose/polypyrrole hybrid aerogel: An efficient capture strategy for microplastics removal - Wei-peng Qiu; Hai-ze Su; Hao Su; Shao-hua Luo; Li-shan Lai; Jia-le Zhu; Zhen-lin Xu; Hong Wang; Peng Wen (Chemical Engineering Journal, 2025)

Rhizosphere microbiota modulate cadmium mobility dynamics and phytotoxicity in rice under differential Cd stress - Linxiu Cheng; Zhenling Li; Lijun Zhou; Jie Xie; Qiangqiang Zhou; Mingjun Ding; Peng Wang; Hua Zhang; Minghua Nie; Gaoxiang Huang (Plant and Soil, 2025)

Pre-action Neuronal Encoding of Task Situation Uncertainty in the Medial Prefrontal Cortex of Rats - Qiulin Hua; Yu Peng; Jianyun Zhang; Baoming Li; Jiyun Peng (Neuroscience Bulletin, 2025)

Oxymatrine possibly inhibits differentiation and maturation of oligodendrocytes in the remyelination of the toxin-induced demyelination animal model - Mei Li; Fei Huang; Jian Song; Renzhang Liang; Zhongwei Zhou; Yinglan Lin; Lili Hu; Jinghai Gu; Hua Yang; Shaozhang Hou; Huisheng Ma; Peng Wang (Metabolic Brain Disease, 2025)

Integrated transcriptomic and metabolomic revealed the effect of salicylic acid treatment on improving the storability of ‘Ventura’ celery - Pei-Zhuo Liu; Ya-Hui Wang; Li-Xiang Wang; Yong-Ju Wei; Yue-Hua Sun; Xu Sun; Chen Chen; Ya-Peng Li; Ai-Sheng Xiong (Postharvest Biology and Technology, 2025)

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

A possible biotic precursor, Archaeodunaliella junggarensis n. gen. n. sp., in the Upper Paleozoic Fengcheng Formation from Junggar Basin, Northwest China - Li-Ye Zhu; Hua Zhang; Tian-Ming Shi; Peng Tang (Palaeoworld, 2025)

Electrochemical membrane bioreactors for wastewater treatment: Mechanisms of membrane fouling control and applications to refractory pollutants - Shuli Liu; Yatong Gao; Xiaohong Han; Jiajun Hua; Yuhong Zhang; Glen T. Daigger; Qi Li; Ning Guo; Xiao Mi; Jia Kang; Peng Zhang (Journal of Environmental Chemical Engineering, 2025)

Magnetic CoNi@CN for efficient synergistic removal of tetracycline: Bimetallic electronic synergy and non-radical pathway - Peng Li; Sujuan Chen; Yu Kang; Yu Han; Lianghu Su; Chaoqun Tan; Longjiang Zhang; Saier Wang; Hua Wu (Journal of Environmental Chemical Engineering, 2025)

Mechanical performance analysis of fully grouted bolts considering yield and hardening characteristics - Akang Li; Hua Cheng; Zhongwen Yue; Chuanxin Rong; Peng Wang; Jian Lin (International Journal of Rock Mechanics and Mining Sciences, 2025)

The influence of pulsed electric fields with different waveforms on the extraction of valuable compounds from microalgae - Liuxia Li; Yifan Gao; Zihuang Peng; Xun Pei; Ruorong Hua; Fuchang Lin; Rui Zhang; Yi Liu (Innovative Food Science & Emerging Technologies, 2025)

Virtual screening and molecular mechanism of novel anti-benign prostatic hyperplasia peptides from Syngnathus schlegeli - Ailing Duan; Xiangxi Yi; Xiangtan Zhao; Si Li; Xinjian Qu; Geng Qin; Qiang Lin; Hua Chen; Peng Wan; Deke Chen; Xin Chen; Weimao Zhong; et al. (Food Research International, 2025)

New insight into quality changes in bread dough under different state/phase transitions during frozen storage - Jin-Hong Zhao; Jing-Wei Li; Zhen-Hua Wang; Hong-Wei Xiao; Shyam S. Sablani; Sai Zhang; Yi-Jiao Peng (Food Hydrocolloids, 2025)

Transcriptomic evidence from peripheral blood reveals nonlinear gene expression trajectories of aging in female rhesus macaques - Chong-Jun Weng; Long-Bao Lv; Li-Qin Yang; Long Zhao; Zheng-Fei Hu; Si-Yu Ma; Yi-Jiang Li; Wen-Xian Xiao; Yun Wang; Xin-Tian Hu; Gong-Hua Li; Qing-Peng Kong (Science China Life Sciences, 2025)

Association Between Whole Blood Iron and Nonalcoholic Fatty Liver Disease in Elderly: A Case–Control Study - Zhe-Ying Jiang; Wei-Jia Meng; Ying Wang; Hua-Qin Su; Bi-Xiu Mao; Cai-Li Wang; Feng-Lian Peng; Cui-Ping Li; Lian-Ping He (Biological Trace Element Research, 2025)

A Typical Riedel Shear Pattern of Active Faults in the Laolongwan Basin, Northeastern Tibetan Plateau - Kai-Xun Wang; Xiao-Gang Li; Wei Shi; Xiang-You Feng; Qian Yang; Jie Li; Zheng-Jian Xu; Zhou-Jun Peng; Shao-Hua Xu; Yi-Xue Xiong; Mao Lin (Journal of Earth Science, 2025)

VUV photoelectron ionization source for molecular beam mass spectrometer and its application for SF6 discharge product detection - Peng Liu; Chenxin Wu; Shan Deng; Yuanyuan Xie; Lei Hua; Haiyang Li; Shengrui Yu; Ping Chen (Analytica Chimica Acta, 2025)

Plant community‐dominating species can sustain population biomass by modifying and strengthening their own growth traits to deal with long‐term grazing - Yu-Wen Zhang; Ze-Chen Peng; Zhao-Feng Wang; Sheng-Hua Chang; Yu-Feng An; Duo-Cai Li; Fu-Jiang Hou; Ji-Zhou Ren (Agriculture, Ecosystems & Environment, 2025)

Revealing the occurrence characteristics, interaction mechanisms, and health risk of phthalates in agricultural soil of arid regions across Northwest China - Guo-dong Kang; Peng Lei; Lei-lei Lu; Ning Wang; Meng-jiao Li; Liang-liang Liu; Rui-yun Sun; Sheng-hu Zhang; Yan-hua Liu; Ping Wu (Environmental Monitoring and Assessment, 2025)

In vitro physiological and biochemical responses underlying salt tolerance of five turfgrass species - Zhen-Peng Wei; Yu-Ping Xiong; Jaime A. Teixeira da Silva; Jian-Rong Li; Jun-Yu Liu; Yuan Li; Zhan Bian; Xin-Hua Zhang; Guo-Hua Ma (Vegetos, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Fragments of ancient continental lithospheric mantle in the Mogok metamorphic Belt, Northern Myanmar: Re–Os isotope and platinum group element constraints - Qing-Hua Zhang; Bin Su; Yi Chen; Victoria Pease; Tou-Ping Peng; Zhu-Yin Chu; Yi-Bing Li; Kai-Hui Shi; Si Chen (Precambrian Research, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

The emerging threat of hybrid microplastics: Impacts on per(poly)fluoroalkyl substance bioaccumulation and phytotoxicity in floating macrophytes - Zi-wei Chen; Zu-lin Hua; Ye-bing Shi; Li Gu; Fu-zhu Ye; Jia-yun Chen; Peng Guo (Journal of Hazardous Materials, 2025)

Ionic liquid modified MOF-808 for efficient adsorption and stable capture of radioactive iodine - Xiao-Jun Dai; Yi-Ting Chen; Wen-Ge Zhang; Shu-Xuan Li; Wen-Rui Zhang; Xiang-Hua Qi; Chun-Hui Gong; Peng Wang; Man-Li He; Yi Yang (Journal of Environmental Management, 2025)

Reducing environment and enhanced productivity controlled the accumulation of organic matter in the Upper Yangtze Basin, South China during the Late Ordovician-Early Silurian - Yan-Jun Bao; Yuan-Yuan Sun; Di Zhang; Jian-Fei Yan; Yu-Peng Men; Wei Sun; Jia-Shan Lin; You-Li Wan; Jian-Wei Kang; Wen-Hua Wang; Qiangba Zhaxi (Journal of Asian Earth Sciences, 2025)

Response of Litopenaeus vannamei to dietary Isothiocyanate: Growth, biochemistry, immunity and gene expression related to hepatopancreas and intestinal health - Chen Chen; Mengling Nie; Xinghui Cai; Ying Hang; Aike Li; Lin Qiao; Peng Kang; Qianqian Wang; Yunchao Pan; Xueming Hua (Fish & Shellfish Immunology, 2025)

Bioinspired neural network-enabled metre-scale attached ultraductile cementitious nanosensors with temperature-immune - Hua Fu; Penggang Wang; Heping Zheng; Bo Pang; Zuquan Jin; Xiaoyun Song; Li Tian; Zhenxing Du; Bukhari Mohd Nadeem; Peng Zhang; Zhengkai Hu (Chemical Engineering Journal, 2025)

Investigating tree shading and thermal variations in a subtropical zone: Single Tree to Urban Squares - Xiang Zhang; Peng Ren; Ling-Ye Yao; Qi Li; Xue Zhong; Kai-Xin Liu; Tong-Ye Guo; Jia-Hao Yang; Li-Hua Zhao; Stephan Pauleit; Mohammad A. Rahman (Building and Environment, 2025)

Multi-Target Inhibitor of ZJQ- 3 F Against AChE/BACE1/GSK3β Targets Improves the Cognitive Impairment of APP/PS1/Tau Triple-Transgenic Mouse Models of Alzheimer’s Disease - Nan Wang; Xin-zhu Li; Xiao-wen Jiang; Xin-yue Ning; Li-jun Zhou; Wen-jie Liu; Qiong Wu; Xin-peng Wang; Yu Xing; Zhen-tong Qi; Zi-hua Xu; Hong-tao Song; et al. (Molecular Neurobiology, 2025)

Rheinheimera fenheensis sp. nov., Isolated from Fenhe River Basin, China - Xuan Shao; Yun-Lin Peng; Jin-Hang Guo; Zhao-Tong Chen; Hua-Ming Zhong; Di Meng; Hong-Jian Hou; Xi-Ying Zhang; Yong Zhao; Yi Li (Current Microbiology, 2025)

Balancing the benefits and risks of China’s national salt iodization policy over 30 years using disability-adjusted life years (DALYs): a systematic review and meta-analysis - Wenxiu Chen; Xinyi Liu; Bin Zhang; Chenhui Sang; Hua Li; Ying Peng; Wei An; Min Yang (Critical Reviews in Food Science and Nutrition, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Complete genome sequence of Pseudoalteromonas lipolytica M7NS11, a chitinolytic bacterium isolated from the New Britain Trench - Bin Jin; Xiao Liang; Xiaoyu Wang; Li-Hua Peng; Jin-Long Yang (Marine Genomics, 2025)

One-pot synthesis of visible-light responsive BiOCl/BiOBr/g-C3N4 ternary heterojunction with excellent photocatalytic activity - Lijun Cheng; Jianhua Shi; Bingjing Yao; Yiyun Peng; Wenhui Li; Shun Xin; Hua Gao; Shaohua Ma (Journal of Water Process Engineering, 2025)

Pipeline misconnections in separated sewer systems worsen urban river ecological status through stormwater discharge - Tian Ouyang; Jianchao Liu; Guanghua Lu; Hua Wang; Yiping Li; Feifei Zheng; Peng Gao (Journal of Environmental Management, 2025)

Effects of aging years on taste attributes of Huangjiu and their correlation with non-volatile compounds: A study based on E-tongue, UPLC-MS untargeted metabolomics, and WGCNA - Dianhui Wu; Ziqiang Chen; Mingtao Ma; Wenzhe Li; Zhengcong Peng; Zhenbao Shi; Jinglong Zhang; Hua Liu; Guangfa Xie; Jian Lu (Food Chemistry, 2025)

Deoxynivalenol removal and quality evaluation of foxtail millet under electron beam irradiation - Min Li; Shanshan He; Sifan Yang; Naiwei Peng; Huishan Shen; Xingli Liu; Yanyan Zhang; Hua Zhang (Food Control, 2025)

Corrigendum to “Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations” [Comput. Geotech. 182 (2025) 107160] - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Polycomponent metal-organic frameworks of substituent polydispersion hydroxypropyl-β-cyclodextrin as inhalable drug carrier - Xiaojian He; Huipeng Xu; Xiangyu Zhao; Feng Li; Ningning Peng; Jialong Wang; Wenqiang Hua; Feixiang Wang; Guanghong Xu; Rui Yang; Jiwen Zhang; Li Wu (Carbohydrate Polymers, 2025)

Steel frame joints with multistage performance for collaboratively resisting earthquakes - Jian-peng Wei; Han Tian; Dong-hua Wang; Li-min Tian (Soil Dynamics and Earthquake Engineering, 2025)

Antibiotic-induced multi-trophic effects and their cascades in a sub-tropical freshwater ecosystem - Kai-Sheng Yao; Pei-Liang Zhou; Li-Juan Tan; Hua-Qiao Yang; Lu-Kai Qiao; Fang-Zhou Gao; You-Sheng Liu; Feng-Jiao Peng; Guang-Guo Ying; Paul J. Van den Brink (Journal of Hazardous Materials, 2025)

NLRC3 regulates RIP2, STING, TBK1, and TRAF6 mediated type I IFN signaling and inflammatory response in large yellow croaker Larimichthys crocea - Yu Qing Xu; Ying Li; Kun Huang Han; Jia Xi Zhang; Kai Qing Li; Jing Jiang; Zhao Han Sun; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2025)

Development and evaluation of recombinant multi-epitopes vaccine against nervous necrosis virus - Chen Zhang; Wei-Nan Zhao; Xin-Xin Liu; Wen-Ye Song; Hai-Hua Peng; Min Yang; Peng-Fei Li; Jin-Qi Wei; Yong-Can Zhou; Yun Sun (Fish & Shellfish Immunology, 2025)

Characteristics of microbial carbon pump in the sediment of kelp aquaculture zone and its contribution to recalcitrant dissolved organic carbon turnover: insights into metabolic patterns and ecological functions - Jun-Yang Ma; Ji-Hua Liu; Cheng-Zhuang Chen; Yi-Ze Zhang; Zhan-Sheng Guo; Min-Peng Song; Feng Jiang; Zi-Tong Chai; Zhu Li; Su-Xian Lv; Yu-Jiao Zhen; Lu Wang; et al. (Environmental Research, 2025)

A hydrogel-based composite facilitates efficient and recyclable tetracycline biodegradation in aquatic environments - Ze-Hua Cui; Qian He; Zhi-Peng Li; Yao Deng; Xiao-Ping Liao; Chaoqun Zhang; Jian Sun; Hao Ren; Lu Han (Environmental Research, 2025)

Probabilistic vulnerability evaluation of buildings under landslide runout impacts considering the 3D dynamic interaction processes - Xiaoping Sun; Peng Zeng; Tianbin Li; Qiang Xu; Hua Zhao; Xin Wang (Engineering Geology, 2025)

Deep Hypothermic Low Flow Results in Multiple Aspects of Neurological Deficits in Mice by eEF2 Hyperphosphorylation - Yumei Liao; Dongyang Che; Peng Liu; Xinyu Wang; Yanlin Zhang; Lingling Guo; Jinlin Hu; Tianyao Li; Mei Fong Lam; Nan Ma; Shiqing Zhang; Hua Lu; et al. (Molecular Neurobiology, 2025)

Mangiferin promotes porcine oocyte maturation and delays the postovulatory aging process by up-regulating NRF2 levels - Xiuwen Yuan; Hewei Ji; Yuhao Zhang; Huilin Peng; Neng-hao Cao; Jia-jun Ren; Xue-rui Yao; Xingwei Liang; Nam-hyung Kim; Yong-nan Xu; Ying-hua Li (Theriogenology, 2025)

Incidence, risk factors, and prognosis of hospitalized mechanical eye injuries in China: data from China Ocular Trauma Study (COTS) 2021–2023 - Han Han; Yongjie Chen; Gao Si; Guowei Huang; Jiayi Song; Wenfang Zhang; Danyan Liu; Jie Zhong; Xuemin Jin; Dawei Sun; Shenwen Liu; Yanming Huang; et al. (Science Bulletin, 2025)

Mechanistic impact of organics on electro-induced transformation of iron oxides and simultaneous uranium immobilization in wastewater - Mi Li; Dan Huang; Lanlan Cao; Sheng Liu; Xiaoyan Wu; Zhaowen Cheng; Xiaowen Zhang; Yilong Hua; Ying Peng; Qi Fang; Tao Cai (Journal of Hazardous Materials, 2025)

Rapid absolute quantification of glucose and fructose isomers in honey using a boronic acid-based reactive matrix by MALDI-TOF/TOF tandem mass spectrometry - Zhang-Na Qin; Jia-Min Chen; Jia-Wei Li; Zhen-Peng Zhen; Qi-Zhao Chen; Zhi-Qiang Zhang; Gui-Hua Wang; Yu-Feng Gao (Food Chemistry, 2025)

Adverse associations of pre-pregnancy exposure to PM2.5 and its components with fetal growth alleviated by residential greenness: a prospective cohort study - Si-Wei Dai; Zhen-Hua Li; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Chun-Yong Wang; Xiao-Yu Zhao; Hai-Yang Weng; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Pollution, 2025)

An analytical solution to the radiation-convective heat transfer in a parallel-plates direct absorption solar heat collection duct - Chao-Hua Peng; Chuan-Shuai Dong; Li-Zhi Zhang (Energy and Buildings, 2025)

Fracture Characteristics of Granite Specimens after Heating-Cooling treatments: Insights from Experiments and GBM Simulations - Hao Yin; Yan-Hua Huang; Kun-Bo Zhang; Xue-Wei Liu; Jun Peng; Ming-Xu Li (Computers and Geotechnics, 2025)

Development of a novel LBL@DHBA/Cu-MOF coating on titanium implants to accelerate early osseointegration by promoting neural-vascular-bone coupling regeneration - Peng Hua; Xiaoyi Pan; Jiming Liu; Xuemei Chen; Manjuan Li; Yan Guo; Xuan Li; Pengyuan Leng; Guoyong Fan; Mengjiao Zheng; Kai Yu; Pingping Ma; et al. (Chemical Engineering Journal, 2025)

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Design, synthesis, and antifungal activity of novel pyrazole carboxamide derivatives containing benzimidazole moiety as potential SDH inhibitors - Fei Jin; Feng Peng; Xiang-Yi Kong; Wen-Rui Li; Jian-Qi Chai; Min Chen; Ai-Min Lu; Chun-Long Yang; Guo-Hua Li (Molecular Diversity, 2025)

Hydrogen peroxide regulated split-type electrochemiluminescence sensing platform for non-invasive detection of gastric cancer-associated D-amino acids - Juan Li; Ming-Chun Lai; Ya-Meng Zhong; Ya-Ling Chen; Na Wu; Wei Chen; Hua-Ping Peng (Analytica Chimica Acta, 2025)

Regulating organic loading to mitigate the impact of microplastics on nitrogen removal and microbial communities in SBR systems - Yi Yang; Lin Luo; Jian Zhu; Kai Deng; Changjun Li; Ying Zhang; Zhongxiang He; Pofei Wang; Hua Peng (Journal of Water Process Engineering, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Converting waste liquid crystal polyesters into microporous carbons for generating freshwater and electricity - Qiannan Cheng; Tao Peng; Jie Li; Lijie Liu; Qingquan Tang; Luoxin Wang; Hua Wang; Jiang Gong (Chemical Engineering Journal, 2025)

Temperature-tuned dual-selective NO2/diisopropylamine sensor based on (NH4)0.33WO3 doped γ-WO3 nanosheets-assembled hollow microspheres via simple pyrolysis of commercial ammonium metatungstate - Guo-Li Chen; Hui-Ye Jiang; Yan Jiang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2025)

A cross-sectional survey of international voyage ships entering Zhoushan Port by sea, Zhoushan, 2020-2022 - Yuzhe Hua; Yaxin Dai; Jingping Yi; Wenjie Wu; Peng Li; Kefeng Li; Wei Chen; An Tang (Frontiers in Marine Science, 2025)
Crew members aboard international voyage ships are susceptible to imported acute respiratory infections, leading to clusters of outbreaks that pose challenges to the health of crew members. The aim of the proposed study was to optimize a plan for the quarantine process and rescue measures in response to a coronavirus disease 2019 (COVID-19) outbreak at sea to provide policy guidance for the prevention and control of severe infectious diseases on international voyage ships. Here, we described the baseline characteristics of international voyage ships and crew members entering Zhoushan Port from 2020 to 2022 and analyzed the factors influencing the incidence rate of COVID-19 among crew members. There were 161 COVID-19 cases among cargo ships entering Zhoushan Port by sea, with an average incidence rate of 16.00% (95% CI: 13.73%–18.27%). The incidence rate of COVID-19 was significantly higher among crew members with replacement, long voyage, and those who stayed at multiple anchorages or stayed for a long time. The risk of COVID-19 infection for crew members staying at more than 4 anchorage was the highest, which was 2.667 (95% CI: 1.857–3.830) times that of crew members staying at less than 4 anchorage. We developed and refined the workflow for a public health assistance plan for outbreaks at sea on the basis of our experience with several COVID-19 outbreaks on international voyage ships. The workflow includes fundamental requirements, sampling and testing methods, personnel transfer procedures, medical waste disposal guidelines, and disinfection procedures for affected ships. Our public health assistance plan can be applied to other international voyage ships for which urgent public health assistance is needed during sudden infectious disease outbreaks.

Three new metabolites from the endophyte Fusarium proliferatum T2-10 - Jian-Bing Tan; Wei-Wei Peng; Mei-Fang Li; Feng-Hua Kang; Yu-Ting Zheng; Li Xu; Si-Yu Qin; Yuan-Tao Huang; Zhen-Xing Zou (Natural Product Research, 2025)

Two new compounds from Pentadesma butyracea and their biological activities - Yue Yang; Li Hua Gong; Fu Hua Peng; Tao Jiang; Jian Guo Hu; Hong Dong Liu; Bin Li; Yin Xia Yang; Jing Ying Peng; Xue Mei Gao (Phytochemistry Letters, 2025)

Late Pliocene evolution of hydroclimate, temperature and ecosystem in the Tianshui Basin, northeastern Tibetan Plateau, China: A multiproxy geochemical approach - Tingjiang Peng; Xiaomiao Li; Hui Hua; Zhenzhong Tian; Mingqiu Zhang; Meng Li; Zhenhua Ma; Benhong Guo; Jia Liu; Zhantao Feng; Zhijun Zhao; Chunhui Song (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Mineralogy, geochemistry, and S isotope investigation of seafloor massive sulfides from the Yunzang hydrothermal field, South Atlantic Ridge - Wen-Sheng Li; Pei Ni; Xue-Fa Shi; Bing Li; Shao-Wen Liu; Stefano Albanese; Fei-Peng Fan; Guan-Hua Wang; An-Qi Hong (Journal of Geochemical Exploration, 2025)

Preparation of a La(OH)CO3/NiAl-LDHs interface junction photoinitiated activator: Excellent photoinitiated activity and the photoactive pathway for destruction of phenol in wastewater - Hui-Min Zhao; Wei-Peng Jia; Rui Dang; Xiang-Rong Ma; Yang Ma; Shuang-Yu Li; Xin Han; Nai-Cai Xu; Yu-Hong Kang; Yong Gao; Hua-Rui Hao; Rui Bai; et al. (Journal of Environmental Chemical Engineering, 2025)

Efficient non-doped blue and white OLEDs with negligible roll-off efficiency using anthracene-based hybrid local and charge transfer emitters - Kang Chen; Qiao Luo; Yuqin Du; Yali Peng; Xiaoxia Li; Huixia Xu; Yanqian Miao; Hua Wang; Runfeng Chen; Junsheng Yu; Dongge Ma (Chemical Engineering Journal, 2025)

Monsoon Climate and Anthropogenic Influences Shape Primate Distributions Across the Southeastern Edge of the Qinghai‐Tibet Plateau - Chen Li; Yi‐hao Fang; Guo‐peng Ren; Yan‐peng Li; Zhi‐pang Huang; Liang‐wei Cui; Dionisios Youlatos; Paul A. Garber; Xi‐jun Ni; Hua Zhu; De‐wen Luo; Xin Liu; et al. (Global Change Biology, 2025)
The southeastern edge of the Qinghai‐Tibet Plateau (Yunnan, China) exhibits high biodiversity but stark differences in species richness between its western Longitudinal Range Gorge (LRG) and eastern Yunnan Plateau (YP). We collected distribution data for 16 primate species in Yunnan and analyzed palynological records over the past 20 ka from 21 localities to identify the biogeographic, climatic, and anthropogenic factors that have driven the present‐day distribution of primates in this region. By integrating local ecological knowledge, field surveys, species distribution models, niche utilization rates, and historical vegetation and land use changes, we found that spatial–temporal shifts in the monsoon climate have been a critical factor in shaping primate species richness on the southeastern edge of the Qinghai‐Tibet Plateau. Compared to the YP, the LRG receives more precipitation, has more limited seasonal temperature variation, and has higher minimum temperatures during the coldest month. These conditions have facilitated the development of moist evergreen broadleaf forests, which represent a more suitable habitat for the 14 primate species that inhabit this area. In contrast, the drought‐adapted forests of the YP support only one primate species. Palynological records indicate that the differentiation of the LRG and YP predates human influence. However, over the past 2000 years, anthropogenic habitat loss and hunting have significantly affected the distribution of primates. The ranges of gibbons, langurs, and snub‐nosed monkeys are now restricted to the central and northern regions of the LRG and have disappeared from lower elevations. Lorises have disappeared from their northernmost range. In contrast, the distribution of macaques has remained relatively stable. The Yangtze‐Red River‐24° N line marks the biogeographic boundary of high primate species richness and biodiversity in the LRG and southeastern Yunnan. Our research suggests that changes in monsoon climate have fundamentally shaped contemporary species richness, while recent anthropogenic pressures have caused ‘range contraction’ for many taxa.

Elemental Imbalances After Manganese Exposure and the Regulatory Potential of Curcumin - Hua Zhao; Jia-Min Zeng; Yao Li; Chun-Yan Ao; Duo Liu; Jing-Peng Zhuo; Chun Yu; Jia-Qi Ban; Jun Li (Biological Trace Element Research, 2025)

The effects of phospholipids (PL) addition in the high fat diet on growth performance, oxidative stress, lipid and protein metabolism, and muscle development in yellow catfish Pelteobagrus fulvidraco - Qing-Lin Li; Biao Wang; Hua Zheng; Li-Xiang Wu; Peng-Cheng Xu; Xiao-Ying Tan (Aquaculture, 2025)

Mink enteritis virus infection induced cell cycle arrest and autophagy for its replication - Dong Lu-jiao; Li Zhi-juan; Sun Ying-Li; Fan Hua; Li Wen-qian; Zhang Hui-ning; Peng Jun; Xie Zhi-jing (Veterinary Microbiology, 2025)

Waterproofing enhancement mechanism of the double sealing gaskets: Experimental test and theoretical analysis - Hua-Yong Li; Huai-Na Wu; Dong-Lin Feng; Lei Liu; Qing-long Cui; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Harnessing the role of rhizo-bacteria to mitigate salinity stress in rice (Orzya sativa); focus on antioxidant defense system, photosynthesis response, and rhizosphere microbial diversity - Zejian Chen; Peng Zhang; Bin Wang; Hui Li; Shuxin Li; Hua Zhang; Fasih Ullah Haider; Xiangnan Li (Rhizosphere, 2025)

Angular normalization of GOES-16 and GOES-17 land surface temperature over overlapping region using an extended time-evolving kernel-driven model - Boxiong Qin; Shuisen Chen; Biao Cao; Yunyue Yu; Peng Yu; Qiang Na; Enqing Hou; Dan Li; Kai Jia; Yingpin Yang; Tian Hu; Zunjian Bian; et al. (Remote Sensing of Environment, 2025)

Genomic, transcriptomic, and metabolomic analyses reveal convergent evolution of oxime biosynthesis in Darwin’s orchid - Kai Jiang; Birger Lindberg Møller; Shaofan Luo; Yu Yang; David R. Nelson; Elizabeth Heather Jakobsen Neilson; Joachim Møller Christensen; Kai Hua; Chao Hu; Xinhua Zeng; Mohammed Saddik Motawie; Tao Wan; et al. (Molecular Plant, 2025)

Origin of the recently-discovered Zhongpai Co-rich pyrite deposit in the Lanping-Simao Basin, southwest China: Constraints of trace elements and S isotopes of pyrite and U-Pb ages of monazite - Li-Qing Li; Hai-Peng Wang; Dai Zhang; Jia-Xi Zhou; Chang-Hua Yang; Yong-Guo Jiang; Liang Shen; Kai Luo (Journal of Asian Earth Sciences, 2025)

Energy, economic, emissions analysis of semi-flexible crystalline silicon photovoltaic system integrated with factory building roofs based on actual electricity load and cost conditions - Hua Zhang; Xinzhu Chen; Wenxin Li; Ruili Peng; Jie Ji; Xiaoxiao Su; Chenglong Luo (Energy and Buildings, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Reinforced Collaborative-Competitive Representation for Biomedical Image Recognition - Junwei Jin; Songbo Zhou; Yanting Li; Tanxin Zhu; Chao Fan; Hua Zhang; Peng Li (Interdisciplinary Sciences: Computational Life Sciences, 2025)

Identification and characterization of Alternaria spp. causing leaf blotch on Salix matsudana: A study from Rudong city, China - Yi-Lin Chen; Bing-Yao Peng; Yu Wan; De-Wei Li; Li-Hua Zhu (Crop Protection, 2025)

The influence of greening management and landscape patterns on plant diversity in urban green spaces in Danzhou, China - Mei-Hui Zhu; Qian Li; Jia-Li Yuan; Josep Padullés Cubino; Joel B. Johnson; Jian-Peng Cui; Mir Muhammad Nizamani; Zhi-Xin Zhu; Hua-Feng Wang (Urban Forestry & Urban Greening, 2025)

Fully hydro-mechanical coupled analyses of the deep excavation above a multi-aquifer-aquitard system - Ming-Guang Li; Yue-Heng Yan; Zhong-Hua Xu; Hao-Biao Chen; Chen-Xin Peng; Jin-Jian Chen (Tunnelling and Underground Space Technology, 2025)

Spatial distribution of bacteria in response to phytoplankton community and multiple environmental factors in surface waters in Sanggou Bay - Song Peng; Rong Bi; Jiwen Liu; Jiaxuan Cui; Xinkai Fu; Xiaotong Xiao; Ruihuan Li; Zengjie Jiang; Shulan Xu; Chuanli Zhang; Xiao-Hua Zhang; Meixun Zhao (Marine Environmental Research, 2025)

A plant growth-promoting bacterium supports cadmium detoxification of rice by inducing phenylpropanoid and flavonoid biosynthesis - Yingjie Wu; Haiyang Zhao; Meijuan Xiao; Huimin Liu; Hua He; Lu Peng; Qi Tao; Xiaoyan Tang; Yanyan Zhang; Rong Huang; Bing Li; Changquan Wang (Journal of Hazardous Materials, 2025)

Molecular mechanism of pyrazosulfuron-ethyl degradation by Chenggangzhangalella sp. BI-1 and study on enhanced bioremediation of contaminated soil with rhammelolipid - Hao Zhang; Zi-wei Hua; Zi-yue Ding; Hui-ying Yang; Tie-jun Wang; Yu-ying Li; B. Larry Li; Xing Huang; Peng-fei Duan; Qiu-hong Niu (Journal of Environmental Chemical Engineering, 2025)

Tracing the geographical origin of Chinese green tea based on fluorescent sensor array combined with multi-way chemometrics analyses - Xinyao Lin; Chunling Yin; Leqian Hu; Liuchuang Zhao; Mengyao Chen; Xia Hua; Zhimin Liu; Peng Li (Food Research International, 2025)

Magnetically controlled fluorescence biosensor for simultaneous detection of aflatoxin B1 and its toxin-producing gene aflD - Yaqi Li; Shuangfeng Peng; Xin Chen; Danni Sun; Xiang Zuo; Chang Liu; Qi Zhang; Shijie Li; Hua Ye; Dezhao Kong (Food Bioscience, 2025)

Regional disparities in PPCPs contamination of urban wastewater treatment plants: Unveiling influential factors and ecological effects - Xing Chen; Xiaofei Lu; Jiahua Peng; Guijin Su; Jing Meng; Qianqian Li; Yukang Hua; Ming Hu; Bin Shi (Environmental Pollution, 2025)

Fabrication of PBS/PLA/Fibroin-Agarose nerve guidance conduit with sandwich compression resistant wall structure for repairment of 10 mm-sciatic nerve defect - Wen Zhang; Meng-Fei Hao; Hao Peng; Dong-Yi Wei; Jing-Jing Yao; Tian Guo; Li-Min Yang; Hua-Jie Wang (Chemical Engineering Journal, 2025)

Distinct lignocelluloses of plant evolution are optimally selective for complete biomass saccharification and upgrading Cd2+/Pb2+ and dye adsorption via desired biosorbent assembly - Huiyi Zhang; Yongtai Wang; Hao Peng; Boyang He; Yunong Li; Hailang Wang; Zhen Hu; Hua Yu; Yanting Wang; Mengzhou Zhou; Liangcai Peng; Miao Wang (Bioresource Technology, 2025)

Research landmarks on the 60th anniversary of Epstein-Barr virus - Lan-Yi Zhong; Chu Xie; Le-Le Zhang; Yan-Lin Yang; Yuan-Tao Liu; Ge-Xin Zhao; Guo-Long Bu; Xian-Shu Tian; Zi-Ying Jiang; Bo-Yu Yuan; Peng-Lin Li; Pei-Huang Wu; et al. (Science China Life Sciences, 2025)

Association Between Exposure to Multiple Toxic Metals in Follicular Fluid and the Risk of PCOS Among Infertile Women: The Mediating Effect of Metabolic Markers - Xin Wang; Ying Zhang; Jie Peng; Hua Zhang; Tingting Jiang; Zhikang Zhang; Tao Yin; Xun Su; Tao Zhang; Lingchao Shen; Shitao He; Xiaolei Wang; et al. (Biological Trace Element Research, 2025)

Rare diphenylheptanoid-phenylheptanoid hybrids with α-glucosidase inhibitory effects from the pollen of Typha angustifolia - Chao Wang; Yu-Peng Li; Xu Gong; Li-She Gan; Hua Zhang (Natural Product Research, 2025)

Dietary lecithin attenuates adverse effects of high fat diet on growth performance, lipid metabolism, endoplasmic reticulum stress and antioxidant capacity in the intestine of largemouth bass (Micropterus salmoides) - Hua Zheng; Biao Wang; Qing-Lin Li; Tao Zhao; Peng-Cheng Xu; Yu-Feng Song; Zhi Luo (Aquaculture, 2025)

AMPK activation by dietary acadesine improves fillet texture in large yellow croaker (Larimichthys crocea) fed a linseed oil-based diet - Shengdi Chen; Zihan Sun; Ningning Liu; Chenbin Yang; Na Li; Lu Li; Chaoqing Wei; Binlun Yan; Huan Gao; Peng Tan; Hua Mu (Aquaculture, 2025)

Experimental and numerical study on the waterproof performances of the sealing gaskets under coupled compression-shear stress - Huai-Na Wu; Hua-Yong Li; Lei Liu; Xin-Xin Yang; Ren-Peng Chen (Tunnelling and Underground Space Technology, 2025)

Sex-specific associations between maternal exposure to metal mixtures and fetal growth trajectories: A prospective birth cohort study - Zhen-Hua Li; Cheng-Yang Hu; Si-Wei Dai; Hui-Ya Ma; Si-Yu Zhang; Chen Sun; Jia-Hui Li; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Xiu-Jun Zhang (Science of The Total Environment, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Visible light-powered photodynamic antibacterial chlorophyllin-derived metallochlorins - Yuling Xue; Kuoran Xing; Max Jing Rui Tham; Bang Lin Li; Narattam Sikdar; Lai Peng Leong; Ching Hua Lee; Justin Jang Hann Chu; Wee Han Ang; David Tai Leong (Chemical Engineering Journal, 2025)

A combined genetic modification and chemical engineering strategy for designing high-performance cellulose nanofibrils separators - Ling-Hua Xu; Peng-Fei Wang; Ying Xu; Jing Liu; Xiao-Peng Peng; Jia Liu; Xiao-Jun Shen; Jia-Long Wen; Quanzi Li; Tong-Qi Yuan (Chemical Engineering Journal, 2025)

Characterization of the complete chloroplast genome of purple flowering stalk (Brassica campestris var. purpuraria) and comparisons with related species - Yihui Gong; Limeng Duan; Guihua Zhou; Yuting Yuan; Jiali Zhang; Haiyan He; Peng Li; Hua Huang (Genetic Resources and Crop Evolution, 2025)

Dietary Probiotic Rhodopseudomonas palustris Formulation Improves Growth Performance, Muscle Composition, Digestive Enzyme Activity, Non-Specific Immunity and Disease Resistance of Juvenile Ivory Shell (Babylonia areolata) - Xiao Wang; Yao-Peng Lu; Ze-Long Zhang; Pei-Hua Zheng; Jun-Tao Li; Xiu-Xia Zhang; Jia-Jun Li; Heng-Mei Wu; Jian-An Xian (Fishes, 2024)
Rhodopseudomonas palustris (RP) are known anaerobic bacteria with probiotic properties containing several bioactive compounds and enzymes that benefit aquatic animals. However, studies on the use of RP on aquatic animal species are limited. This study investigated the effects of dietary supplementation with RP formulation on the growth, non-specific immunity, and disease resistance of juvenile ivory shells (Babylonia areolata). The experiment was conducted for 8 weeks, with B. areolata fed a control diet (RP0) and four diets containing four different RP formulations, with doses of 1 (RP1), 5 (RP2), 10 (RP3), and 20 (RP4) g/kg, respectively. Higher levels of R. palustris in the formulation led to increased final weight, weight gain, and specific growth rate in B. areolata. The crude protein content was significantly higher in the RP4 group compared to the RP0 group. However, there was no significant difference in the crude lipid content. Higher levels of R. palustris in the RP4 formulation group increased the trypsin and lipase activities. Dietary supplementation with RP significantly increased the total antioxidant capacity, superoxide dismutase, and catalase activities and decreased the malondialdehyde content in B. areolata. Acid phosphatase and alkaline phosphatase activities were significantly increased in the RP4 group compared to the RP0 group. Dietary RP significantly increased the expression levels of antioxidant-related (superoxide dismutase, Cu/Zn-superoxide dismutase, glutathione S-transferase A-like, ferritin) and immune-related (acid phosphatase, cytochrome c) genes. Higher levels of R. palustris in the formulations RP3 and RP4 increased the survival rate of B. areolata challenged with Vibrio parahaemolyticus. These findings indicate that R. palustris preparation could improve growth performance, muscle composition, and digestive capacity and may act as an immune booster for preventing disease in B. areolata.

Dietary Iodine Can Effectively Alleviate the Adverse Effects of Fermented Rapeseed Meal on the Growth, Liver Health, and Antioxidant Capacity of Tilapia (GIFT, Oreochromis niloticus) - Di Peng; Ya-Xue Li; Li-Xue Dong; Ke Cheng; Hua Wen; Juan Tian; Jian-Min Zhang; Yang-Yang Liu; Wei-Hua Gao; Yong Min; Ming-Dian Liu; Ming Jiang (Fishes, 2024)
An 8-week feeding trial was conducted to evaluate the effects of dietary fermented rapeseed meal (FRM), potassium iodide, and their interactions on growth performance, approximate composition, and antioxidant capacity in tilapia, Oreochromis niloticus (initial body weight: 3.50 ± 0.15 g). Six isonitrogenous and isolipidic diets from a 2 × 3 factorial design were formulated with two levels of FRM (25.8 and 51.6%) and three levels of potassium iodide (0, 6, and 12 mg/kg), respectively. The results indicated that dietary levels of FRM and iodine had no significant influence on the SR of tilapia but exerted significant effects on weight gain (WG), specific growth rate (SGR), feed intake (FI), hepatosomatic index, and viscerosomatic index. The WG, SGR, and FI of tilapia in the 51.6% FRM groups were significantly lower than those in other groups (p

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Varied chromosome distribution behaviours during meiosis in triploid Chinese chives contribute to the formation of viable pollen - Peng-Qiang Yao; Li-Hua Xie; Mei-Yu Li; Si-Qian Jiao; Shuai-Zheng Qi; Zhe Wang; Shi-Ping Cheng (Chromosome Research, 2024)

Anti-photoaging activity of triterpenoids isolated from Centella asiatica - Yi-yun Dang; Tao Liu; Yu-die Liu; Jia-yi Li; Yi Jing; Miao-jie Yang; Han Zhang; Miao-miao Jiang; Hong-hua Wu; Wen-zhi Yang; Nan Li; Peng Zhang (Phytochemistry, 2024)

Unraveling anti-aging mystery of green tea in C. elegans: Chemical truth and multiple mechanisms - Jia-ping Ke; Jia-Yi Li; Zi Yang; Hao-Yue Wu; Jing-Ya Yu; Yi Yang; Chen-Hui Chen; Peng Zhou; Fang Hua; Wei Wang; Fenglin Hu; Gang-Xiu Chu; et al. (Food Chemistry, 2024)

Characterization of newly isolated Bacillus cereus D3 Co-producing α-amylase and protease and its application in food raw materials - Shuang Wang; Hua Bai; Zongmin Wang; Lin Peng; Ling Li; Hongbo Yan; Lanlan Zhu; Yanbo Wang; Jinyan Shao; Jizhou Liu (Food Bioscience, 2024)

A robust COF membrane on polyethylene support via ethanol-assisted self-assembly of COF nanosheets for efficient desalination - Xianjuan Zhang; Yu Zheng; Runnan Zhang; Hua Jin; Peng Lu; Hui Wang; Zhongyi Jiang; Yanshuo Li (Desalination, 2024)

Ultra-capacity and low-cost P3-type K0.5Mn0.96Fe0.04O2 cathode materials for K-ion batteries - Jun Cong; Shao-hua Luo; Yi-cheng Lin; Peng-yu Li; Li-xiong Qian; Sheng-xue Yan; Xin Liu; Xue-fei Lei (Chemical Engineering Journal, 2024)

Notes on two new species of Russula subsect. Cyanoxanthinae (Russulaceae, Russulales) from southern China - Yan-Liu Chen; Jun-Feng Liang; Sheng-Kun Wang; Bin Chen; Jin-Hua Zhang; Meng-Ya An; Xing Li; Xue-Lian Gao; Xia Chen; Jin-Peng Liao (Mycological Progress, 2024)

The role of Gαq in regulating NLRP3 inflammasome activation - Ruixue Kong; Lijun Peng; Honggang Bao; Lulu Sun; Yan Feng; Hua Li; Dashan Wang (Inflammation Research, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Benzo(a)pyrene exposure during pregnancy leads to germ cell apoptosis in male mice offspring via affecting histone modifications and oxidative stress levels - Lin Zhang; Wen-Qi Chen; Xiao-Ying Han; Hong-Li Wang; Peng-Zhi Gao; Dong-Mei Wang; Zheng Cao; Chang-Hua Sun; Dong Cheng; Jing Bai; Qi-Long He; Shu-Zhen Liu (Science of The Total Environment, 2024)

Enantioselective effects of chiral profenofos on the conformation for human serum albumin - Wenze Li; Long Sun; Xiaofan Yang; Changsheng Peng; Rimao Hua; Meiqing Zhu (Pesticide Biochemistry and Physiology, 2024)

Identification and bioactivity evaluation of twelve previously undescribed depsidone derivatives from Garcinia oligantha - Xiao-Hui Peng; Sha Chen; Xiao-Fan Liu; Jin-Yuan Yang; Fan-Zhu Meng; Hao Cao; Da-Hong Li; Hui-Ming Hua (Phytochemistry, 2024)

Research and application of joint-constrained inversion of transient electromagnetic multivariate parameter - Jian-lei Guo; Yan-wei Hou; Xiong-wei Li; Zhi-peng Qi; Ke-rui Fan; Wen-han Li; Wei-hua Yao; Xiu Li (Journal of Applied Geophysics, 2024)

Planting halophytes increases the rhizosphere ecosystem multifunctionality via reducing soil salinity - Jin-Peng Hu; Yuan-Yuan He; Jian-Hong Li; Zhao-Long Lü; Yue-Wei Zhang; Yuan-Hong Li; Jia-Lü Li; Ming-Xu Zhang; Yan-Hua Cao; Jin-Lin Zhang (Environmental Research, 2024)

Multi-touch microcapsules/silicone-polyacrylate hybrid hydrogels with precise self-healing ability and their self-powered sensing applications in emergency rescue - Bingqian Zhao; Xiaolong He; Wenjian Li; Hang Zhang; Han Liu; Hua Qiu; Peng Gu; Kunlin Chen (Chemical Engineering Journal, 2024)

Oxygen-coordinated cobalt single atom steered by doped-O and CoO for efficient hydrogen evolution at industrial current densities - Junfeng Huang; Yantao Wang; Jian Li; Ruyu Xue; Lanyue Zhang; Hua Li; Yu Long; Peng Zhang; Yong Peng; Cailing Xu (Chemical Engineering Journal, 2024)

Programmed DNA tile response system enabled accurate detection of ATP for clinical diagnosis - Dongxia Li; Yanan Peng; Liangqing Lu; Delun Chen; Bingrong Wang; Qiumei Pu; Qionglin Zhou; Xinxin Xiao; Mingpeng Fu; Xiaohong Wang; Jinchun Tu; Hua Pei; et al. (Chemical Engineering Journal, 2024)

Incorporating Sb (III) and Bi (III) ions into Cs2AgNaInCl6 perovskite toward efficient white-light emission with high color rendering index - Bing Xu; Xiaoqing Peng; Hua Zhong; Linfeng Wang; Xiao Jin; Jinke Bai; Qinghua Li (Chemical Engineering Journal, 2024)

Strap-on Buoyant Device to Enhance Gastrointestinal Tract Retention of Felodipine Osmotic Pump Tablets - Qijia Ni; Zeru Li; Libumo Baqing; Tianfu Li; Huipeng Xu; Falan Li; Ningning Peng; Caifen Wang; Jianhua Lu; Zhigang Wang; Kai Wang; Chao Jiang; et al. (AAPS PharmSciTech, 2024)

Testosterone-promoting effects of Trichosanthes kirilowii-derived peptides on TM3 cells - Zhilin He; Dong Peng; Jieyu Zeng; Wanying Liang; Xinqi Li; Junyi Chen; Pan Li; Bing Du; Hua Li (Food Bioscience, 2024)

Dual-active sites and reversible-structural covalent organic framework for highly stable alkali metal-ion batteries - Kang Hua; Longhai Zhang; Quanwei Ma; Hongbao Li; Rui Wang; Peng Xiong; Shilin Zhang; Tengfei Zhou; Yangyang Liu; Chaofeng Zhang (Chemical Engineering Journal, 2024)

LPAR6 Participates in Neuropathic Pain by Mediating Astrocyte Cells via ROCK2/NF-κB Signal Pathway - Xiaoyi Fan; Ruitong Chu; Xin Jiang; Peng Ma; Yan Chu; Tong Hua; Mei Yang; Ruifeng Ding; Jian Li; Zhenghua Xiang; Hongbin Yuan (Molecular Neurobiology, 2024)

Spatiotemporal variation in rice evapotranspiration under the influence of rice expansion: a case study in the Sanjiang Plain, Northeast China - Yuqi Li; Xuhua Hu; Yufeng Luo; Yang Xu; Peng Huang; Dan Yuan; Changhong Song; Yuanlai Cui; Hua Xie (Paddy and Water Environment, 2024)

Characteristics analysis of leakage diseases of Beijing underground subway stations based on the field investigation and data statistics - Hua Peng; Yujie Li; Xiaokai Niu; Haidong Tang; Xue Meng; Zichen Li; Kuangdi Wan; Wei Li; Wei Song (Transportation Geotechnics, 2024)

Comprehensive assessment of the water environment carrying capacity based on machine learning - Hua Zhang; Huaming Li; Xiangqin Xu; Xubo Lv; Jiayu Peng; Qiaoran Weng; Wenhui Wang; Kun Lei (Journal of Cleaner Production, 2024)

Biotemplate synthesis of graphitic carbon-doped ZnO tube bundles rich in oxygen vacancies for dual-sensing of NO2/H2S at different temperatures - Zhao-Qi Cui; Rui Gao; Guo-Li Chen; Shi-Kai Shen; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Actn2 defects accelerates H9c2 hypertrophy via ERK phosphorylation under chronic stress - Kang Wang; Ye Wang; Hua Wan; Jie Wang; Li Hu; Shuainan Huang; Mingchen Sheng; Jiayi Wu; Xing Han; Youjia Yu; Peng Chen; Feng Chen (Genes & Genomics, 2024)

An effective object detector via diffused graphic large selective kernel with one-to-few labelling strategy for small-scaled crop diseases detection - Jianlei Kong; Chenghao Hua; Xuebo Jin; Nan Guo; Li Peng (Crop Protection, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

Changes in PI3K/AKT and NRF2/HO-1 signaling expression and intestinal microbiota in bleomycin-induced pulmonary fibrosis - Chenchen Li; Yuxia Cao; Yousheng Peng; Ting Ma; Fanlin Wu; Yongli Hua; Xiuqin Wang; Tong Bai; Yanming Wei; Peng Ji (Food and Chemical Toxicology, 2024)

Mantle-rooted fluid pathways and world-class gold mineralization in the giant Jiaodong gold province: Insights from integrated deep seismic reflection and tectonics - Li-Qiang Yang; Jun Deng; Liang Zhang; Ai-Hua Zhao; M. Santosh; Xue-Feng Yu; Wei Yang; Da-Peng Li; Wei Shan; Dong Xie; Xiang-Dong Liu; Xue Gao; et al. (Earth-Science Reviews, 2024)

Soil improvement using biostimulated MICP: Mechanical and biochemical experiments, reactive transport modelling, and parametric analysis - Yi-jie Wang; Wen-bo Chen; Peng-lin Li; Zhen-yu Yin; Jian-hua Yin; Ning-jun Jiang (Computers and Geotechnics, 2024)

Ce-anchored NiFeOOH derived from in-situ self-optimization for efficient and highly durable water oxidation - Jinzhi Jia; Junfeng Huang; Kailu Guo; Yongyu Cha; Denan Wang; Mudong Tu; Huijiao Wang; Jian Li; Hua Li; Yong Peng; Jier Huang; Cailing Xu (Chemical Engineering Journal, 2024)

Structuring restricted amorphous molecular chains in the reinforced cellulose film by uniaxial stretching - Jing Wang; Shi-Peng Chen; De-Long Li; Lin Zhou; Jia-Xin Ren; Li-Chuan Jia; Gan-Ji Zhong; Hua-Dong Huang; Zhong-Ming Li (Carbohydrate Polymers, 2024)

Over-expression of SgRVE1 from fine-stem stylo (Stylosanthes guianensis var. intermedia) up-regulates CBF gene expression and enhances cold tolerance in Arabidopsis - Cong-Cong Wang; Chen Liang; Han-Ying Li; Huai-An Huang; Liang-Liang He; Cui-Ling Liu; Zhi-Hao Wu; Chun-Sheng Gui; Ci Ren; Yi-Hua Wang; Hao-Yu Yang; Dan-Wen Zhong; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Replacing soybean meal with fermented rapeseed meal in diets: potential effects on growth performance, antioxidant capacity, and liver and intestinal health of juvenile tilapia (Oreochromis niloticus) - Yaxue Li; Xing Lu; Lixue Dong; Di Peng; Jianmin Zhang; Zongbin Cui; Hua Wen; Juan Tian; Ming Jiang (Fish Physiology and Biochemistry, 2024)

Multiple Matching Attenuation Based on Curvelet Domain Extended Filtering - Qingfeng Hua; Zhang Chen; Huili He; Jun Tan; Haifeng Chen; Guanbao Li; Peng Song; Bo Zhao; Xiuping Jiang (Journal of Ocean University of China, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Correction to: Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao‑Bo Li; Yan‑Xun Han; Zi‑Yue Fu; Yu‑Chen Zhang; Min Fan; Shu‑Jia Sang; Xi‑Xi Chen; Bing‑Yu Liang; Yu‑Chen Liu; Peng‑Cheng Lu; Hua‑Wei Li; Hai‑Feng Pan; et al. (Environmental Science and Pollution Research, 2024)

Dietary cholesterol intervention could alleviate the intestinal injury of Oreochromis niloticus induced by plant-based diet via the intestinal barriers - Jiayuan Jiang; Xing Lu; Li-Xue Dong; Di Peng; Jian-Min Zhang; Juan Tian; Hua Wen; Ming Jiang (Fish & Shellfish Immunology, 2024)

Versatile MOF-based nanofibrous heterostructures for engineering the CO2 photoreduction activity and selectivity: From CO to C2H5OH - Xu-Chao Xia; Feng Cheng; Peng Sun; Amare Aregahegn Dubale; Hao Han; En-Tian Cui; Jun Song; Xiu-Li Yang; Ming-Hua Xie (Chemical Engineering Journal, 2024)

Mechanisms and clinical landscape of N6-methyladenosine (m6A) RNA modification in gastrointestinal tract cancers - Dan-Hua Zhu; Kun-Kai Su; Xiao-Xi Ou-Yang; Yan-Hong Zhang; Xiao-Peng Yu; Zu-Hong Li; Seyedeh-Sara Ahmadi-Nishaboori; Lan-Juan Li (Molecular and Cellular Biochemistry, 2024)
Epigenetics encompasses reversible and heritable chemical modifications of non-nuclear DNA sequences, including DNA and RNA methylation, histone modifications, non-coding RNA modifications, and chromatin rearrangements. In addition to well-studied DNA and histone methylation, RNA methylation has emerged as a hot topic in biological sciences over the past decade. N6-methyladenosine (m6A) is the most common and abundant modification in eukaryotic mRNA, affecting all RNA stages, including transcription, translation, and degradation. Advances in high-throughput sequencing technologies made it feasible to identify the chemical basis and biological functions of m6A RNA. Dysregulation of m6A levels and associated modifying proteins can both inhibit and promote cancer, highlighting the importance of the tumor microenvironment in diverse biological processes. Gastrointestinal tract cancers, including gastric, colorectal, and pancreatic cancers, are among the most common and deadly malignancies in humans. Growing evidence suggests a close association between m6A levels and the progression of gastrointestinal tumors. Global m6A modification levels are substantially modified in gastrointestinal tumor tissues and cell lines compared to healthy tissues and cells, possibly influencing various biological behaviors such as tumor cell proliferation, invasion, metastasis, and drug resistance. Exploring the diagnostic and therapeutic potential of m6A-related proteins is critical from a clinical standpoint. Developing more specific and effective m6A modulators offers new options for treating these tumors and deeper insights into gastrointestinal tract cancers.

Application of modified discontinuous deformation analysis to dynamic modelling of the Baige landslide in the Jinsha River - Chenxi Xie; Jianhui Deng; Xinyan Peng; Zhongkang Yang; Siyuan Zhao; Hua Li (Journal of Mountain Science, 2024)

Colonization ability and uniformity of resources and environmental factors determine biological homogenization of soil protists in human land‐use systems - Zhi‐Peng Li; Hua‐Yuan Shangguan; Haifeng Yao; Xiao‐Ru Yang; Yuri Mazei; Biao Zhu; Stefan Scheu; Xin Sun (Global Change Biology, 2024)
Humans have substantially transformed the global land surface, resulting in the decline in variation in biotic communities across scales, a phenomenon known as “biological homogenization.” However, different biota are affected by biological homogenization to varying degrees, but this variation and the underlying mechanisms remain little studied, particularly in soil systems. To address this topic, we used metabarcoding to investigate the biogeography of soil protists and their prey/hosts (prokaryotes, fungi, and meso‐ and macrofauna) in three human land‐use ecosystem types (farmlands, residential areas, and parks) and natural forest ecosystems across subtropical and temperate regions in China. Our results showed that the degree of community homogenization largely differed between taxa and functional groups of soil protists, and was strongly and positively linked to their colonization ability of human land‐use systems. Removal analysis showed that the introduction of widespread, generalist taxa (OTUs, operational taxonomic units) rather than the loss of narrow‐ranged, specialist OTUs was the major cause of biological homogenization. This increase in generalist OTUs seemingly alleviated the negative impact of land use on specialist taxa, but carried the risk of losing functional diversity. Finally, homogenization of prey/host biota and environmental conditions were also important drivers of biological homogenization in human land‐use systems, with their importance being more pronounced in phagotrophic than parasitic and phototrophic protists. Overall, our study showed that the variation in biological homogenization strongly depends on the colonization ability of taxa in human land‐use systems, but is also affected by the homogenization of resources and environmental conditions. Importantly, biological homogenization is not the major cause of the decline in the diversity of soil protists, and conservation and study efforts should target at taxa highly sensitive to local extinction, such as parasites.

Preparation of bacterial fertilizer from biogas residue after anaerobic co-digestion of kitchen waste and residual sludge - Chuan Li; Chang Hua; Lingling Chen; Zimei Miao; Rui Xu; Sili Peng; Zhiwei Ge; Lingfeng Mao (Environmental Science and Pollution Research, 2024)

Association of sudden sensorineural hearing loss with meteorological factors: a time series study in Hefei, China, and a literature review - Xiao-Bo Li; Yan-Xun Han; Zi-Yue Fu; Yu-Chen Zhang; Min Fan; Shu-Jia Sang; Xi-Xi Chen; Bing-Yu Liang; Yu-Chen Liu; Peng-Cheng Lu; Hua-Wei Li; Hai-Feng Pan; et al. (Environmental Science and Pollution Research, 2024)
Air pollution can cause disease and has become a major global environmental problem. It is currently believed that air pollution may be related to the progression of SSNHL. As a rapidly developing city in recent years, Hefei has serious air pollution. In order to explore the correlation between meteorological variables and SSNHL admissions, we conducted this study. This study investigated the short-term associations between SSNHL patients admitted to the hospital and Hefei climatic variables. The daily data on SSNHL-related hospital admissions and meteorological variables containing mean temperature (T-mean; °C), diurnal temperature range (DTR; °C), atmospheric pressure (AP; Hp), and relative humidity (RH; %), from 2014 to 2021 (2558 days), were collected. A time-series analysis integrating distributed lag non-linear models and generalized linear models was used. PubMed, Embase, Cochrane Library, and Web of Science databases were searched. Literature published up to August 2023 was reviewed to explore the potential impact mechanisms of meteorological factors on SSNHL. The mechanisms were determined in detail, focusing on wind speed, air pressure, temperature, humidity, and air pollutants. Using a median of 50.00% as a baseline, the effect of exceedingly low T-mean in the single-day hysteresis effect model began at a lag of 8 days (RR = 1.032, 95% CI: 1.001 ~ 1.064). High DTR affected the admission rate for SSNHL on lag 0 day. The significance of the effect was the greatest on that day (RR = 1.054, 95% CI: 1.007 ~ 1.104) and then gradually decreased. High and exceedingly high RH affected the admission rate SSNHL on lag 0 day, and these effects lasted for 8 and 7 days, respectively. There were significant associations between all grades of AP and SSNHL. This is the first study to assess the effect of meteorological variables on SSNHL-related admissions in China using a time-series approach. Long-term exposures to high DTR, RH values, low T-mean values, and all AP grades enhance the incidence of SSNHL in residents. Limiting exposure to extremes of ambient temperature and humidity may reduce the number of SSNHL-related hospital visits in the region. It is advisable to maintain a suitable living environment temperature and avoid extreme temperature fluctuations and high humidity. During periods of high air pollution, it is recommended to stay indoors and refrain from outdoor exercise.

Rice rhizospheric effects and mechanism on soil cadmium bioavailability during silicon application - Yi Yang; Hua Peng; Kai Deng; Yu Shi; Wei Wei; Saihua Liu; Changjun Li; Jian Zhu; Yanjiao Dai; Min Song; Xionghui Ji (Science of The Total Environment, 2024)

Comprehensive effects of salinity, dissolved organic carbon and copper on mortality, osmotic regulation and bioaccumulation of copper in Oryzias melastigma - Liang Cui; Xiaoguang Li; Yan Luo; Xiangyun Gao; Li Chen; Xubo Lv; Jiayu Peng; Hua Zhang; Kun Lei (Science of The Total Environment, 2024)

Evolutionary genomics of climatic adaptation and resilience to climate change in alfalfa - Fan Zhang; Ruicai Long; Zhiyao Ma; Hua Xiao; Xiaodong Xu; Zhongjie Liu; Chunxue Wei; Yiwen Wang; Yanling Peng; Xuanwen Yang; Xiaoya Shi; Shuo Cao; et al. (Molecular Plant, 2024)

Enhanced adsorption of uranium onto humicacid modified goethite from aqueous solution: An soil environmental perspective - Yi Yang; Xiaowen Zhang; Ying Peng; Xiaoyan Wu; Tao Cai; Yilong Hua; Mi Li; Dongshan Tang (Journal of Environmental Chemical Engineering, 2024)

Knockdown of the cap ‘n’ collar isoform C gene increases the susceptibility of Agrotis ipsilon to chlorantraniliprole and phoxim - Qing-Hua Xiao; Wu-Ye Li; Jin Zhang; Jia-Min Yu; Dong-Yang Liu; Jiang-Nan Peng; Mao-Ye Li; Su Liu (Journal of Asia-Pacific Entomology, 2024)

Electroporation of Chlorella vulgaris with laboratory devices capable of generating arbitrary waveform pulses - Liuxia Li; Zihuang Peng; Nan Liu; Yi Liu; Hua Li; Qin Zhang; Fuchang Lin (Innovative Food Science & Emerging Technologies, 2024)

Axisymmetric finite strain consolidation model for soft soil consolidation with vertical drains under combined loading considering creep and non-Darcy flow - Peng-Lin Li; Zhen-Yu Yin; Ding-Bao Song; Jian-Hua Yin; Yu Pan (Geotextiles and Geomembranes, 2024)

Combination of virtual screening, machine learning, molecular dynamics simulations and sensory evaluation to discover novel umami peptides from fermented Atlantic cod - Hao Zou; Hao Wang; Jinlong Zhao; Hua Feng; Shanyu Peng; Qingwen Liu; Zhihui Qin; Ziye Zhang; Hong Lin; Zhenxing Li (Food Bioscience, 2024)

Karyotype analysis of Chinese chive germplasms with different ploidy levels and their evolutionary relationships - Peng-Qiang Yao; Jian-Hua Chen; Pei-Fang Ma; Li-Hua Xie; Jiang Shi; Shi-Ping Cheng (Genetic Resources and Crop Evolution, 2024)

HOXB9 promotes laryngeal squamous cell carcinoma progression by upregulating MMP12 - Chuanhui Sun; Hua Deng; Qiuying Li; Peng Wang; Yujiang Chen; Yanan Sun; Changsong Han (Functional & Integrative Genomics, 2024)

A newly isolated strain of Bacillus subtilis W2Z exhibited probiotic effects on juvenile red claw crayfish, Cherax quadricarinatus - Ze-Long Zhang; Jia-Jun Li; Si-Wen Xing; Yao-Peng Lu; Pei-Hua Zheng; Jun-Tao Li; Chen-Guang Hao; Jia-Rui Xu; Jian-An Xian; Li-Min Zhang; Xiu-Xia Zhang (Aquaculture, 2024)

Anthropogenic factors explain urban plant diversity across three tropical cities in China - Lin-Yuan Guo; Mir Muhammad Nizamani; AJ Harris; Josep Padullés Cubino; Joel B. Johnson; Jian-Peng Cui; Hai-Li Zhang; Jing-Jiang Zhou; Zhi-Xin Zhu; Hua-Feng Wang (Urban Forestry & Urban Greening, 2024)

BDNF mimetics recover palmitic acid-induced injury in cardiomyocytes by ameliorating Akt-dependent mitochondrial impairments - Man-Ru Zhang; Bang-Yun Zuo; Yu-Chen Song; Dan-Dan Guo; Qing-Liu Li; Jin-Xiu Lyu; Hua Zhu; Jing Zhao; Peng-Zhou Hang (Toxicology and Applied Pharmacology, 2024)

BambooBase: A comprehensive database of bamboo omics and systematics - Yun-Long Liu; Shu-Yang Gao; Guihua Jin; Meng-Yuan Zhou; Qijuan Gao; Cen Guo; Yi-Zhou Yang; Liang-Zhong Niu; Enhua Xia; Zhen-Hua Guo; Peng-Fei Ma; De-Zhu Li (Molecular Plant, 2024)

Integration of transcriptome, gut microbiota, and physiology reveals toxic responses of the red claw crayfish (Cherax quadricarinatus) to imidacloprid - Yao-Peng Lu; Jia-Han Liu; Xiu-Xia Zhang; Chi Xu; Pei-Hua Zheng; Jun-Tao Li; Jia-Jun Li; Dong-Mei Wang; Jian-An Xian; Ze-Long Zhang (Journal of Hazardous Materials, 2024)

Rational biodiesel production from oxidation stability perspective: Evaluation of lipid-soluble carbonyl compound formation in the seed oil and biodiesel with long-term storage - Xiao-Hui Peng; Hua-Ming Xiao; Shuai Zhao; Dilshad Hussain; Jian-Li Chen; Dan Luo; Dan Wang; Xin Lv; Xian Wang; Hong Chen; Fang Wei (Fuel, 2024)

Maize cultivar mixtures increase aboveground biomass and grain quality via trait dissimilarity and plasticity - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (European Journal of Agronomy, 2024)

A highly-efficient locally encoded boundary scheme for lattice Boltzmann method on GPU - Zehua Zhang; Cheng Peng; Chengxiang Li; Hua Zhang; Tao Xian; Lian-Ping Wang (Computer Physics Communications, 2024)

Waste cigarette butts-templated synthesis of in-situ graphitic carbon-doped ZnO fibers boosting dual-selectivity NO2/butanone at different temperatures - Zhao-Qi Cui; Ze Wei; Cong Chen; Yuan-Yuan Sun; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Integrated analysis of transcriptome and small RNAome reveals regulatory network of rapid and long-term response to heat stress in Rhododendron moulmainense - Si-Jia Liu; Chang Cai; Hong-Yue Cai; Yu-Qing Bai; Ding-Yue Wang; Hua Zhang; Jin-Gen Peng; Li-Juan Xie (Planta, 2024)
Main conclusion The post-transcriptional gene regulatory pathway and small RNA pathway play important roles in regulating the rapid and long-term response of Rhododendron moulmainense to high-temperature stress. Abstract The Rhododendron plays an important role in maintaining ecological balance. However, it is difficult to domesticate for use in urban ecosystems due to their strict optimum growth temperature condition, and its evolution and adaptation are little known. Here, we combined transcriptome and small RNAome to reveal the rapid response and long-term adaptability regulation strategies in Rhododendron moulmainense under high-temperature stress. The post-transcriptional gene regulatory pathway plays important roles in stress response, in which the protein folding pathway is rapidly induced at 4 h after heat stress, and alternative splicing plays an important role in regulating gene expression at 7 days after heat stress. The chloroplasts oxidative damage is the main factor inhibiting photosynthesis efficiency. Through WGCNA analysis, we identified gene association patterns and potential key regulatory genes responsible for maintaining the ROS steady-state under heat stress. Finally, we found that the sRNA synthesis pathway is induced under heat stress. Combined with small RNAome, we found that more miRNAs are significantly changed under long-term heat stress. Furthermore, MYBs might play a central role in target gene interaction network of differentially expressed miRNAs in R. moulmainense under heat stress. MYBs are closely related to ABA, consistently, ABA synthesis and signaling pathways are significantly inhibited, and the change in stomatal aperture is not obvious under heat stress. Taken together, we gained valuable insights into the transplantation and long-term conservation domestication of Rhododendron , and provide genetic resources for genetic modification and molecular breeding to improve heat resistance in Rhododendron .

The conversion of mycorrhizal types closely associated with the changes in microbial keystone taxa and potential function in subtropical forests - Wenhao Jin; Jiaying Tu; Weixing Sheng; Jiajia Xing; Liyuan Peng; Xiaomin Ma; Junhui Chen; Yongfu Li; Hua Qin (Plant and Soil, 2024)

Pseudocercones A-C, three new polyketide derivatives from the endophytic fungus Pseudocercospora sp. TSS-1 - Wei-Wei Peng; Min Kuang; Yuan-Tao Huang; Mei-Fang Li; Yu-Ting Zheng; Li Xu; Jian-Bing Tan; Feng-Hua Kang; Hai-Bo Tan; Zhen-Xing Zou (Natural Product Research, 2024)

A novel method for identifying aerobic granular sludge state using sorting, densification and clarification dynamics during the settling process - Zhi-Hua Li; Ruo-Lan Wang; Meng Lu; Xin Wang; Yong-Peng Huang; Jia-Wei Yang; Tian-Yu Zhang (Water Research, 2024)

Effects of antimicrobial peptides from dietary Hermetia illucens larvae on the growth, immunity, gene expression, intestinal microbiota and resistance to Aeromonas hydrophila of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yong-Qi Meng; Jia-Jun Li; Xiu-Xia Zhang; Jun-Tao Li; Jia-Rui Xu; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

DNA Methylation Analysis Reveals Potential Mechanism in Takifugu rubripes Against Cryptocaryon irritans Infection - Yu-qing Xia; Yi Yang; Yan-yun Liu; Jian-xin Cheng; Ying Liu; Cheng-hua Li; Peng-fei Liu (Marine Biotechnology, 2024)

A triggered DNA nanomachine with enzyme-free for the rapid detection of telomerase activity in a one-step method - Huajie Pang; Yanan Peng; Rui Zhang; Zhijun Gao; Xiangde Lai; Dongxia Li; Xuan Zhao; Yuanyuan Wang; Hua Pei; Bin Qiao; Yuxiang Ji; Qiang Wu (Analytica Chimica Acta, 2024)

Effects of Dietary Fish Meal Replaced by Cottonseed Protein Concentrate on Growth Performance, Antioxidant Capacity, and Liver and Intestinal Health of Juvenile Hybrid Culter - Guangming Xu; Huijie Wei; Di Peng; Lang Zhang; Xing Lu; Qing Li; Lixue Dong; Juan Tian; Hua Wen; Guiying Wang; Ming Jiang (Fishes, 2024)
The objective of this study was to assess the impact of concentrated cottonseed protein (CPC) as a substitute for fishmeal (FM) in juvenile hybrid culter (Erythroculter ilishaeformis ♀ × Ancherythroculter nigrocauda ♂). A total of 360 fish with an initial body weight of 10.0 ± 0.5 g were randomly allocated into 12 indoor culture tanks, with each tank containing 30 fish. Four diets were formulated in which fish meal (FM) was replaced by CPC at different inclusion levels: 0% (T0), 15% (T15), 30% (T30), and 45% (T45). The corresponding amounts of CPC included were 0, 61, 122, and 182 g/kg, respectively. At the end of the 10-week feeding trial, the findings revealed an inverse correlation between the proportion of CPC replacing FM and both final body weight (FBW) and weight growth rate (WG) in hybrid culter. Specifically, the T30 and T45 groups exhibited significantly lower FBW and WG compared to the T0 group (p 0.05). However, the crude lipid content was highest in hybrid culter fed the T45 diet and lowest in the T0 group (p 0.05). The contents of total protein (TP) and albumin (ALB) declined slightly as the proportion of FM substituted by CPC increased, yet this decline did not reach statistical significance (p > 0.05). Serum alanine aminotransferase (ALT) activity elevated with increasing dietary CPC, and the T45 group exhibited significantly higher ALT activity compared to the T0 group (p

Mortality risk of people living with HIV under hypothetical intervention scenarios of PM2.5 and HIV severity: a prospective cohort study - Shujuan Yang; Chuanteng Feng; Teng Fei; Dan Wu; Liao Feng; Fengshun Yuan; Yao Fu; Hua Ma; Bin Yu; Li Liu; Yizhuo Li; Yiping Li; et al. (Science of The Total Environment, 2024)

Behavioral and molecular response of the insect parasitic nematode Steinernema carpocapsae to plant volatiles - Peng-hua Bai; Jin-Ping Yu; Rui-rui Hu; Qian-wen Fu; Hai-chao Wu; Xing-yue Li; Guo-hao Zu; Bao-sheng Liu; Yu Zhang (Journal of Invertebrate Pathology, 2024)

Unusual weakening trend of the East Asian winter monsoon during MIS 8 revealed by Chinese loess deposits and its implications for ice age dynamics - Qingzhen Hao; Shuzhen Peng; Xinbo Gao; Slobodan B. Marković; Sheng-Hua Li; Junjie Zhang; Fengjiang Li; Long Han; Yu Fu; Xuechao Wu; Luo Wang; Bing Xu; et al. (Global and Planetary Change, 2024)

Multi-comparted microgels delivering human derived probiotics and deferoxamine for multidrug-resistant infection and healing - Chao Hua; Fengbo Yang; Xiaoli Jia; Yichi Lu; Xiaoxiao Li; Peng Zhao; Malcolm Xing; Guozhong Lyu (Chemical Engineering Journal, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Design of an active-source seismic detection system based on illumination analysis and migration imaging experiments: considering the Zhuxi mining area as an example - Wen Li; Yong Chen; Shan-Hui Xu; Jiu-Peng Hu; Bao-Jin Liu; Yong-Peng Ouyang; Yin-Juan He; Ya-Li Tan; Xin-Sheng Hua; Jing-Jing Qin; Qian Li; Jia Jia (Applied Geophysics, 2024)

PLZF protein forms a complex with protein TET1 to target TCF7L2 in undifferentiated spermatogonia - Xiaomin Du; Donghui Yang; Xiuwei Yu; Yudong Wei; Wenbo Chen; Yuanxin Zhai; Fanglin Ma; Mengfei Zhang; Shicheng Wan; Yunxiang Li; Xinchun Yang; Aili Aierken; et al. (Theriogenology, 2024)

Salvirrane A-F, six undescribed nordrimane sesquiterpene derivatives from Salvia castanea Diels f. tomentosa Stib and their cytotoxic activities - Rui Zhang; Dong-Dong Wang; Lian-Yu Tang; Peng-Xue Ji; Xin-Min Li; Zi-Feng Guo; Jue Wang; Jing-Ming Jia; An-Hua Wang (Phytochemistry, 2024)

Estimation of sequential transient flow around cylinders using recurrent neural network coupled graph convolutional network - Hao-Ran Xie; Yue Hua; Yu-Bai Li; Nadine Aubry; Wei-Tao Wu; Yong He; Jiang-Zhou Peng (Ocean Engineering, 2024)

Decoupling the effects of air temperature change on soil erosion in Northeast China - Yunfei Cao; Li Hua; Danying Peng; Yuhang Liu; Long Jiang; Qi Tang; Chongfa Cai (Journal of Environmental Management, 2024)

Functional characterization of RIP2 in large yellow croaker (Larimichthys crocea), a protein involved in the host antiviral responses via NF-κΒ, IRF3/7 related signaling - Jing Jiang; Ying Li; Kai Qing Li; Ying Jia Shen; Fang Li; Yi Lei Wang; Yong Hua Jiang; Peng Fei Zou (Fish & Shellfish Immunology, 2024)

Effects of dietary astaxanthin on growth performance, muscle composition, non-specific immunity, gene expression, and ammonia resistance of juvenile ivory shell (Babylonia areolate) - Teng Li; Pei-Hua Zheng; Xiu-Xia Zhang; Ze-Long Zhang; Jun-Tao Li; Jia-Jun Li; Jia-Rui Xu; Dong-Mei Wang; Jian-An Xian; Hui Guo; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

Effects of dietary chitosan oligosaccharide on the growth, intestinal microbiota and immunity of juvenile red claw crayfish (Cherax quadricarinatus) - Ze-Long Zhang; Yan-Lei Cao; Jia-Rui Xu; Xiu-Xia Zhang; Jia-Jun Li; Jun-Tao Li; Pei-Hua Zheng; Jian-An Xian; Yao-Peng Lu (Fish & Shellfish Immunology, 2024)

In-situ sodium chloride template synthesis of γ-WO3 hollow cubes for high-sensing and dual-selective hydrazine/dibutylamine detection at different temperatures - Guo-Li Chen; Ming-Song Lv; Jing Zhang; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2024)

Effect of simplified inoculum agent on performance and microbiome during cow manure-composting at industrial-scale - Weiwei Dong; Rui Zhou; Xudong Li; Hua Yan; Jinshui Zheng; Nan Peng; Shumiao Zhao (Bioresource Technology, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Molecular markers and phenotypic identification reveal the genetic diversity and structure of four local tea plant populations in China - Zhihui Wang; Hua Peng; Cuinan Yue; Chuan Ye; Wenjin Li; Puxiang Yang (Genetic Resources and Crop Evolution, 2024)

Overexpression of cucumber CYP82D47 enhances resistance to powdery mildew and Fusarium oxysporum f. sp. cucumerinum - Hong-yu Wang; Peng-fei Li; Yu Wang; Chun-yu Chi; Xiao-xia Jin; Guo-hua Ding (Functional & Integrative Genomics, 2024)

A new C 19 -diterpenoid alkaloid in Aconitum georgei Comber - Lin-Lin Yao; Sheng-Qi Zhang; Ce Guo; Bin-Xian Li; Hua-Juan Yang; Tian-Peng Yin; Le Cai (Natural Product Research, 2024)

Managing stability of aerobic granules by coordinating diameter and denitrification - Yong-Peng Huang; Xin Wang; Ruo-Lan Wang; Jin-Tao He; Yuan Huang; Zhen-Yu Hang; Xi Chen; Zhi-Hua Li (Science of The Total Environment, 2024)

Assessment of heavy metals concentrations in five marine organisms from Lianyungang in China and the corresponding health risk - Ya-Qin Zhang; Chun-Hui Gong; Xiang-Hua Qi; Wen-Jun Wang; Peng-Tao Cao; Qiang Li; Peng Wang; Yi Yang (Regional Studies in Marine Science, 2024)

The central Qiangtang Metamorphic Belt in northern Tibet is an in-situ Paleo-Tethys Ocean: Evidence from newly discovered Late Devonian radiolarians - Xin Li; Noritoshi Suzuki; Yi-chun Zhang; Hua Zhang; Mao Luo; Dong-xun Yuan; Quan-feng Zheng; Wen-kun Qie; Qi Ju; Feng Qiao; Hai-peng Xu; Xiao-hui Cui (Gondwana Research, 2024)

Classification of Rosa roxburghii Tratt from different geographical origins using non-targeted HPLC-UV-FLD fingerprints and chemometrics - Xiao-Dong Sun; Min Zhang; Shuo Zhang; Yi-Xuan Chen; Jun-Hua Chen; Peng-Jiao Wang; Xiu-Li Gao (Food Control, 2024)

Urban greenspaces shape soil protist communities in a location-specific manner - Hua-Yuan Shangguan; Stefan Geisen; Zhi-Peng Li; Hai-Feng Yao; Gang Li; Martin F. Breed; Stefan Scheu; Xin Sun (Environmental Research, 2024)

Efficacy of bioaugmentation with nondomesticated mixed microbial consortia under ammonia inhibition in anaerobic digestion - Chao Li; Fan Lü; Wei Peng; Pinjing He; Hua Zhang (Bioresource Technology, 2024)

Neomicrocoleus gen. nov. (Microcoleaceae, Oscillatoriales), a novel cyanobacterial genus from benthic mats in a water channel - Ruozhen Geng; Zhongshi He; Kaihui Gao; Peng Xiao; He Zhang; Si Chen; Hua Li; Gongliang Yu; Renhui Li (Journal of Oceanology and Limnology, 2024)

Analysis of light field and flow field of vortex rods tube photobioreactor based on field synergy principle - Siding Li; Hua Wen; Chuyi Peng; Chunyang Ma (Algal Research, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Investigation of the acicular aragonite growth behavior in AOD stainless steel slag during slurry-phase carbonation - Ya-Jun Wang; Jun-Guo Li; Meng-Jie Tao; Xi Zhang; Jian-Bao Zhang; Song Qin; Shao-Hua Liu; Li-Jie Peng; Xiao-Pei Zhang; Ya-Nan Zeng (Science of The Total Environment, 2023)

Associations between long-term exposure to PM2.5 chemical constituents and allergic diseases: evidence from a large cohort study in China - Chuanteng Feng; Ying Shao; Tingting Ye; Changwei Cai; Chun Yin; Xiaobo Li; Hongyun Liu; Hua Ma; Bin Yu; Mingfang Qin; Yang Chen; Yongfang Yang; et al. (Science of The Total Environment, 2023)

Rhizoid-associated cyanobacteria are the main contributors to biological nitrogen fixation in restored moss crust - Jiaoli Zheng; Dengcheng Zhang; Hua Li; Chengrong Peng; Yongding Liu; Dunhai Li (Rhizosphere, 2023)

Numerical simulation of hydrodynamic performance of pump-jet propulsor with serrated trailing-edge duct under different working conditions - Yu Sun; Li-xin Qu; Huang-hua Peng; Jia-min Guo; Zhi-xin Xiong (Ocean Engineering, 2023)

Identification and characterization of a novel Iflavirus in a stored-product psocid, Liposcelis bostrychophila (Psocodea: Liposcelididae) - Peng-Yu Guo; Dan-Dan Wei; Hua-Yue Feng; Xin-Ping Tang; Yu-Ang Chen; Yi Li; Jin-Jun Wang (Journal of Stored Products Research, 2023)

Long-term grazing improved soil chemical properties and benefited community traits under climatic influence in an alpine typical steppe - Yu-Wen Zhang; Ze-Chen Peng; Sheng-Hua Chang; Zhao-Feng Wang; Duo-Cai Li; Yu-Feng An; Fu-Jiang Hou; Ji-Zhou Ren (Journal of Environmental Management, 2023)

Separatable polydopamine-coated cobalt-chitosan beads for Cr(VI) removal from wastewater with superior capacity - Yimin Huang; Xueyan Li; Yan Peng; Hua Zhang; Anxian Shi; Xiujun Deng; Baoling Wang; Yingtang Zhou; Bing Wang; Guangzhi Hu (Journal of Environmental Chemical Engineering, 2023)

A novel non-centrifugal sugar prepared from tiger nut (Cyperus esculentus L.) meal: Preparation methods and comparison with sugarcane - Run-Yang Zhang; Xin-Yun Huang; Peng-Xiao Chen; Tian Li; Meng-Meng Jiang; Yi-Long Wang; Wen-Xue Zhu; Hua-Min Liu (Food Research International, 2023)

Correlations between flavor and fermentation days and changes in quality-related physiochemical characteristics of fermented Aurantii Fructus - Ya-Ting Xie; Ting-Ting Bai; Tao Zhang; Peng Zheng; Min Huang; Li Xin; Wen-Hui Gong; Abid Naeem; Fang-You Chen; Hua Zhang; Jin-Lian Zhang (Food Chemistry, 2023)

JAZ1 gene regulates starch biosynthesis and changes physicochemical properties in wheat grains - Sha-Sha Yuan; Peng Fan; Dan-Dan Zhang; Hai-Tao Liu; Peng-Fei Wang; Tian-Cai Guo; Ge-Zi Li; Yong-Hua Wang; Guo-Zhang Kang (Food Bioscience, 2023)

Joint effects of prenatal exposure to air pollution and pregnancy-related anxiety on birth weight: A prospective birth cohort study in Ma’anshan, China - Zhen-Hua Li; Yi-Cheng Mao; Yang Li; Sun Zhang; Hui-Yu Hu; Zhe-Ye Liu; Xue-Jie Liu; Jia-Wen Zhao; Kai Huang; Mao-Lin Chen; Guo-Peng Gao; Cheng-Yang Hu; et al. (Environmental Research, 2023)

Insights into unrevealing the effects of the monovalent cation substituted tunnel-type cathode for high-performance sodium-ion batteries - Wen-Jing Shi; Heng-Xiang Li; Ding Zhang; Fang-Hui Du; Yu-Han Zhang; Zhao-Yang Wang; Xiao-Hua Zhang; Peng-Fang Zhang (Chemical Engineering Journal, 2023)

Relative contribution of ammonia-oxidizing bacteria and denitrifying fungi to N2O production during rice straw composting with biochar and biogas residue amendments - Xu Lin; Naif Abdullah Al-Dhabi; Fanghong Li; Nanyi Wang; Hua Peng; Anwei Chen; Genyi Wu; Jiachao Zhang; Lihua Zhang; Hongli Huang; Binghua Yan; Lin Luo; et al. (Bioresource Technology, 2023)

CDK6 is a novel predictive and prognosis biomarker correlated with immune infiltrates in multiple human neoplasms, including small cell lung carcinoma - Guo-Sheng Li; Zhi-Guang Huang; Dong-Ming Li; Yu-Lu Tang; Jin-Hua Zheng; Lin Yang; Yue Feng; Jun-Xi Peng; Jing-Xiao Li; Yu-Xing Tang; Neng-Yong Zeng; Mei-Hua Jin; et al. (Functional & Integrative Genomics, 2023)

Chlorite-incorporated clay nanosheets as acid and H2O2-activated gas-bombs for combating peri-implant infection - Cheng Yang; Lei Chen; Pengfei Yang; Siteng Li; Ruanbin Li; Han Liu; Feng Peng; Mei Li; Dongdong Zhang; Dengwen Zheng; Donghui Wang; Hua Zhong (Applied Clay Science, 2023)

Complete genome sequence of Paris polyphylla chlorotic mottle virus infecting Paris polyphylla var. yunnanensis in southwest China - Qiongji He; Binghua Chen; Hongying Zheng; Yuhao Cao; Mengyin Hua; Yueyan Yin; Jiejun Peng; Junmin Li; Jianping Chen; Fei Yan; Xuemei Song; Lin Lin (Archives of Virology, 2023)

Land use decouples parasite–metazoan host biodiversity associations in soils across subtropical and temperate zones in China - Zhi‐Peng Li; Stefan Geisen; Hua‐Yuan Shangguan; Alexei V. Tiunov; Stefan Scheu; Yong‐Guan Zhu; Xin Sun (Global Ecology and Biogeography, 2023)
Aim Soils harbour a large number of unicellular eukaryotic parasites of metazoans, particularly Apicomplexa. Apicomplexan distribution, their associations with hosts, and impacts of human‐dominated land use are little studied. We aimed to fill this gap by a biodiversity survey across large spatial scales. Location China. Time period May to September 2021. Major taxa studied Soil Apicomplexa and Metazoa Methods We used metabarcoding to investigate the biogeography of and links between Apicomplexa and soil Metazoa in three human‐dominated ecosystem types (farmlands, residential areas and parks) and more natural forest ecosystems across subtropical, warm‐temperate and mid‐temperate climatic regions in China. Results Human‐dominated land use indirectly reduced apicomplexan taxon richness by reducing metazoan taxon richness. However, the richness reduction of parasites was generally more pronounced in subtropical and mid‐temperate regions than in the warm‐temperate region. Mechanisms driving the richness reduction of parasites also differed between climatic regions, with the reduction in the subtropical region less related to the decrease in metazoan richness than in the mid‐temperate region. Human‐dominated ecosystems reduced richness associations between parasites and Metazoa, and this disrupted the cascading effect of climatic factors from metazoan to parasite communities. Moreover, co‐occurrence analyses showed that metazoan taxa more abundant in human‐dominated land‐use systems with dryer and hotter conditions were less likely associated with apicomplexan taxa. Main conclusions We conclude that decreased host taxon richness is an important, but not the only driver of reduced parasite taxon richness in soil systems. Apicomplexan richness was largely decoupled from metazoan richness in human‐dominated ecosystems, which emphasizes the important role of human activities in rewiring fundamental ecological patterns with global change. Overall, the results advance our understanding of principle characteristics of and interactions in soil communities, and their response to human activities, especially agriculture and urbanization.

Blood Transcriptome Analysis Provides Responsive Changes in Gene Expression between Ex Situ and Captive Yangtze Finless Porpoises (Neophocaena asiaeorientalis asiaeorientalis) - Zhichen Cao; Denghua Yin; Zhanwei Li; Yan Yan; Peng Zhang; Sigang Zhang; Danqing Lin; Zhong Hua; Jialu Zhang; Congping Ying; Han Zhang; Pao Xu; et al. (Fishes, 2023)
The Yangtze finless porpoise (Neophocaena asiaeorientalis asiaeorientalis, YFP) is an endangered species endemic to the Yangtze River in China, and it is the only freshwater whale in the genus Neophocaena. In terms of protection, three effective conservation strategies exist: in situ conservation, ex situ conservation, and artificial breeding, all of which have been implemented by the Chinese government. Of these, ex situ conservation involves the relocation of Yangtze finless porpoises to semi-natural waters with less human interference, and artificial breeding involves the relocation of Yangtze finless porpoises to a controlled environment that is more strictly managed. To compare and analyze the responsive changes in gene expression of the YFPs between the ex situ and controlled environments, we performed the RNA sequencing of blood tissues from these YFPs. A total of 1201 differentially expressed genes (DEGs) were identified, of which 423 were up-regulated in the ex situ population and 778 were up-regulated in the controlled-environment population. Gene enrichment analysis showed that 1201 DEGs between the ex situ and controlled-environment populations were generally enriched for vision-, digestion- and immune-system-related pathways. Further analysis revealed that several key immune system pathways, such as the chemokine signaling pathway and B cell receptor signal pathway, were activated in the ex situ population. In addition, the key pathways related to vision, including phototransduction and the inflammatory mediator regulation of TRP channels, as well as the pathways related to the digestive system, such as protein digestion and absorption and salivary secretion, were activated in the controlled-environment population. These results suggest that the ex situ populations may respond to complex environmental conditions in semi-natural waters by enhancing their immune function through the increased expression of immune-related genes and that the visual function and protein digestion of the YFPs were improved compared to those of the ex situ population based on the conditions of artificial feeding, such as the higher transparency of the water and regular feeding. This study provides clues for evaluating the adaptability of YFPs to different environments and is a useful reference for future ex situ conservation and artificial breeding.

Local temperature responses to actual land cover changes present significant latitudinal variability and asymmetry - Xiangyang Liu; Zhao-Liang Li; Yitao Li; Hua Wu; Chenghu Zhou; Menglin Si; Pei Leng; Si-Bo Duan; Peng Yang; Wenbin Wu; Ronglin Tang; Meng Liu; et al. (Science Bulletin, 2023)

The effects of domain division types on the performance prediction of a rim-driven thruster - Peng Li; Cong Sun; Hua-Dong Yao; Zeping Wang; Chao Wang; Kaiqiang Weng (Ocean Engineering, 2023)

Phylotranscriptomic analyses reveal deep gene tree discordance in Camellia (Theaceae) - Qiong Zhang; Ryan A. Folk; Zhi-Qiong Mo; Hang Ye; Zhao-Yuan Zhang; Hua Peng; Jian-Li Zhao; Shi-Xiong Yang; Xiang-Qin Yu (Molecular Phylogenetics and Evolution, 2023)

Histopathological observation and comparative transcriptome analysis reveal immune response mechanisms to Aeromonas dhakensis infection in Macrobrachium rosenbergii - Xin Peng; Zhenxiao Zhong; Hua Zhong; Jinlin Gong; Tingting Du; Li Ding; Xuan Lan; Haihui Tu; Qiongying Tang; Zhenglong Xia; Guoliang Yang; Shaokui Yi (Fish & Shellfish Immunology, 2023)

Long-term anthropogenic field management enhanced wheat productivity and resource utilization in the Loess Plateau region of China - Peng Wu; Gang Zhao; Qi Wu; Hua Huang; Peng Zhang; Kemoh Bangura; Jianfu Xue; Min Sun; Shangzhong Li; Lei Wang; Wanli Cheng; Jian Fu; et al. (European Journal of Agronomy, 2023)

Laser boosting the influx of calcium ions to enhance gasdermin e-dependent pyroptosis driven by a dual-layer polydopamine nanoagonist - Xiaoling Qiu; Weixi Jiang; Xun Guo; Chier Du; Xiaoting Wang; Yu Tian; Hongjin An; Jingxue Wang; Yuanli Luo; Yuan Guo; Peng Luo; Hua Teng; et al. (Chemical Engineering Journal, 2023)

Recent positive selection signatures reveal phenotypic evolution in the Han Chinese population - Huaxia Luo; Peng Zhang; Wanyu Zhang; Yu Zheng; Di Hao; Yirong Shi; Yiwei Niu; Tingrui Song; Yanyan Li; Shilei Zhao; Hua Chen; Tao Xu; et al. (Science Bulletin, 2023)

Gas chromatography-mass spectrometry-based metabolomics reveals the potential mechanism of action of saikosaponin D against DSS-induced acute ulcerative colitis - Yujiao Yan; Shusheng Yin; Xueyan Bian; Junhui Li; Peng Wei; Xi Guo; Jingjie Zhou; Xiajuan Yao; Hong Hu; Deliang Kong; Haibing Hua; Yongming Li (Phytochemistry Letters, 2023)

Residual load-bearing capacity of corroded reinforced concrete columns with an annular cross-section - Hua-Peng Chen; Yu Jiang; Wen-Bin Li (Ocean Engineering, 2023)

Tree rings in Tsuga dumosa reveal increasing drought variability in subtropical southwest China over the past two centuries - Yun-Li Yin; Zaw Zaw; Xin-Hua Peng; Hui Zhang; Pei-Li Fu; Wen-Li Wang; Achim Bräuning; Ze-Xin Fan (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Extraction kinetics of separating molybdenum(Ⅵ) over iron(Ⅲ) from high acid leach solutions with mixtures of P507 and N235 - Miaomiao Peng; Keyu Shen; Yangjing Tan; Zhiyi Hu; Chun Liu; Zhixiong Liu; Wenbin Yan; Jun Hua; Fei Li (Minerals Engineering, 2023)

The microbial degradation of AAOO based cutting fluid wastewater - Bao-Hua Li; Jiang-Hua Huang; Xiao-Lei Li; Qian Ma; Peng-Fei Zhao; Wen Huang (Journal of Water Process Engineering, 2023)

Copper enhanced arsenic-accumulation in As-hyperaccumulator Pteris vittata by upregulating its gene expression for As uptake, translocation, and sequestration - Chen-Jing Liu; You-Jing Peng; Chun-Yan Hu; Si-Xue He; Shu-Fen Xiao; Wei Li; Song-Ge Deng; Zhi-Hua Dai; Lena Q. Ma (Journal of Hazardous Materials, 2023)

Increased ascorbic acid synthesis by overexpression of AcGGP3 ameliorates copper toxicity in kiwifruit - Xiaoying Liu; Chang Cheng; Yan Min; Xiaodong Xie; Abu Naim Md. Muzahid; Haiyan Lv; Hua Tian; Congxiao Zhang; Can Ye; Shifeng Cao; Peng Chen; Caihong Zhong; et al. (Journal of Hazardous Materials, 2023)

Analyzing spatial patterns and influencing factors of different illegal land use types within ecological spaces: A case study of a fast-growing city - Hua Li; Yinuo Peng; Minying Li; Yaye Zhuang; Xiaoyu He; Jinyao Lin (Journal of Cleaner Production, 2023)

A thermoplastic polyurethane-based composite aerogel with low shrinkage and high specific surface area enhanced by activated carbon for highly efficient oil/water separation - Qidong Wang; Jiayi Zhu; Fangjun Yu; Yunyan Li; Ye Zhang; Xiangwen Peng; Donghuan He; Siyi Zhao; Weihong Zheng; Jizhen Shang; Shuai Li; Hua Wang; et al. (Journal of Environmental Chemical Engineering, 2023)

New insights into the regulation mechanism of Pacific white shrimp (Litopenaeus vannamei) hepatopancreas under 4-nonylphenol exposure using transcriptome analysis - Pei-Hua Zheng; Yao-Peng Lu; Xiu-Xia Zhang; Ke-Er Luan; Ze-Long Zhang; Jia-Jun Li; Tong Xu; Jun-Tao Li; Jian-An Xian; Hui Guo; An-Li Wang (Fish & Shellfish Immunology, 2023)

Trade-offs and synergies of plant traits co-drive efficient nitrogen use in intercropping systems - Hao Yang; Wei-Ping Zhang; Hua-Sen Xu; Rui-Peng Yu; Ye Su; Surigaoge Surigaoge; Pei-Xuan Wang; Xin Yang; Hans Lambers; Long Li (Field Crops Research, 2023)

Crop cultivar mixtures stabilize productivity, partly via facilitation, when conditions are less benign - Ye Su; Rui-Peng Yu; Hua-Sen Xu; Jian-Hao Sun; Jian-Hua Zhao; Wei-Ping Zhang; Hao Yang; Surigaoge Surigaoge; Ragan M. Callaway; Long Li (Field Crops Research, 2023)

Temperature-dependent NO2/diisopropylamine sensor based on SnO2 squama-wrapped tubes derived from waste bamboo shoot skin - Bao-Yu Song; Cong Chen; Ya-Nan Li; Xian-Fa Zhang; Xiao-Li Cheng; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Development and validation of a machine learning model to predict prognosis in HIV-negative cryptococcal meningitis patients: a multicenter study - Junyu Liu; Yaxin Lu; Jia Liu; Jiayin Liang; Qilong Zhang; Hua Li; Xiufeng Zhong; Hui Bu; Zhanhang Wang; Liuxu Fan; Panpan Liang; Jia Xie; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2023)

Cytotoxic lanostane-type triterpenes from the fruiting bodies of Ganoderma lucidum - Xiu-run Huang; Fang Cai; Jing Chen; Chang-hui Wu; Ye Li; Jian-hua Xu; Peng Li (Natural Product Research, 2023)

Serum levels of IL-6/IL-10/GLDH may be early recognition markers of anti-tuberculosis drugs (ATB) -induced liver injury - Huai-Rong Xiang; Yun Li; Xuan Cheng; Bei He; Hua-Min Li; Qi-Zhi Zhang; Bin Wang; Wen-Xing Peng (Toxicology and Applied Pharmacology, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Hypoxia and panvascular diseases: exploring the role of hypoxia-inducible factors in vascular smooth muscle cells under panvascular pathologies - Yiqing Hu; Yongchao Zhao; Peng Li; Hao Lu; Hua Li; Junbo Ge (Science Bulletin, 2023)

Insights into the reaction of anammox to exogenous pyridine: Long-term performance and micro mechanisms - Jie Qian; Di Luo; Peng-fei Yu; Bin Ye; Ying-hua Li; Yong-yong Wang; Yu-nan Gao; Jin-xiang Fu (Bioresource Technology, 2023)

Study on the association of the microstructure and bone metabolism in the osteoporotic femoral head - Cheng Wang; Peng Wang; Feng Li; Yang Li; Minwei Zhao; Hui Feng; Haoye Meng; Junyang Li; Peng Shi; Jiang Peng; Hua Tian (Molecular Biology Reports, 2023)
Background We compared the bone microstructure and metabolism of the femoral heads in patients with osteoporosis (OP) and non-OP patients to investigate the pathologic mechanism of OP and guide clinical treatment. Methods and results From January 2020 to June 2021, we obtained femoral head samples from 30 patients undergoing hip replacement due to femoral neck fracture. All patients were women aged approximately 67 to 80 years (mean age, 74 years). According to the dual-energy X-ray results, the femoral head samples were divided into the OP (T< − 2.5) and non-OP (T > − 1.5) groups. Microcomputed tomography scanning, bone metrology analysis, hematoxylin and eosin staining, and Masson’s trichrome staining were used to compare the local bone trabecular microstructure changes. Quantitative reverse transcription PCR was performed to identify changes in the osteogenesis-related genes and the osteoclast-related genes in specific regions to reflect osteogenic and osteoclastic activities. Femoral heads with OP showed significant changes in the local bone microstructure. Bone density, bone volume fraction, and the number and thickness of the bone trabeculae decreased. Local bone metabolism was imbalanced in the areas with microstructural changes in femoral heads with OP, with increased osteoclast activity and decreased osteoblast activity. Conclusions Deterioration of bone microstructure is closely related to abnormal bone metabolism associated with the activity of osteoblasts and osteoclasts in osteoporotic femoral heads. Promoting bone formation by improving local bone metabolism, enhancing osteogenic activity and inhibiting osteoclast activity may be a promising way of preventing local OP and osteoporotic fractures.

Functional and molecular approaches for studying and controlling microbial communities in anaerobic digestion of organic waste: a review - Nora Dinova; Wei Peng; Mihaela Kirilova-Belouhova; Chao Li; Irina Schneider; Erqi Nie; Ivaylo Yotinov; Haowen Duan; Yovana Todorova; Fan Lü; Hua Zhang; Yana Topalova; et al. (Reviews in Environmental Science and Bio/Technology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Orogenic gold mineralization in the Huangling region and its intimate tectonic linkage to the Neoproterozoic orogeny of South China - Huimin Wang; Qinglin Xia; Zhou Zhou; Li Lei; Changliang Chen; Peng Yang; Yin Gong; Qi Hua; Qibing Bao (Precambrian Research, 2023)

Identification and expression characteristics of NLP (NIN-like protein) gene family in pepper (Capsicum annuum L.) - Yuan Wu; Shi-xian Su; Tao Wang; Gui-Hua Peng; Lei He; Cha Long; Wei Li (Molecular Biology Reports, 2023)

Supramolecular nanoassemblies-mediated GSH depletion boosts synergistic chemo- and photodynamic therapy for immunogenicity enhancement - Dun Wang; Wei Ma; Yun Huang; Wei Wang; Shuang Li; Hongbin Liu; Yuqi Zhao; Dongdong Peng; Cui-Yun Yu; Hua Wei (Chemical Engineering Journal, 2023)

Anthropogenic vulnerability assessment of global terrestrial protected areas with a new framework - Jiahui Meng; Yaoqi Li; Yuhao Feng; Fangyuan Hua; Xiaoli Shen; Sheng Li; Nawal Shrestha; Shijia Peng; Carsten Rahbek; Zhiheng Wang (Biological Conservation, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Long-term cadmium exposure induces chronic obstructive pulmonary disease-like lung lesions in a mouse model - Wen-Jing Wang; Kun Peng; Xue Lu; Yan-Yan Zhu; Zhao Li; Qing-Hua Qian; Ya-Xin Yao; Lin Fu; Yan Wang; Yi-Chao Huang; Hui Zhao; Hua Wang; et al. (Science of The Total Environment, 2023)

A clean two-stage Bayer process for achieving near-zero waste discharge from high-iron gibbsitic bauxite - Guo-tao Zhou; Yi-lin Wang; Yu-guan Zhang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Cleaner Production, 2023)

Pulsed counterclockwise rotation of the southwestern Sichuan Basin in response to the India-Asia convergence during 128-42 Ma - Qi Shen; Chun-Sheng Jin; Wen-Tian Liang; Chuan-Zhi Li; Hui-Hui Yang; Ya-Zhou Ran; Xuan He; Guan-Zuo Wu; Kai Jiang; Jian-Gang Li; Peng Han; Si-Hua Yuan (Earth and Planetary Science Letters, 2023)

Tailored interface composition improves the integrity of electrode/electrolyte interphases for high-voltage Ni-rich lithium metal batteries in a sulfolane-based electrolyte - Xiaodie Deng; Jialin Li; Pengbin Lai; Silan Kuang; Jiaxiang Liu; Pengpeng Dai; Haiming Hua; Peng Dong; Yingjie Zhang; Yang Yang; Jinbao Zhao (Chemical Engineering Journal, 2023)

Exploring deep residual network based features for automatic schizophrenia detection from EEG - Siuly Siuly; Yanhui Guo; Omer Faruk Alcin; Yan Li; Peng Wen; Hua Wang (Physical and Engineering Sciences in Medicine, 2023)
Schizophrenia is a severe mental illness which can cause lifelong disability. Most recent studies on the Electroencephalogram (EEG)-based diagnosis of schizophrenia rely on bespoke/hand-crafted feature extraction techniques. Traditional manual feature extraction methods are time-consuming, imprecise, and have a limited ability to balance accuracy and efficiency. Addressing this issue, this study introduces a deep residual network (deep ResNet) based feature extraction design that can automatically extract representative features from EEG signal data for identifying schizophrenia. This proposed method consists of three stages: signal pre-processing by average filtering method, extraction of hidden patterns of EEG signals by deep ResNet, and classification of schizophrenia by softmax layer. To assess the performance of the obtained deep features, ResNet softmax classifier and also several machine learning (ML) techniques are applied on the same feature set. The experimental results for a Kaggle schizophrenia EEG dataset show that the deep features with support vector machine classifier could achieve the highest performances (99.23% accuracy) compared to the ResNet classifier. Furthermore, the proposed model performs better than the existing approaches. The findings suggest that our proposed strategy has capability to discover important biomarkers for automatic diagnosis of schizophrenia from EEG, which will aid in the development of a computer assisted diagnostic system by specialists.

Two new compounds from edible mushroom Sarcomyxa edulis - Lan Yao; Jian-Hua Lv; Mei-Chen Pan; Lei Xing; Lu-Peng Wang; Chang-Tian Li; Shu-Yan Liu; Yu Li (Natural Product Research, 2023)

Corrigendum to “Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus)” [Aquaculture 563 (2023) /739023] - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Zein nanospheres assisting inorganic and organic drug combination to overcome stent implantation-induced thrombosis and infection - Hua-Jie Wang; Meng-Fei Hao; Guan Wang; Hao Peng; Fazli Wahid; Yan Yang; Lei Liang; Shan-Qin Liu; Ren-Long Li; Shu-Ying Feng (Science of The Total Environment, 2023)

Bioaccessibility and transport of lentil hull polyphenols in vitro, and their bioavailability and metabolism in rats - Fanghua Guo; Li Peng; Hua Xiong; Rong Tsao; Hua Zhang; Li Jiang; Yong Sun (Food Research International, 2023)

Evolution characteristic of atmospheric black carbon particles at a coastal site in the Pearl River Delta, China - Jing Wei; Xiao-Feng Huang; Yan Peng; Xiao-Yu Lin; Zhen-Hua Lei; Li-Ming Cao; Wen-Fei Zhu; Song Guo; Ling-Yan He (Environmental Pollution, 2023)

Low-temperature and dual-sensing NO2/dimethylamine sensor based on single-crystal WO3 nanoparticles-supported sheets synthesized by simple pyrolysis of spoiled WCl6 powder - Guo-Li Chen; Ming-Song Lv; Li-Li Sui; Zhao-Peng Deng; Ying-Ming Xu; Li-Hua Huo; Shan Gao (Chemical Engineering Journal, 2023)

Description of Limnobaculum eriocheiris sp. nov., an intestinal bacterium of Eriocheir sinensis, and reclassification of the genera Jinshanibacter and Insectihabitans as Limnobaculum - Nan-Nan Li; Hong-Chuan Wang; Jia-Yu Li; Wei He; Hua-Peng Xue; Tian-Heng Gao; Zhe Zhao; Dao-Feng Zhang (Antonie van Leeuwenhoek, 2023)

Outer membrane vesicles induce the mussel plantigrade settlement via regulation of c-di-GMP - Guanju Wu; Xiao-Meng Hu; Li-Hua Peng; Wen Zhang; Xiao Liang; Sergey Dobretsov; Jin-Long Yang (Biofouling, 2023)

Elucidating colony bloom formation mechanism of a harmful alga Phaeocystis globosa (Prymnesiophyceae) using metaproteomics - Hua-Min Cheng; Shu-Feng Zhang; Xiao-Lian Ning; Jian-Xiang Peng; Dong-Xu Li; Hao Zhang; Kun Zhang; Lin Lin; Si-Qi Liu; Walker O. Smith; Da-Zhi Wang (Science of The Total Environment, 2023)

Adsorptive removal of oxytetracycline in wastewater by Cu/Al doped carbon microspheres prepared from low-molecular-weight chitosan - Yan Huang; Leichao Wang; Ge Niu; Mingqing Hua; Linhua Zhu; Peng Cui; Xiaowei Li; Yanhong Chao; Wenshuai Zhu; Zhichang Liu (Journal of Environmental Chemical Engineering, 2023)

Toward sustainable green alumina production: A critical review on process discharge reduction from gibbsitic bauxite and large-scale applications of red mud - Guo-tao Zhou; Yi-lin Wang; Tian-gui Qi; Qiu-sheng Zhou; Gui-hua Liu; Zhi-hong Peng; Xiao-bin Li (Journal of Environmental Chemical Engineering, 2023)

Effect of air frying and baking on physicochemical properties and digestive properties of scallop (Patinopecten yessoensis) adductor muscle - Zi-Ye Wang; Zi-Xuan Wu; Guan-Hua Zhao; De-Yang Li; Yu-Xin Liu; Lei Qin; Peng-Fei Jiang; Da-Yong Zhou (Food Bioscience, 2023)

The role of MAPK/NF-κB-associated microglial activation in T-2 toxin-induced mouse learning and memory impairment - Na Li; Chun-Yan Yao; Jun Diao; Xiao-Ling Liu; En-Jie Tang; Qing-Song Huang; Yu-Meng Zhou; Yue-Gu Hu; Xiu-Kuan Li; Jin-Yun Long; Hua Xiao; Da-Wei Li; et al. (Food and Chemical Toxicology, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Arsenic induced plant growth by increasing its nutrient uptake in As-hyperaccumulator Pteris vittata: Comparison of arsenate and arsenite - You-Jing Peng; Chun-Yan Hu; Wei Li; Zhi-Hua Dai; Chen-Jing Liu; Lena Q. Ma (Environmental Pollution, 2023)

A localized high concentration carboxylic ester-based electrolyte for high-voltage and low temperature lithium batteries - Pengbin Lai; Boyang Huang; Xiaodie Deng; Jialin Li; Haiming Hua; Peng Zhang; Jinbao Zhao (Chemical Engineering Journal, 2023)

Salvia miltiorrhiza polysaccharide and its related metabolite 5-methoxyindole-3-carboxaldehyde ameliorate experimental colitis by regulating Nrf2/Keap1 signaling pathway - Yu-Ping Fu; Xi Peng; Chao-Wen Zhang; Quan-Xing Jiang; Cen-Yu Li; Berit Smestad Paulsen; Frode Rise; Chao Huang; Bin Feng; Li-Xia Li; Xing-Fu Chen; Ren-Yong Jia; et al. (Carbohydrate Polymers, 2023)

How much urban air quality is affected by local emissions: A unique case study from a megacity in the Pearl River Delta, China - Meng-Xue Tang; Xiao-Feng Huang; Pei-Ting Yao; Run-Hua Wang; Zhi-Jie Li; Chao-Xi Liang; Xing Peng; Li-Ming Cao; Ke Du; Kuangyou Yu; Song Guo (Atmospheric Environment, 2023)

Cesium exposure and pulmonary function decline: Potential mediating role of oxidative stress in chronic obstructive pulmonary disease patients - Min-Min Tang; Xue-Feng Hou; Jing Sun; Jia-Yi Cheng; You-Peng Deng; Meng-Die Li; Ling Liu; Dong-Xu Hua; Jin Yang; Ya-Lin Jiang; Lin Fu; Hui Zhao (Atmospheric Pollution Research, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Effect of Tip Rake Distribution on the Hydrodynamic Performance of Non-Planar Kappel Propeller - Chen-Wei Chen; Xu-Peng Chen; Zhao-Ye Zhou; Li-Wan Chen; Chi Zhang; Tian-Jiang Zheng; Hua-Min Li (Journal of Marine Science and Engineering, 2023)
Taking advantage of end-plate effects to enhance propeller efficiency is engaging. This paper applied a 4-order B-spline curve to design the rake distribution of Kappel propellers using five types of Kappel propellers that each possesses different tip rakes, and one type has no constructed end-plate. The RANS method coupled with the γ transition model was utilized to analyze the open-water performance of the six propellers, considering cavitating flow. It was found that the tip rake is conducive to the thrust capacity of the Kappel propellers, mostly improving the propulsion efficiency by 2.5% at a designed advance speed with the appropriate tip rake. The increase in the tip rake will magnify the low-pressure value and area on the suction side blade surface, together with the phenomenon of the stretching tip vortex and the inhibition of wake vortex contraction, which are both beneficial to the elevation of propulsion efficiency. However, the sheet cavitation behavior of the six propellers aggravates as the tip rake rises. Accordingly, the reasonable range of a tip rake for the design of a Kappel propeller in favor of the propulsion performance is suggested in this paper, exhibiting the promising potential of energy savings for the application to marine vehicles.

Hydroquinone triggers pyroptosis and endoplasmic reticulum stress via AhR-regulated oxidative stress in human lymphocytes - Xiaohan Yang; Shuangyan Dong; Chao Li; Ming Li; Caihong Xing; Jin He; Cheng Peng; Hua Shao; Qiang Jia (Toxicology Letters, 2023)

Continuous rotating bending NiTi sheets for elastocaloric cooling: Model and experiments - Siyuan Cheng; Yinan Xiao; Xueshi Li; Hongyang Lin; Peng Hua; Liyuan Sheng (International Journal of Refrigeration, 2023)

Fine mapping and candidate gene analysis of qFL-A12-5: a fiber length-related QTL introgressed from Gossypium barbadense into Gossypium hirsutum - Xianghui Xiao; Ruixian Liu; Juwu Gong; Pengtao Li; Ziyin Li; Wankui Gong; Aiying Liu; Qun Ge; Xiaoying Deng; Shaoqi Li; Quanjia Chen; Hua Zhang; et al. (Theoretical and Applied Genetics, 2023)

Transcriptomic analysis provides new insights into the secondary follicle growth in spotted scat (Scatophagus argus) - Mou-Yan Jiang; Yi-Fan Zhou; Hao Liu; You-Xing Peng; Yuan-Qing Huang; Si-Ping Deng; Yang Huang; Gang Shi; Chun-Hua Zhu; Guang-Li Li; Dong-Neng Jiang (Frontiers in Marine Science, 2023)
Spotted scat ( Scatophagus argus ) is an important mariculture fish that is of great economic significance in East and Southeast Asia. To date, there are no studies on ovary development and regulation in S. argus . Herein, the ovary transcriptome profiles of S. argus at different stages were constructed, and the genes and pathways potentially involved in secondary follicle growth were identified. A total of 25,426 genes were detected by sequencing the mRNAs from the ovary libraries at stage III (n=3) and IV (n=3). Notably, 2950 and 716 genes were up-regulated and down-regulated in the stage IV ovary, respectively, compared to the stage III ovary. The differentially expressed genes (DEGs) were found to be mostly involved in regulating steroidogenesis, vitellogenesis, lipid metabolism, and meiosis. Up-regulation of steroid hormone synthesis pathway genes ( fshr , cyp17a1 , and foxl2 ) and insulin-like growth factor pathway genes ( igf1r , ifg2r , igfbp1 , igfbp3 , and igfbp7 ) in the ovary at stage IV was possibly the reason for the increased serum estrogen. Moreover, ppara , ppard , fabp3 , and lpl were up-regulated in the stage IV ovary and were potentially involved in the lipid droplet formation in the oocyte. Many DEGs were involved in the cellular cycle, meiosis, and cAMP or cGMP synthesis and hydrolysis, indicating that meiosis was restarted at stage IV ovary. In addition, numerous TGF-beta signal pathway genes were up-regulated in the stage IV ovary. This ovary transcript dataset forms a baseline for investigating functional genes associated with oogenesis in S. argus .

Cross-modality comparison between structural and metabolic networks in individual brain based on the Jensen-Shannon divergence method: a healthy Chinese population study - Yu-Lin Li; Mou-Xiong Zheng; Xu-Yun Hua; Xin Gao; Jia-Jia Wu; Chun-Lei Shan; Jun-Peng Zhang; Dong Wei; Jian-Guang Xu (Brain Structure and Function, 2023)

Teleost TRAF7, a protein functions in the host antiviral responses via NF-κB and IRF3/7 mediated signaling - Peng Tian Li; Ying Li; Ying Chen; Jia Xi Zhang; Zi Hao Luo; Yi Fan Zhang; Jing Jiang; Yi Lei Wang; Zi Ping Zhang; Yong Hua Jiang; Peng Fei Zou (Frontiers in Marine Science, 2023)
Tumor necrosis factor receptor-associated factors (TRAFs) play vital roles in tumor necrosis factor receptor (TNF-R) and interleukin-1 receptor/Toll-like receptor (IL-1R/TLR) mediated signaling pathway. However, the role that TRAF7 plays in the host immune responses is largely unknown in comparison to the extensive and in-depth research that has been conducted on other members of the TRAF family. Notably, Lc -TRAF7, a cloned TRAF7 ortholog, was discovered in the large yellow croaker ( Larimichthys crocea ) in the current study, which has an open reading frame (ORF) of 1,962 base pairs and encodes a protein of 653 amino acids (aa). Lc -TRAF7 is consisted of a RING finger domain, a coiled-coil domain, and seven WD40 domains, with the genomic organization consisted of 20 exons and 19 introns. According to the expression analysis, Lc-TRAF7 was presented in a wide range of detected organs and tissues of the healthy fish, and was able to significantly induced by stimulations of poly I:C, LPS, PGN, and Pseudomonas plecoglossicida infection. Subcellular distribution analysis revealed that Lc- TRAF7 was a cytoplasmic protein, with the RING finger and coiled-coil domain function importantly in its subcellular localization. Luciferase assays demonstrated that Lc -TRAF7 overexpression significantly induced the activation of NF-κB, IRF3, IRF7, and IFN1 promoters. In addition, the WD40 domains play a pivotal role in the NF-κB promoter activation, whereas the RING finger and coiled-coil domain were essential in the IRF3, IRF7, and IFN1 promoter activation. Notably, Lc -TRAF7 overexpression could suppress SVCV proliferation in EPC cells, and the expression levels of IRF3 , IRF7 , ISG15, ISG56 , RSAD2 , and TNF-α were up-regulated under Lc -TRAF7 overexpression in LYCMS cells. These findings collectively implied that Lc -TRAF7 may function as an important regulator in the host antiviral responses via the NF-κB as well as IRF3/7 involved signaling pathways.

An antioxidant lignan glycoside and triterpenoid saponins from the leaves of Synsepalum dulcificum - Xin-Peng Li; Jun-Fei Wang; Rong Huang; Tang-Chang Xu; Si-Si Liu; Qing-Rong Yang; Shao-Hua Wu (Phytochemistry Letters, 2023)

Numerical investigation on vortex control effect of pump-jet propulsion via porous blade tips - Yu Sun; Li-xin Qu; Geng Wang; Huang-hua Peng; Jia-min Guo (Ocean Engineering, 2023)

2000 years of lake-level fluctuations and human adaptation around China's largest freshwater lake - Huanye Wang; Weiguo Liu; Qin Leng; Lin Yang; Hui Zhao; Jun Yang; Yuwei Chen; Shangbin Xiao; Yunning Cao; Jing Hu; Xiaoke Qiang; Peng Cheng; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Using apatite to differentiate metallogenic potential and environment of granitic rocks: A case study from the Tongshanling W-Sn-Cu-Pb-Zn ore field, Nanling Range (South China) - Xiao-jun Hu; Huan Li; Michael W. Förster; Safiyanu Muhammad Elatikpo; Hua Kong; Jing-hua Wu; Da-peng Zhu (Journal of Geochemical Exploration, 2023)

Synergetic effect of Ce/Zr for ethanol synthesis from syngas over Rh-based catalyst - Caixia Zhu; Kaizhuang Xu; Yuan Fang; Qian Lv; Kun Jiang; Huibo Zhao; Yang Chen; Peng Wang; Hua Yang; Lizhi Wu; Yu Tang; Li Tan (Fuel, 2023)

Symbiotic Ni3Se4/Ni heterostructure induced by unstable NiSe2 for enhanced hydrogen generation - Kailu Guo; Yantao Wang; Junfeng Huang; Hua Li; Yong Peng; Cailing Xu (Chemical Engineering Journal, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Cover crop by irrigation and fertilization improves soil health and maize yield: Establishing a soil health index - Peng Li; Huijuan Zhang; Jianjun Deng; Libo Fu; Hua Chen; Chunkai Li; Li Xu; Jiaguo Jiao; Shixiang Zhang; Jidong Wang; Duo Ying; Huixin Li; et al. (Applied Soil Ecology, 2023)

Paracoccus marinaquae sp. nov., isolated from coastal water of the Yellow Sea - Hua-Peng Xue; Zi-Yue Fu; Wei He; Lei Wang; Wen-Jun Li; Ai Hua Zhang; Jian-Ke Huang; Dao-Feng Zhang; Zhe Zhao (Archives of Microbiology, 2023)

Identification of sex-linked marker and candidate sex determination gene in ornamental fish, African scat (Scatophagus tetracanthus) - You-Xing Peng; Yuan-Qing Huang; Jian Zhong; Zheng-Ting Jiang; Sen Fan; Hong-Juan Shi; Hua-Pu Chen; Si-Ping Deng; Guang-Li Li; Dong-Neng Jiang (Aquaculture, 2023)

Alleviation of Cd-polluted paddy soils through Si fertilizer application and its effects on the soil microbial community - Hua Peng; Kai Deng; Yu Shi; Saihua Liu; Zhu Jian; Changjun Li; Xionghui Ji; Shengnan Li (Science of The Total Environment, 2023)

Sesquiterpenoids and monoterpenoids from the water decoction of Valeriana officinalis L - Shi-Wei Li; Bian-Xia Xue; Tian-Tian Yang; Ran Li; Mingjie Zhang; Miao Wang; Li-Hua Zhang; Peng Zhang; Yi Zhang; Tao Wang; Shao-Xia Wang; Hong-Hua Wu (Phytochemistry, 2023)

The profiles of durian (Durio zibethinus Murr.) shell phenolics and their antioxidant effects on H2O2-treated HepG2 cells as well as the metabolites and organ distribution in rats - Yangzheng He; Li Peng; Hua Xiong; Wenqiang Liu; Hua Zhang; Xin Peng; Xuemei Zhu; Fanghua Guo; Yong Sun (Food Research International, 2023)

New insights into the regulation mechanism of red claw crayfish (Cherax quadricarinatus) hepatopancreas under air exposure using transcriptome analysis - Yao-Peng Lu; Pei-Hua Zheng; Xiu-Xia Zhang; Jun-Tao Li; Ze-Long Zhang; Jia-Rui Xu; Yong-Qi Meng; Jia-Jun Li; Jian-An Xian; An-Li Wang (Fish & Shellfish Immunology, 2023)

Association between ambient carbon monoxide levels and hospitalization costs of patients with myocardial infarction: Potential effect modification by ABO blood group - Qing-Song Huang; Lai-Xin Zhou; Li-Li Yang; Yue-Xu Jiang; Hua Xiao; Da-Wei Li; Yu-Meng Zhou; Yue-Gu Hu; Na Li; Ya-Fei Li; Ai-Ling Ji; Peng Luo; et al. (Environmental Research, 2023)

Can sedentarization decrease the dependence of pastoral livelihoods on ecosystem services? - Xuhuan Dai; Bo Li; Hua Zheng; Yanzheng Yang; Zihan Yang; Chenchen Peng (Ecological Economics, 2023)

Cellulose mineralization with in-situ synthesized amorphous titanium dioxide for enhanced adsorption and auto-accelerating photocatalysis on water pollutant - Jin-Long Zhu; Shi-Peng Chen; Wei Lin; Hua-Dong Huang; Zhong-Ming Li (Chemical Engineering Journal, 2023)

W18O49 sensitized with Pd nanoparticles for ultrasensitive ppb-level formaldehyde detection - Peng Wang; Shisong Guo; Zhixiang Hu; Tiankun Li; Shiliang Pu; Hui Mao; Hong Cai; Zhenfeng Zhu; Hua-Yao Li; Huan Liu (Chemical Engineering Journal, 2023)

Construction of 3D ternary layered double hydroxides on nickel foam for enhancing dielectric barrier discharge plasma to degrade DUR: Performance, mechanism and energy efficiency - Tianyao Shen; Xiaojing Wang; Jiaqin Li; Chunyan Yang; Peng Xu; Hua Chai; Peng Wang; Guangshan Zhang (Chemical Engineering Journal, 2023)

Stitching electron localized heptazine units with “carbon patches” to regulate exciton dissociation behavior of carbon nitride for photocatalytic elimination of petroleum hydrocarbons - Qi Guo; Yuning Wu; Linhong Xia; Xue-Fang Yu; Kaisheng Zhang; Yujie Du; Lixue Zhang; Hua Tang; Jianbo Cheng; Jianpeng Shang; Yanhua Peng; Zhuo Li; et al. (Chemical Engineering Journal, 2023)

Poly(ionic liquid) boosts overall performance of electrocatalytic reduction of low concentration of CO gas - Guo-Yi Duan; Xiao-Qiang Li; Jun-Wu Chen; Guang-Rong Ding; Peng-Xin Guan; Bao-Hua Xu (Chemical Engineering Journal, 2023)

Receptor and Ionic Mechanism of Histamine on Mouse Dorsolateral Striatal Neurons - Jian-Ya Peng; Kang-Li Shen; Xiu-Juan Fan; Zeng-Xin Qi; Hui-Wei Huang; Jian-Lan Jiang; Jian-Hua Lu; Xiao-Qin Wang; Xiao-Xia Fang; Wang-Rui Yuan; Qiao-Xuan Deng; Shu Chen; et al. (Molecular Neurobiology, 2023)

The complete mitochondrial genome of Parachiloglanis hodgarti and its phylogenetic position within Sisoridae - Jiasheng Li; Ying Peng; Shufei Zhang; Yifan Liu; Kun Zhang; Jian Chen; Hua Zhang; Chi Zhang; Bingjian Liu (Journal of Oceanology and Limnology, 2023)

Effects of Dietary Eucommia ulmoides Leaf Extract on Growth, Muscle Composition, Hepatopancreas Histology, Immune Responses and Microcystin-LR Resistance of Juvenile Red Claw Crayfish (Cherax quadricarinatus) - Yao-Peng Lu; Pei-Hua Zheng; Jia-Rui Xu; Yan-Lei Cao; Jun-Tao Li; Chen-Guang Hao; Ze-Long Zhang; Jian-An Xian; Xiu-Xia Zhang; An-Li Wang (Fishes, 2022)
The objective of the present study was to investigate the effects of different doses of dietary Eucommia ulmoides leaf extract (ELE) on juvenile red claw crayfish (Cherax quadricarinatus). A total number of 720 red claw crayfish (initial body weight of 0.24 ± 0.01 g) were randomly assigned to six groups and fed diets containing 0 (Diet 1), 0.5 (Diet 2), 1 (Diet 3), 2 (Diet 4), 4 (Diet 5) and 10 (Diet 6) g dry weight (dw) ELE kg (dw)−1 diets for eight weeks and challenged with microcystin-LR stress. The results indicated that dietary supplementation with 1–2 g dw ELE kg (dw)−1 diet could significantly improve the weight gain rate (WGR) and specific growth rate (SGR) of crayfish. Muscle crude protein contents of crayfish fed Diet 2, Diet 3, and Diet 4 were significantly higher than those of the control group. Compared with the control group, dietary ELE could increase total antioxidant capacity (T-AOC), superoxide dismutase (SOD), glutathione peroxidase (GPx), acid phosphatase (ACP), alkaline phosphatase (AKP), and phenoloxidase (PO) activities and decrease malondialdehyde (MDA) level of crayfish. Dietary ELE significantly increased the relative expression levels of SOD, thioredoxin 1 (TRX1), GPx, selenium-dependent glutathione peroxidase (Se-GPx), cytochrome P450 (CYP450), anti-lipopolysaccharide factor (ALF) and C-type lysozyme (C-LZM) mRNA of crayfish compared with the control group during the feeding experiment. When subjected to MC-LR stress for 48 h, the mRNA expression levels of SOD, GPx, Se-GPx, glutathione-s-transferase 1 (GST1), ALF, hemocyanin (HEM), and C-LZM in the hepatopancreas could be improved to varying degrees compared with the Diet 1. Supplementation of 1–2 g dw ELE kg (dw)−1 diet could improve the survival rate (SR) of crayfish under MC-LR stress. These results indicated that dietary ELE (1–2 g dw ELE kg (dw)−1 diet) could improve the growth performance, muscle protein, and non-specific immune response and increase the SR of crayfish under MC-LR stress by regulating the mRNA expression levels of the immune- and antioxidant-related genes.

46,XY disorders of sex development: the use of NGS for prevalent variants - Qi-Gen Xie; Peng Luo; Kai Xia; Zuo-Qing Li; Zhe Xu; Cheng Su; Chun-Hua Deng (Human Genetics, 2022)

Selection of core evaluation indices and construction of a comprehensive evaluation method for machine-harvested tea plant cultivars - Zhihui Wang; Hua Peng; Cuinan Yue; Wenjin Li; Zhongfei Tong; Puxiang Yang (Euphytica, 2022)

Genetic variations in the bitter taste receptor gene TAS2R38 are related to cigarette smoking behavior in Han Chinese smokers - Fei-Yan Qi; Zhou-Hai Zhu; Meng Li; Ying Guan; Qi-Yuan Peng; She-Ming Lu; Zhi-Hua Liu; Ming-Feng Wang; Ming-Ming Miao; Zhang-Yu Chen; Xue-Mei Li; Jie Bai; et al. (Genes & Genomics, 2022)

Immobilization of Cd2+ and Pb2+ by biomineralization of the carbonate mineralized bacterial consortium JZ1 - Peng Zhang; Xiao-Qiang Liu; Li-yuan Yang; Hua-ze-yu Sheng; An-qi Qian; Ting Fan (Environmental Science and Pollution Research, 2022)

Spatiotemporal resilience assessment and comparison in China’s bay area - Yu Han; Yaowen Zhang; Han Zhang; Cuicui Feng; Tianran Hua; Yiqun Yang; Peng Yun; Jian Zeng; Li Peng; Jiangning Zeng; Guanqiong Ye (Frontiers in Marine Science, 2022)
The bay area is a crucial land–sea junction zone containing essential urban clusters while receiving extremely complex internal and external disturbances that challenge more on its resilience management. However, a sound management tool based on the bay area’s resilience is widely lacking due to the difficulty of unifying resilience indicators and quantifying resilience relationships between regions. This paper tries to establish a comprehensive resilience index for coastal bays from four major resilience-related dimensions, namely, physical structure, social development, ecological environment, and hazards, and applies it into the three major developed bay areas in China. A coupling coordination degree model was used to further reveal the resilience development and its internal coordination by temporal and spatial differences. The results show that the index could clearly reveal the resilience changes from the year 2000 to 2020 of the three bays with the common key drivers of socioeconomic development. It also explains the resilience changes among three bay areas through analyzing synergistic and conflict relationships between the four sub-resilience systems.

Assessment of paddy expansion impact on regional climate using WRF model: a case study in Sanjiang Plain, Northeast China - Peng Huang; Dan Li; Hua Xie; Chaoli Liu; Hayat Ullah; Yang Xu; Changhong Song; Chunsheng Dai; Yuanlai Cui; Yufeng Luo (Theoretical and Applied Climatology, 2022)

Effect of posaconazole on the concentration of intravenous and oral cyclosporine in patients undergoing hematopoietic stem cell transplantation - Li-E Zhu; Hui-Ping Huang; Yi-Peng Cai; Yan Wang; Bao-Hua Xu; Mao-Bai Liu; Xue-Mei Wu (European Journal of Clinical Pharmacology, 2022)

Functional analysis of HADH c.99C>G shows that the variant causes the proliferation of pancreatic islets and leu-sensitive hyperinsulinaemia - Wu Long; Yue-Bing Wang; Peng-Fei Qu; Lin Ma; Si-Jie Wei; Yan-Mei Xi; Jin-Liang Du; Xue Tang; Kai Liu; Yu-Hua Li; Pu-Ping Lei (Journal of Genetics, 2022)

Transgenic expression of rice OsPHR2 increases phosphorus uptake and yield in wheat - Yan Li; Yuhui Fang; Chaojun Peng; Xia Hua; Yu Zhang; Xueli Qi; Zhengling Li; Yumin Wang; Lin Hu; Weigang Xu (Protoplasma, 2022)

Single-base methylome analysis reveals dynamic changes of genome-wide DNA methylation associated with rapid stem growth of woody bamboos - Liang-Zhong Niu; Wei Xu; Peng-Fei Ma; Zhen-Hua Guo; De-Zhu Li (Planta, 2022)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

Succession of Aphanizomenon flos-aquae and Microcystis aeruginosa in direct co-culture experiments at different temperatures and biomasses - Qianzhi Wen; Peng Xiao; Hua Li; Wenke Li; Gongliang Yu; Renhui Li (Journal of Oceanology and Limnology, 2022)

Negative air ion exposure ameliorates depression-like behaviors induced by chronic mild stress in mice - Yun-Qing Hu; Ting-Ting Niu; Jian-ming Xu; Li Peng; Qing-Hua Sun; Ying Huang; Ji Zhou; Yu-Qiang Ding (Environmental Science and Pollution Research, 2022)
The presence of negative air ions (NAI) is suggested to be a beneficial factor in improving psychological status and used in treating depression as an alternative approach. However, more biological evidence from animal models is needed to ensure the effects of NAI on the mood regulation, through which can facilitate identification of possible underlying mechanisms. In this study, the chronic mild stress (CMS) protocol was used to induce depressive-like behaviors in mice, and the effects of NAI exposure on CMS-induced depression-like behaviors were examined. Thirty-day NAI exposure prevented the CMS-induced depression-like behaviors as shown by the restoration of sucrose preference and reduced immobility time in the tail suspension test. In addition, the elevation of serous corticosterone was present in CMS-treated mice but not existed in those with the NAI exposure. Furthermore, we observed altered ratios of some cytokines secreted by type 1 T helper (Th1) cells and Th2 cells in CMS-treated mice, but it could be restored after NAI exposure. In conclusion, NAI intervention is able to ameliorate CMS-induced depression-like behaviors in mice, and this effect is associated with the alteration of corticosterone and functional rebalance between Th1 and Th2 cells.

Comparative genomic analysis of the genus Marinomonas and taxonomic study of Marinomonas algarum sp. nov., isolated from red algae Gelidium amansii - Jian-Heng Xue; Bei-Ning Zhang; Feng Zhang; Ying-Ying Liu; Wen-Jie Wu; Zhao-Ming Wu; Yue Si; Peng-Xi Yang; Xiang Xing; Li-Hua Zhao (Archives of Microbiology, 2022)

Preparation and Biocompatibility Study of Contrast-Enhanced Hernia Mesh Material - Xuzhong Ding; Jiachen Zhu; Anning Liu; Qiyang Guo; Qing Cao; Yu Xu; Ye Hua; Yumin Yang; Peng Li (Tissue Engineering and Regenerative Medicine, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Systematic contributions of CFEM domain‐containing proteins to iron acquisition are essential for interspecies interaction of the filamentous pathogenic fungus Beauveria bassiana - Yue‐Jin Peng; Jia Hou; Hao Zhang; Jia‐Hui Lei; Hai‐Yan Lin; Jin‐Li Ding; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2022)
Summary Common in fungal extracellular membrane (CFEM) domain is unique in fungal proteins and some of which contribute to iron acquisition in yeast. However, their roles in iron acquisition remain largely unknown in filamentous fungi. In this study, 12 CFEM‐containing proteins were bioinformatically identified in the filamentous entomopathogenic fungus Beauveria bassiana , and the roles of 11 genes were genetically characterized. Transmembrane helices were critical for their association with intracellular membranes, and their number varied among proteins. Eleven CFEM genes significantly contribute to vegetative growth under iron starvation and virulence. Notably, the virulence of most disruptants could be significantly weakened by a decrease in iron availability, in which the virulence of Δ Bbcfem7 and 8 strains was partially recovered by exogenous hemin. Δ Bbcfem7 and 8 mutants displayed defective competitiveness against the sister entomopathogenic fungus Beauveria brongniartii . All 11 disruptants displayed impaired growth in the antagonistic assay with the saprotrophic fungus Aspergillus niger , which could be repressed by exogenous ferric ions. These findings not only reveal the systematic contributions of CFEM proteins to acquire two forms of iron (i.e. heme and ferric ion) in the entire lifecycle of entomopathogenic fungi but also help to better understand the mechanisms of fungus–host and inter–fungus interactions.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Microbial composition and nitrogen removal pathways in a novel sequencing batch reactor integrated with semi-fixed biofilm carrier: evidence from a pilot study for low- and high-strength sewage treatment - Peng-fei Chen; Rui-jian Zhang; Zhi-li Du; Guang-hua Wang; Hao-tao Dong; Bin Cui; Ru-pei Fan; Lu-xin Li; Qian-bin Wang; Ying-shi Liu; Zhi-min Sun (Environmental Science and Pollution Research, 2022)

Anti-inflammatory and antioxidant activities of chemical constituents from the flower buds of Buddleja officinalis - Fei-Bing Huang; Na Liang; Nusrat Hussain; Xu-Dong Zhou; Muhammad Ismail; Qing-Ling Xie; Huang-He Yu; Yu-Qing Jian; Cai-Yun Peng; Bin Li; Bin Liu; Sheng-Huang Chen; et al. (Natural Product Research, 2022)

Corrigendum: The Identification of Fish Eggs From Four Economically Important Species in Guanghai Bay (China) - Yan-Jing Zheng; Xiao-Juan Peng; Wei-Xu Cai; Quan-Sheng Lou; Xiang-Li Lyu; Ying-Hua Huang (Frontiers in Marine Science, 2022)

LncDACH1 promotes mitochondrial oxidative stress of cardiomyocytes by interacting with sirtuin3 and aggravates diabetic cardiomyopathy - Qi Zhang; Danyang Li; Xue Dong; Xiaowen Zhang; Junwu Liu; Lili Peng; Bo Meng; Qi Hua; Xinyu Pei; Lu Zhao; Xiaoxi Hu; Yang Zhang; et al. (Science China Life Sciences, 2022)

The Identification of Fish Eggs From Four Economically Important Species in Guanghai Bay (China) - Yan-Jing Zheng; Xiao-Juan Peng; Wei-Xu Cai; Quan-Sheng Lou; Xiang-Li Lyu; Ying-Hua Huang (Frontiers in Marine Science, 2022)
By far, very few studies have dealt with the ichthyoplankton diversity in Guanghai Bay (China), which is a potential spawning ground for many important fish species. In this study, fish eggs collected in Guanghai Bay were identified through molecular method combined with visual taxonomic method. We employed two mitochondrial gene regions of cytochrome c oxidase subunit I (COI) and 16S ribosomal RNA (16S rRNA) as genetic markers for species identification. Through sequence identification at NCBI, 121 eggs with overlapping size range and easy to be confused were discriminated as four economically important species: seven as silver sillago Sillago sihama , 48 as black-banded sillago Sillago nigrofasciata , 38 as yellow drum Nibea albiflora , and 28 as Pacific seabream Acanthopagrus pacificus . Phylogenetic analyses showed that these 121 eggs clustered in four groups with strong support. To testify the validity of these identification results, species identification through five BarcodingR package methods was also carried out using sequences of 33 fish specimens as a reference library covering four target species. Finally, a highly consensus of species assignment results was achieved across different methods. Morphological characteristics and detailed photographs for eggs from these four species were supplied here. Eggs of each species are pelagic, round, have a smooth chorion and one single oil globule. Embryonic pigment patterns vary as eggs develop and can be used for species distinguishing. Eggs from S. nigrofasciata and A. pacificus were described for the first time in this study. One simple and accurate method for identifying N. albiflora eggs was additionally provided. Moreover, the morphological differences between two Sillago eggs offered supportive evidence for the recent separation of S. nigrofasciata as a new species from S. sihama . All these results would be critical for the discrimination of eggs from these four species and the estimation for their spawning areas. Meanwhile, our study would contribute to the stock assessment and fishery management in Guanghai Bay.

Recent advances in the structure, synthesis, and applications of natural polymeric hydrogels - Khalid Gul; Ren-You Gan; Cui-Xia Sun; Ge Jiao; Ding-Tao Wu; Hua-Bin Li; Ahmad Kenaan; Harold Corke; Ya-Peng Fang (Critical Reviews in Food Science and Nutrition, 2022)

Identification of PDXDC1 as a novel pleiotropic susceptibility locus shared between lumbar spine bone mineral density and birth weight - Yu-Qian Song; Shi-Di Hu; Xu Lin; Xiang-He Meng; Xiao Wang; Yin-Hua Zhang; Cheng Peng; Rui Gong; Tao Xu; Tong Zhang; Chen-Zhong Li; Dao-Yan Pan; et al. (Journal of Molecular Medicine, 2022)
An increasing number of epidemiological studies have suggested that birth weight (BW) may be a determinant of bone health later in life, although the underlying genetic mechanism remains unclear. Here, we applied a pleiotropic conditional false discovery rate (cFDR) approach to the genome-wide association study (GWAS) summary statistics for lumbar spine bone mineral density (LS BMD) and BW, aiming to identify novel susceptibility variants shared between these two traits. We detected 5 novel potential pleiotropic loci which are located at or near 7 different genes ( NTAN1 , PDXDC1 , CACNA1G , JAG1 , FAT1P1 , CCDC170 , ESR1 ), among which PDXDC1 and FAT1P1 have not previously been linked to these phenotypes. To partially validate the findings, we demonstrated that the expression of PDXDC1 was dramatically reduced in ovariectomized (OVX) mice in comparison with sham-operated (SHAM) mice in both the growth plate and trabecula bone. Furthermore, immunohistochemistry assay with serial sections showed that both osteoclasts and osteoblasts express PDXDC1 , supporting its potential role in bone metabolism. In conclusion, our study provides insights into some shared genetic mechanisms for BMD and BW as well as a novel potential therapeutic target for the prevention of OP in the early stages of the disease development. Key messages We investigated pleiotropy-informed enrichment between LS BMD and BW. We identified genetic variants related to both LS BMD and BW by utilizing a cFDR approach. PDXDC1 is a novel pleiotropic gene which may be related to both LS BMD and BW. Elevated expression of PDXDC1 is related to higher BMD and lower ratio n-6/n-3 PUFA indicating a bone protective effect of PDXDC1.

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

A novel classification method for EEG-based motor imagery with narrow band spatial filters and deep convolutional neural network - Senwei Xu; Li Zhu; Wanzeng Kong; Yong Peng; Hua Hu; Jianting Cao (Cognitive Neurodynamics, 2022)

Sterols and triterpenoids from Ganoderma lucidum and their reversal activities of tumor multidrug resistance - Min Wu; Cui-e Shen; Qiao-fa Lin; Jin-yi Zhong; Yan-fei Zhou; Ben-chen Liu; Jian-hua Xu; Zhi-qiang Zhang; Peng Li (Natural Product Research, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Bone Marrow Mesenchymal Stem Cells Exert Protective Effects After Ischemic Stroke Through Upregulation of Glutathione - Xiao-Yan Lan; Zheng-Wu Sun; Gui-Lian Xu; Cheng-Yan Chu; Hua-Min Qin; Shen Li; Xin Geng; Peng Gao; Johannes Boltze; Shen Li (Stem Cell Reviews and Reports, 2022)

Cancer metabolism and tumor microenvironment: fostering each other? - Yiyuan Yuan; Huimin Li; Wang Pu; Leilei Chen; Dong Guo; Hongfei Jiang; Bo He; Siyuan Qin; Kui Wang; Na Li; Jingwei Feng; Jing Wen; et al. (Science China Life Sciences, 2022)

Responses and feedback of litter properties and soil mesofauna to herbaceous plants expansion into the alpine tundra on Changbai Mountain, China - Ying-jie Zhang; Ying-hua Jin; Jia-wei Xu; Hong-shi He; Yan Tao; Zhi-peng Yang; Jing Zhao; Yin-xia Diao; Chen-hui Sun; Mai-He Li (Journal of Mountain Science, 2022)

Integrative testing device for investigating the hydro-mechanical behavior of highly expansive clay - Yun-zhi Tan; Fan Peng; Hui Li; Hua-jun Ming; De-an Sun (Arabian Journal of Geosciences, 2022)

Myrothecol A, a new alkylresorcinol with cytotoxicity from Myrothecium sp. - Zhen-Hua Li; Hui-Yuan Yang; Wen-Ting Zhu; Dong-Dong Jing; Shi-Neng Li; Peng-Ke Yan (Natural Product Research, 2022)

Fine mapping and candidate gene analysis of qGSN5, a novel quantitative trait locus coordinating grain size and grain number in rice - Hua Yuan; Peng Gao; Xiaoling Hu; Min Yuan; Zhengyan Xu; Mengya Jin; Wencheng Song; Shijie Zhan; Xiaobo Zhu; Bin Tu; Ting Li; Yuping Wang; et al. (Theoretical and Applied Genetics, 2022)

Effect of feed restriction on the intestinal microbial community structure of growing ducks - Jun-peng Li; Qi-fan Wu; Sheng-chao Ma; Jian-mei Wang; Bin Wei; Yang Xi; Chun-chun Han; Liang Li; Hua He; He-he Liu (Archives of Microbiology, 2022)

The in vitro and in vivo anti-inflammatory activities of triterpene saponins from Clematis florida - Na-Na Yang; Yi-Fan Zhang; Hai-Tao Zhang; Xin-Hua Ma; Jin-Huang Shen; Peng Li; Tian-Hua Zhong; Yong-Hong Zhang (Natural Product Research, 2021)

The sesquiterpenes from the stem and leaf of Clausena lansium with their potential antibacterial activities - Xin-Yuan Liu; Xiao-Xiang Fu; Yu-Yan Li; Zhong-Hua Xiong; Bao-Tong Li; Wen-Wen Peng (Natural Product Research, 2021)

Standard litterbags underestimate early-stage lower-order root decomposition rate in a subtropical forest, China - Guan-tao Chen; Yu-qin Chen; Yong Peng; Hong-ling Hu; Jiu-long Xie; Gang Chen; Yin-long Xiao; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2021)

Comprehensive evaluation of 47 tea [Camellia sinensis (L.) O. Kuntze] germplasm based on entropy weight method and grey relational degree - Zhihui Wang; Puxiang Yang; Hua Peng; Chen Li; Cuinan Yue; Wenjin Li; Xinfeng Jiang (Genetic Resources and Crop Evolution, 2021)

Seasonal progression of photoprotection responses in different aged savin juniper plants under shade and sun - Jin-Ling Zhang; Xiao-Gang Li; Xue-Hua Xu; Hai-Peng Chen; Yu-Ling Li; Robert D. Guy (Trees, 2021)

N, P, and COD conveyed by urban runoff: a comparative research between a city and a town in the Taihu Basin, China - Li Zhao; Xiaodong Liu; Peng Wang; Zulin Hua; Yuan Zhang; Hongqin Xue (Environmental Science and Pollution Research, 2021)

Influence of elevation on bioregionalisation: A case study of the Sino‐Himalayan flora - Yun Liu; Jian‐Fei Ye; Hai‐Hua Hu; Dan‐Xiao Peng; Li‐Na Zhao; Li‐Min Lu; Wajid Zaman; Zhi‐Duan Chen (Journal of Biogeography, 2021)
Aim Elevation is an important factor that influences bioregionalisation in mountainous areas, but its effects are not well known. Taking the Sino‐Himalayan flora as a case, we aimed to test the effect of elevation on bioregionalisation and provide a regionalisation scheme of the Sino‐Himalayan flora. Location The Sino‐Himalaya (East Himalaya, the Hengduan Mountains and the Yunnan Plateau in China). Taxon Angiosperms. Methods We compiled distribution data and elevation ranges of angiosperms in the Sino‐Himalaya and adjacent areas and reconstructed a species‐level phylogenetic tree of 19,313 angiosperm species. The area was divided into 398 grid cells, each 1 × 1°. Nine datasets of different elevation ranges were then used to delineate the flora of the Sino‐Himalaya and adjacent areas using the phylogenetic dissimilarity approach. Results A comparison of nine regionalisation schemes of the Sino‐Himalayan flora based on different elevation range datasets revealed that more than half of grid cells were allocated to more than one subregion. Most of these grid cells were located in areas with a wide range of elevation and/or at the boundaries between subregions. After revising the subregion allocations of eight shifting grid cells, we generated a phylogeny‐ and elevation‐based regionalisation scheme of three regions, comprising eight subregions, for the Sino‐Himalayan flora. Main conclusions By integrating phylogenetic and elevational information, the Sino‐Himalaya can be divided into three floristic regions: the Yunnan Plateau region, the Hengduan Mountains region and the East Himalaya region. Our study provides novel insights into the regionalisation of the flora and highlights the importance of incorporating elevation data in the bioregionalisation of areas with a broad elevational range.

Exploring the dynamic mechanism of allosteric drug SHP099 inhibiting SHP2E69K - Shan Du; Xin-hua Lu; Wei-Ya Li; Li-Peng Li; Yang-Chun Ma; Liang Zhou; Jing-Wei Wu; Ying Ma; Run-Ling Wang (Molecular Diversity, 2021)

A new epimer of azaphilone derivative pinophilin B from the gorgonian-derived fungus Aspergillus fumigatus 14–27 - Ya-Hui Zhang; Xiao-Yue Peng; Li-Xi Feng; Hua-Jie Zhu; Fei Cao; Chang-Yun Wang (Natural Product Research, 2021)

Characterization of the pectin methylesterase inhibitor gene family in Rosaceae and role of PbrPMEI23/39/41 in methylesterified pectin distribution in pear pollen tube - Xiaoxuan Zhu; Chao Tang; Qionghou Li; Xin Qiao; Xian Li; Yilin Cai; Peng Wang; Yangyang Sun; Hua Zhang; Shaoling Zhang; Juyou Wu (Planta, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Differences in immunity between pathogen-resistant and -susceptible yam cultivars reveal insights into disease prevention underlying ethylene supplementation - Shumei Hua; Zhihua Chen; Lihong Li; Kuan-Hung Lin; Yangwen Zhang; Jieyu Yang; Shi-Peng Chen (Journal of Plant Biochemistry and Biotechnology, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Vertical diversity and association pattern of total, abundant and rare microbial communities in deep‐sea sediments - Yunhui Zhang; Peng Yao; Chuang Sun; Sanzhong Li; Xiaochong Shi; Xiao‐Hua Zhang; Jiwen Liu (Molecular Ecology, 2021)
Microbial abundance and community composition in marine sediments have been widely explored. However, high‐resolution vertical changes of benthic microbial diversity and co‐occurrence patterns are poorly described. The ecological contributions of abundant and rare species in sediments also remain largely unknown. Here, by analysing microbial populations at 14 depth layers of 10 subseafloor sediment cores (water depth 1,250–3,530 m) obtained in the South China Sea, we provided the vertical profiles of microbial β ‐diversity and co‐occurrence influenced by subcommunities of different abundance. These 134 sediment samples were clustered into four groups according to sediment depth (1–2, 6–10, 30–90 and 190–790 cm) with obvious shifts in microbial community compositions. The vertical succession of microorganisms was consistent with redox zonation and influenced by terrestrial inputs. Partitioning of vertical β ‐diversity showed extremely high species replacement between deep layers and the surface layer, indicating selection‐induced loss of rare species and dispersal of dormant cells and spores. By contrast, for horizontal β ‐diversity, richness of rare species became increasingly significant in deep sediments. Accompanying this β ‐diversity profile were clear changes in the association pattern, with microorganisms being less connected in deeper sediment layers, probably reflecting reduced syntrophic interactions. Rare species accounted for an indispensable proportion in the co‐occurrence network, and tended to form complex “small worlds.” The rare subcommunity also responded differently to various environmental factors compared with the abundant subcommunity. Our findings expand current knowledge on vertical changes of marine benthic microbial diversity and their association patterns, emphasizing the potential roles of rare species.

Electrochemical performance and response of bacterial community during phenanthrene degradation in single-chamber air-cathode microbial fuel cells - Tao Hua; Haonan Wang; Shengnan Li; Peng Chen; Fengxiang Li; Wei Wang (Environmental Science and Pollution Research, 2021)

ZnO nanorods/Fe3O4-graphene oxide/metal-organic framework nanocomposite: recyclable and robust photocatalyst for degradation of pharmaceutical pollutants - Li Chen; Jun Peng; Fangqi Wang; Donghao Liu; Wenrong Ma; Jinmeng Zhang; Wenqing Hu; Ning Li; Pierre Dramou; Hua He (Environmental Science and Pollution Research, 2021)

Change detection in SAR images based on superpixel segmentation and image regression - Rui Zhao; Guo-Hua Peng; Wei-dong Yan; Lu-Lu Pan; Li-Ya Wang (Earth Science Informatics, 2021)

Attenuation of Cardiomyocyte Hypertrophy via Depletion Myh7 using CASAAV - Peng Yue; Shutao Xia; Gang Wu; Lei Liu; Kaiyu Zhou; Hongyu Liao; Jiawen Li; Xiaolan Zheng; Yuxuan Guo; Yimin Hua; Donghui Zhang; Yifei Li (Cardiovascular Toxicology, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Copper metabolism in Saccharomyces cerevisiae: an update - Hua Shi; Yunhui Jiang; Yang Yang; Yougong Peng; Chenghua Li (BioMetals, 2021)

Description of Salinimonas profundi sp. nov., a deep-sea bacterium harboring a transposon Tn6333 - Dao-Feng Zhang; Xi-Wen Cui; Wen-Jun Li; Xiao-Mei Zhang; Hua-Peng Xue; Jian-Ke Huang; Ai-Hua Zhang (Antonie van Leeuwenhoek, 2021)

Association of in-hospital intensive statins dosage and death in arteriosclerotic cardiovascular disease with percutaneous coronary intervention: insights of multicentre cohort from China - Peng-yuan Chen; Yuan-hui Liu; Chong-yang Duan; Hua-lin Fan; Li-huan Zeng; Wei Guo; Lei Jiang; Xue-biao Wei; Wen-fei He; Sha Tao; Zhi-qiang Guo; Ji-yan Chen; et al. (European Journal of Clinical Pharmacology, 2020)

Investigating the abrupt change of tropical cyclone (TC) activity in the Western North Pacific by using different TC genesis indices - Li‐Peng Hsiao; Chih‐Hua Tsou; Jia‐Yuh Yu (International Journal of Climatology, 2020)
The tropical cyclone (TC) genesis indices are used to investigate the abrupt change of TC genesis frequency (TCGF) in the Western North Pacific (WNP) from 1979 to 2014 and to discuss the factors leading to the abrupt change. This study shows that TCGF had an abrupt decrease in 1997, but the popular TC genesis indices used in recent studies do not reflect this feature. An appropriate TC genesis index must consider both thermal and dynamic effects to reflect the TCGF abrupt change in the WNP. We modify the dynamic and thermal effects of the existing indices and propose a new TC genesis index, MoχGPI, which is consistent with the observational abrupt change of TC activity regardless of spatial distribution or time‐series patterns. A budget analysis of MoχGPI is conducted to discuss the individual contribution of large‐scale environmental parameters to the TCGF abrupt change. The results show that the change in relative vorticity (including contributions not only from the environmental relative vorticity, but also a part from the relative vorticity by TCs themself) is the dominant effect leading to the TCGF abrupt change in 1997, followed by the vertical wind shear effect.

A new demethyl abietane diterpenoid from the roots of Tripterygium wilfordii - Peng Li; Shao-Xin Shen; Ling-Xue Liu; Jian-Hua Xu; Xin-Hua Ma; Dong-Mei Shi; Zhi-Qiang Zhang (Natural Product Research, 2020)

The molecular mechanisms of copper metabolism and its roles in human diseases - Ji Chen; Yunhui Jiang; Hua Shi; Yougong Peng; Xueying Fan; Chenghua Li (Pflügers Archiv - European Journal of Physiology, 2020)

Comparative iTRAQ Proteomics Reveals Multiple Effects of Selenium Yeast on Dairy Cows in Parturition - Zhi-hua Ren; Li-peng Bai; Liu-hong Shen; Zheng-zhong Luo; Zi-han Zhou; Zhi-cai Zuo; Xiao-ping Ma; Jun-liang Deng; Ya Wang; Sheng-yu Xu; Yu-heng Luo; Sui-zhong Cao; et al. (Biological Trace Element Research, 2020)

Protein extraction and database construction in tea rhizosphere soil - Hai-bin Wang; Chun-lian Zhu; Yu-hua Wang; Qing-xu Zhang; Peng Wang; Ding Li; Xiao-li Jia; Jiang-hua Ye; Hai-bin He (Acta Physiologiae Plantarum, 2020)

Noise does not equal bias in assessing the evolutionary history of the angiosperm flora of China: A response to Qian (2019) - Li‐Min Lu; Hai‐Hua Hu; Dan‐Xiao Peng; Bing Liu; Jian‐Fei Ye; Tuo Yang; Hong‐Lei Li; Miao Sun; Stephen A. Smith; Pamela S. Soltis; Douglas E. Soltis; Zhi‐Duan Chen (Journal of Biogeography, 2020)
In response to our paper on the evolutionary history of the Chinese flora, Qian suggests that certain features of the divergence time estimation employed might have led to biased conclusions in Lu et al (2018). Here, we consider Qian's specific criticisms, explore the extent of uncertainty in the data and demonstrate that (i) no systematic bias toward dates that are too young or too old is detected in Lu et al.; (ii) constraint of the crown age of angiosperms does not bias the generic ages estimated by Lu et al.; and (iii) ages derived from the Chinese regional phylogeny do not bias the conclusions reported by Lu et al. All these analyses confirm that the conclusions reported previously are robust. We argue that, like many large‐scale biodiversity analyses, sources of noise in divergence time estimation are to be expected, but these should not be confused with bias.

Fumonisin B1 Affects the Biophysical Properties, Migration and Cytoskeletal Structure of Human Umbilical Vein Endothelial Cells - Xue Zhao; Yun Wang; Jiang-Li Liu; Jian-Hua Zhang; Shi-Chao Zhang; Yan Ouyang; Jiang-Tao Huang; Xiao-Yan Peng; Zhu Zeng; Zu-Quan Hu (Cell Biochemistry and Biophysics, 2020)

A bacterial polysaccharide biosynthesis-related gene inversely regulates larval settlement and metamorphosis of Mytilus coruscus - Li-Hua Peng; Xiao Liang; Rui-Heng Chang; Jia-Yi Mu; Hui-E Chen; Asami Yoshida; Kiyoshi Osatomi; Jin-Long Yang (Biofouling, 2020)

SCFAs induce autophagy in intestinal epithelial cells and relieve colitis by stabilizing HIF-1α - Chao Zhou; Liangzi Li; Teming Li; Lihua Sun; Jiuheng Yin; Haidi Guan; Liucan Wang; Hongbing Zhu; Peng Xu; Xin Fan; Baifa Sheng; Weidong Xiao; et al. (Journal of Molecular Medicine, 2020)

Interspecific difference in N:P stoichiometric homeostasis drives nutrient release and soil microbial community composition during decomposition - Hanxiong Song; Jingjing Huang; Leming Ge; Changhui Peng; Pengxiang Zhao; Xinyi Guo; Tong Li; Xiaojuan Shen; Qiuan Zhu; Weiguo Liu; Hua Wei; Meng Wang (Plant and Soil, 2020)

Contamination characteristics of heavy metals in particle size fractions from street dust from an industrial city, Central China - Ping Zhong; Jia-Quan Zhang; Da-Mao Xu; Qian Tian; Tian-Peng Hu; Xiang-Yi Gong; Chang-Lin Zhan; Shan Liu; Xin-Li Xing; Shi-Hua Qi (Air Quality, Atmosphere & Health, 2020)

A new diterpenoid alkaloid from Aconitum hemsleyanum - Zhi-Hui Luo; Yang Chen; Xin-Yi Sun; Hua Fan; Wei Li; Liang Deng; Tian-Peng Yin (Natural Product Research, 2020)

Multiple genetic factors affecting the pharmacokinetic and pharmacodynamic processes of tacrolimus in Chinese myasthenia gravis patients - Huan-Yu Meng; Xi Li; Wan-Lin Jin; Cheng-Kai Yan; Xiao-Hua Dong; Qiu Xu; Yu-Yao Peng; Zhi-Bin Li; Yi Li; Zhao-Hui Luo; Li-Qun Xu; Huan Yang (European Journal of Clinical Pharmacology, 2020)

Characteristics and dynamics of the Ganqiuchi rock avalanche triggered by a paleo-earthquake in the Northern Qinling Mountains - Ze-Hua Zhou; Yan Lyu; Sheng-rui Su; Shi-jie Liu; Hui Zhao; Peng Li; Yang Zhou (Journal of Mountain Science, 2020)

Epitranscriptomic technologies and analyses - Xiaoyu Li; Qiao-Xia Liang; Jin-Ran Lin; Jinying Peng; Jian-Hua Yang; Chengqi Yi; Yang Yu; Qiangfeng Cliff Zhang; Ke-Ren Zhou (Science China Life Sciences, 2020)

The BIG gene controls size of shoot apical meristems in Arabidopsis thaliana - Wen Jie Zhang; Li Ming Zhai; Hai Xia Yu; Jing Peng; Shan Shan Wang; Xian Sheng Zhang; Ying Hua Su; Li Ping Tang (Plant Cell Reports, 2020)

A structurally integrated water environmental modeling system based on dual object structure - Peng Wang; Chuanhai Wang; Zulin Hua; Yongping Wei; Tengfei Ma; Xia Shen; Xianmin Zeng; Xiaodong Liu; Li He; Hualei Tang (Environmental Science and Pollution Research, 2020)

Species richness and biodiversity significance of alpine micro-waterbody systems in Gaoligong Mountain, Northwest Yunnan, China - Shuo-Ran Liu; Davide Fornacca; Dao-De Yang; Lu Tan; Xian-Fu Li; Guo-Peng Ren; Jun Sun; Xiao-Yang He; Wen-Shu Yang; Qing-Hua Cai; Wen Xiao (Journal of Mountain Science, 2020)

Effects of Dietary Supplementation of Recombinant Plectasin on Growth Performance, Intestinal Health and Innate Immunity Response in Broilers - Jing Lin Ma; Li Hua Zhao; Dan Dan Sun; Jing Zhang; Yong Peng Guo; Zhi Qiang Zhang; Qiu Gang Ma; Cheng Ji; Li Hong Zhao (Probiotics and Antimicrobial Proteins, 2020)

Induction of 2n female gametes in rubber (Hevea brasiliensis) by high-temperature exposure during megasporogenesis as a basis for triploid breeding - Peng-Qiang Yao; Guo-Hua Li; Yan-Fen Qiu; Xiang-Yang Kang (Tree Genetics & Genomes, 2020)

Vertical variation in Vibrio community composition in Sansha Yongle Blue Hole and its ability to degrade macromolecules - Bei Li; Jiwen Liu; Shun Zhou; Liang Fu; Peng Yao; Lin Chen; Zuosheng Yang; Xiaolei Wang; Xiao-Hua Zhang (Marine Life Science & Technology, 2020)
With the advantages of wide distribution, fast growth, and broad metabolic spectrum to organic carbon compounds, Vibrio may play an important role in organic carbon cycling. However, the ecological roles of Vibrio in many marine environments have not been explored. Here, the world’s deepest ‘blue hole’, the Sansha Yongle Blue Hole (SYBH) in the South China Sea, which is a geographically semi-enclosed environment featuring unique chemical characters, was investigated. The abundance, diversity and carbon source utilization capability of Vibrio were studied by quantification and high-throughput sequencing of Vibrio specific 16S rRNA genes and cultivation methods. The abundance of Vibrio in water column of the SYBH ranged from 3.78 × 10 4 to 7.35 × 10 6 16S rRNA gene copies L −1 . Free-living Vibrio was more abundant than particle-associated Vibrio (~ 1.20 × 10 6 versus~ 2.68 × 10 5 gene copies L −1 ), indicating that Vibrio prefers a free-living life style. The Vibrio assemblages showed clear vertical stratification and could be divided into three groups: aerobic-transition, middle anaerobic and bottom anaerobic zones. Dissolved oxygen (DO), temperature, pH and salinity were the main environmental factors affecting the abundance and community composition. Cultivated Vibrio demonstrated a degrading capability to various macromolecular substrates, including starch, Tween 20/40/80, DNA, gelatin, alginate, casein, chitin, lecithin, κ-carrageenan, mannan, xylan and hyaluronic acid. This suggests that Vibrio could produce a variety of highly active extracellular enzymes. Our study provides new insights into the distribution pattern and possible role in carbon cycle of Vibrio in the unique environment of a ‘blue hole’.

Nocardia panacis sp. nov., a novel actinomycete with antiphytopathogen activity isolated from the rhizosphere of Panax notoginseng - Jia-Yun Hu; Lei Li; Guang Peng; Yi-Qing Li; Li-Hua Xu; Hui-Lin Guan; Li-Xing Zhao; Cui-Ping Miao (Antonie van Leeuwenhoek, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Water and heat availability are drivers of the aboveground plant carbon accumulation rate in alpine grasslands on the Tibetan Plateau - Jian Sun; Tian‐Cai Zhou; Miao Liu; You‐Chao Chen; Guo‐Hua Liu; Ming Xu; Pei‐Li Shi; Fei Peng; Atsushi Tsunekawa; Yu Liu; Xiao‐Dan Wang; Shi‐Kui Dong; et al. (Global Ecology and Biogeography, 2020)
Aim Climate change is expected to have important effects on plant phenology and carbon storage, with further shifts predicted in the future. Therefore, we proposed the community carbon accumulation rate (CAR) from the start of the growing season (SOS) to the peak of the growing season (POS) to fill the gap that the dynamic interactions between plant phenology and plant carbon research. Location Tibetan Plateau. Major taxa Alpine grassland plants. Time period 2015. Methods We conducted a transect survey across grasslands to measure community aboveground net primary production and carbon concentration. Additionally, phenology indicator data (SOS and POS) were extracted from the Global Inventory Modeling and Mapping Studies (GIMMS) normalized difference vegetation index version 3 database. Next, we used ‘ changepoint ’ analysis to detect the patterns of CARs, and performed linear regression and one‐way ANOVA to explore the variability of CARs in response to the environmental factors. Ultimately, the total effects of environmental factors on CARs were illustrated by a structural equation model. Results Our results indicated that three CAR patterns were detected, which are low‐CAR (0.15 g/m 2 /day), medium‐CAR (0.31 g/m 2 /day) and high‐CAR (0.84 g/m 2 /day) patterns. We found that the availabilities of water and heat mediated CARs by regulating soil nutrition variability, and that drought climate and insufficient soil resources co‐constrained the community CAR at long time‐scales. In contrast, high CAR could be explained by more water and heat availability via either direct or indirect effects on soil moisture and soil nutrients. Main conclusions Our findings highlight that water and heat availability are critical driving factors in ecological carbon accumulation processes undergoing climate change. Meanwhile, the vegetative phenology also has important effect on carbon accumulation. Consequently, we propose incorporating the dynamic interactions between plant phenology and plant carbon into the ecological carbon cycle model to improve our understanding of resource utilization and survival strategies of plants under environmental change.

Review of Chinese atmospheric science research over the past 70 years: Atmospheric physics and atmospheric environment - Tijian Wang; Taichang Gao; Hongsheng Zhang; Maofa Ge; Hengchi Lei; Peichang Zhang; Peng Zhang; Chunsong Lu; Chao Liu; Hua Zhang; Qiang Zhang; Hong Liao; et al. (Science China Earth Sciences, 2019)

CRISPR/Cas9 facilitates genomic editing for large-scale functional studies in pluripotent stem cell cultures - Xiao-Fei Li; Yong-Wei Zhou; Peng-Fei Cai; Wei-Cong Fu; Jin-Hua Wang; Jin-Yang Chen; Qi-Ning Yang (Human Genetics, 2019)

Rapid diversification of alpine bamboos associated with the uplift of the Hengduan Mountains - Xia‐Ying Ye; Peng‐Fei Ma; Guo‐Qian Yang; Cen Guo; Yu‐Xiao Zhang; Yun‐Mei Chen; Zhen‐Hua Guo; De‐Zhu Li (Journal of Biogeography, 2019)
Aim The Hengduan Mountains (HDM) of southwest China is a biodiversity hotspot and harbours one of the world's richest temperate floras. However, the origin and evolution of its biota remain largely unresolved. Here we explore the impact of mountain uplift on the diversification process of biodiversity in this hotspot using alpine bamboos. Location The HDM region, southwest China. Taxon Alpine bamboos. Methods We used ddRAD‐seq data from the most complete sampling of alpine bamboos undertaken to date (79% of the species diversity), to investigate their evolutionary history. The ancestral area of these bamboos was reconstructed using a time‐calibrated phylogeny in BioGeoBEARS and diversification rates were inferred using BAMM analyses. In addition, the impact of mountain uplift on the divergence of alpine bamboos was evaluated using trait‐dependent models of diversification. Results The alpine bamboos were strongly supported as monophyletic, and the relationships within them were robustly resolved. Fargesia was found to be polyphyletic and Yushania was resolved as monophyletic. Alpine bamboos originated outside the HDM region during the late Miocene, and spread to this region in the Pliocene, undergoing a significant acceleration in net diversification, which is temporally congruent with the orogeny. The speciation rate increased with altitude and a high diversification rate, estimated to be 0.75 species per million years, was detected for alpine bamboos distributed in high elevations. Main Conclusions Our study demonstrates that heterogeneous mountain habitats and geographical isolation of alpine bamboos, which have limited dispersal ability, are important drivers for their rapid diversification. This study also highlights the power of complementary analyses in revealing the link between species diversification and past geological changes.

Protective role of curcumin in cadmium-induced testicular injury in mice by attenuating oxidative stress via Nrf2/ARE pathway - Shu-Hua Yang; Jian-Bin He; Li-Hui Yu; Lin Li; Miao Long; Ming-Da Liu; Peng Li (Environmental Science and Pollution Research, 2019)

A novel method for sewage sludge composting using bamboo charcoal as a separating material - Yun-bei Li; Peng-fei Jin; Ting-ting Liu; Jing-hua Lv; Ji-shao Jiang (Environmental Science and Pollution Research, 2019)

Traveltime tomography and prestack depth migration for vertical seismic profiling of an angle-domain walkaway on a complex surface - Jian-Guo Li; Xiao-Jie Cui; Jian-Hua Huang; Xiao-Lu Zhang; Yan-Peng Li (Applied Geophysics, 2019)

Comparative Transcriptome Analysis Reveals Differentially Expressed Genes and Signaling Pathways Between Male and Female Red-Tail Catfish (Mystus wyckioides) - Jun-Jie Wu; Yu-Lin Zhou; Zhong-Wei Wang; Guang-Hua Li; Fang-Peng Jin; Li-Li Cui; Hai-Tao Gao; Xin-Ping Li; Li Zhou; Jian-Fang Gui (Marine Biotechnology, 2019)

Predicting the cytotoxicity of disinfection by-products to Chinese hamster ovary by using linear quantitative structure–activity relationship models - Li-Tang Qin; Xin Zhang; Yu-Han Chen; Ling-Yun Mo; Hong-Hu Zeng; Yan-Peng Liang; Hua Lin; Dun-Qiu Wang (Environmental Science and Pollution Research, 2019)

Effect of Fluoride on Small Intestine Morphology and Serum Cytokine Contents in Rats - Hong-wei Wang; Jing Liu; Wen-peng Zhao; Zi-hao Zhang; Si-qi Li; Si-han Li; Shi-quan Zhu; Bian-hua Zhou (Biological Trace Element Research, 2019)

Bile-ology: from bench to bedside - Li-hua Jin; Zhi-peng Fang; Min-jie Fan; Wen-dong Huang (Journal of Zhejiang University-SCIENCE B, 2019)

Analysis of genetic variation of porcine circovirus type 2 within pig populations in central China - Peng-Li Xu; Yu Zhao; Hui-Hua Zheng; Run-Bo Tian; Hao-Ying Han; Hong-Ying Chen; Lan-Lan Zheng (Archives of Virology, 2019)

Development of Upwelling during the Sedimentary Period of the Organic-Rich Shales in the Wufeng and Longmaxi Formations of the Upper Yangtze Region and Its Impact on Organic Matter Enrichment - Shao-Ze Zhao; Yong Li; Hua-Jun Min; Tong Wang; Zhou Nie; Zhan-Zhao Zhao; Jia-Zhen Qi; Jin-Cheng Wang; Jia-Peng Wu (Journal of Marine Science and Engineering, 2019)
This study uses logging data, mineral component content, total organic carbon (TOC) content, and microscopic characteristics of the organic-rich shales in the Wufeng and Longmaxi Formations, as well as data reported by other researchers, to demonstrate that upwelling has played an important role in the organic matter enrichment. The results show that (1) the organic-rich shales of Well N211 in the Upper Yangtze region are located in the Wufeng Formation and the lower Longmaxi Formation, with a burial depth between 2308–2357 m. (2) The organic-rich shales are enriched in biogenic silica. (3) Based on paleogeographic location and characteristics of organisms, this study determines that upwelling occurred during the deposition of the organic-rich shales in the Wufeng and Longmaxi Formations, promoting the enrichment of organic matter in the shales. (4) The upwelling intensity gradually increased from the sedimentary period of the organic-rich shales in the mid-lower Wufeng Formation to the sedimentary period of the Guanyinqiao Member, and then decreased gradually from the sedimentary period of the Guanyinqiao Member to the sedimentary period of the organic-rich shales in the Longmaxi Formation, and leads to the different enrichment of organic matter in the vertical direction. The different developments of upwelling led to the coexistence of both high and low TOC contents in the Guanyinqiao Member along the vertical direction.

Field-evolved resistance and cross-resistance of the two-spotted spider mite, Tetranychus urticae, to bifenazate, cyenopyrafen and SYP-9625 - Jin-Cui Chen; Ya-Jun Gong; Pan Shi; Ze-Hua Wang; Li-Jun Cao; Peng Wang; Shu-Jun Wei (Experimental and Applied Acarology, 2019)

An H-ferritin from the hydrothermal vent shrimp Rimicaris exoculata and its potential role in iron metabolism - Xiao-Li Liu; Sen Ye; Hua-Wei Li; Bo Lu; Yan-Qin Yu; Yu-Peng Fan; Wei-Jun Yang; Jin-Shu Yang (BioMetals, 2019)

Ethyl lucidenates A reverses P-glycoprotein mediated vincristine resistance in K562/A02 cells - Peng Li; Shi-yu Chen; Shao-xin Shen; Ling-xue Liu; Jian-hua Xu; Zhi-qiang Zhang (Natural Product Research, 2019)

Evaluation of injury caused by lace bug, Cochlochila bullita (Stål) (Hemiptera: Tingidae) on Cat’s whiskers, Orthosiphon aristatus (Blume) Miq. and Sweet basil, Ocimum basilicum Linnaeus - Tan Li Peng; Ahmad Said Sajap; Seng Hua Lee; Hui Sin Koh (International Journal of Tropical Insect Science, 2019)

Neuregulin-1β attenuates sepsis-induced diaphragm atrophy by activating the PI3K/Akt signaling pathway - Jin Wu; Hua Liu; Ting Chu; Peng Jiang; Shi-tong Li (Journal of Muscle Research and Cell Motility, 2019)

Adsorption characteristics of Cu(II) and Zn(II) by nano-alumina material synthesized by the sol-gel method in batch mode - Ren-yu Wang; Wei Zhang; Li-ying Zhang; Tian Hua; Gang Tang; Xiao-qian Peng; Ming-hui Hao; Qi-ting Zuo (Environmental Science and Pollution Research, 2019)

Retraction Note to: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Contourlet-based hippocampal magnetic resonance imaging texture features for multivariant classification and prediction of Alzheimer’s disease - Ni Gao; Li-Xin Tao; Jian Huang; Feng Zhang; Xia Li; Finbarr O’Sullivan; Si-Peng Chen; Si-Jia Tian; Gehendra Mahara; Yan-Xia Luo; Qi Gao; Xiang-Tong Liu; et al. (Metabolic Brain Disease, 2018)

Altered intrinsic brain activity and memory performance improvement in patients with end-stage renal disease during a single dialysis session - Peng Li; Dun Ding; Xue-ying Ma; Hua-wen Zhang; Ji-xin Liu; Ming Zhang (Brain Imaging and Behavior, 2018)

Positive PCNA and Ki-67 Expression in the Testis Correlates with Spermatogenesis Dysfunction in Fluoride-Treated Rats - Wen-peng Zhao; Hong-wei Wang; Jing Liu; Pan-pan Tan; Xiang-long Luo; Shi-quan Zhu; Xue-li Chen; Bian-hua Zhou (Biological Trace Element Research, 2018)

Acute effect of fine and coarse particular matter on cardiovascular visits in Ningbo, China - Pei-wen Zheng; Peng Shen; Zhen-hua Ye; Zhen-yu Zhang; Peng-fei Chai; Die Li; Ming-juan Jin; Meng-Ling Tang; Huai-chu Lu; Hong-bo Lin; Jian-bing Wang; Kun Chen (Environmental Science and Pollution Research, 2018)

Boron Affects the Development of the Kidney Through Modulation of Apoptosis, Antioxidant Capacity, and Nrf2 Pathway in the African Ostrich Chicks - Haseeb Khaliq; Wang Jing; Xiao Ke; Yang Ke-Li; Sun Peng-peng; Lei Cui; Qiu Wei-wei; Lei Zhixin; Liu Hua-Zhen; Song Hui; Zhong Ju-Ming; Peng Ke-Mei (Biological Trace Element Research, 2018)

Triterpenoid saponins from the buds of Lonicera similis - Xiao Zhang; Li-Hua Zou; Yu-Lin He; Cheng Peng; Li Guo; Liang Xiong (Natural Product Research, 2018)

Nitrogen additions reduce rhizospheric and heterotrophic respiration in a subtropical evergreen broad-leaved forest - Yong Peng; Guan-tao Chen; Shun Li; Hong-ling Hu; Ting-xing Hu; Li Liu; Yi Tang; Li-hua Tu (Plant and Soil, 2018)

CYP46A1 and the APOEε4 Allele Polymorphisms Correlate with the Risk of Alzheimer’s Disease - Ling Li; Fan Zeng; Yu-Hui Liu; Hui-Yun Li; Shu-Yang Dong; Ze-Yan Peng; Yan-Jiang Wang; Hua-Dong Zhou (Molecular Neurobiology, 2018)

Association between abnormal thalamic metabolites and sleep disturbance in patients with end-stage renal disease - Xueying Ma; Yan Zhang; Shaohui Ma; Peng Li; Dun Ding; Hua Liu; Jixin Liu; Ming Zhang (Metabolic Brain Disease, 2018)

Preference and performance of the two-spotted spider mite Tetranychus urticae (Acari: Tetranychidae) on strawberry cultivars - Ya-Jun Gong; Jin-Cui Chen; Liang Zhu; Li-Jun Cao; Gui-Hua Jin; Ary A. Hoffmann; Chuan-Fei Zhong; Peng Wang; George Lin; Shu-Jun Wei (Experimental and Applied Acarology, 2018)

Dependence of 3‐month Standardized Precipitation‐Evapotranspiration Index dryness/wetness sensitivity on climatological precipitation over southwest China - Shanlei Sun; Haishan Chen; Jinjian Li; Jiangfeng Wei; Guojie Wang; Ge Sun; Wenjian Hua; Shujia Zhou; Peng Deng (International Journal of Climatology, 2018)
In this study, we estimated the respective contributions of precipitation and reference evapotranspiration (ET 0 ) to annual SPEI‐3 (3‐month Standardized Precipitation‐Evapotranspiration Index) anomalies over southwest China (SWC) using numerical experiments. Results show that the dominant factor (i.e., precipitation or ET 0 ) for the dryness/wetness anomalies during 1961–2012 existed due to inter‐annual and inter‐decadal changes over SWC, which indicates the underlying mechanisms of dry/wet conditions have changed. On the other hand, we calculate the dryness/wetness sensitivity to precipitation or ET 0 (defined as changes in SPEI‐3 per millimetre) and find that the dryness/wetness sensitivity to ET 0 is higher than that to precipitation for the whole SWC and the overwhelming majority (99%) of the 269 sites. Overall, the above findings imply that the role of ET 0 in the dry/wet condition evolution is vital and should be paid more attentions. For the magnitude of the dryness/wetness sensitivity to precipitation or ET 0 , an evident increase from the southeast to northwest SWC is identified. Based on the analyses of the relationship between dryness/wetness sensitivity and climatological condition (i.e., precipitation, ET 0 , and aridity), the sensitivity magnitude is dependent on climatological precipitation and generally decreases with its increase. This study provides a wealth of quantitative information (e.g., dryness/wetness anomalies [sensitivity] caused by [to] precipitation and ET 0 ) for better understanding the underlying mechanisms of the dry/wet condition evolution.

The effects of codon usage on the formation of secondary structures of nucleocapsid protein of peste des petits ruminants virus - Xiao-xia Ma; Yi-ning Wang; Xiao-an Cao; Xue-rui Li; Yong-sheng Liu; Jian-hua Zhou; Xue-peng Cai (Genes & Genomics, 2018)

Effects of Wolbachia infection on the postmating response in Drosophila melanogaster - Zhen He; Hua-Bao Zhang; Shi-Tian Li; Wen-Juan Yu; John Biwot; Xiao-Qiang Yu; Yu Peng; Yu-Feng Wang (Behavioral Ecology and Sociobiology, 2018)

Identification of Neoscytalidium dimidiatum causing canker disease of pitaya in Hainan, China - Min Xu; Yun Peng; Zhao Qi; Zhen Yan; Lu Yang; Meng-Die He; Qing-Xiu Li; Cheng-Li Liu; Yun-Ze Ruan; Shuang-Shuang Wei; Jun Xie; You-Quan Xia; et al. (Australasian Plant Pathology, 2018)

Autophagy‐related gene BbATG11 is indispensable for pexophagy and mitophagy, and contributes to stress response, conidiation and virulence in the insect mycopathogen Beauveria bassiana - Jin‐Li Ding; Yue‐Jin Peng; Xin‐Ling Chu; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2018)
Summary Autophagy is a conserved degradation system in eukaryotic cells that includes non‐selective and selective processes. Selective autophagy functions as a selective degradation mechanism for specific substrates in which autophagy‐related protein 11 (ATG11) acts as an essential scaffold protein. In B. bassiana , there is a unique ATG11 family protein, which is designated as BbATG11 . Disruption of BbATG11 resulted in significantly reduced conidial germination under starvation stress. The mutant Δ BbATG11 displayed enhanced sensitivity to oxidative stress and impaired asexual reproduction. The conidial yield was reduced by approximately 75%, and this defective phenotype could be repressed by increasing exogenous nutrients. The virulence of the Δ BbATG11 mutant strain was significantly impaired as indicated in topical and intra‐hemocoel injection bioassays, with a greater reduction in topical infection. Notably, BbATG11 was involved in pexophagy and mitophagy, but these two autophagic processes appeared in different fungal physiological aspects. Both pexophagy and mitophagy were associated with nutrient shift, starvation stress and growth in the host hemocoel, but only pexophagy appeared in both oxidation‐stressed cells and aerial mycelia. This study highlights that BbATG11 mediates pexophagy and mitophagy in B. bassiana and links selective autophagy to the fungal stress response, conidiation and virulence.

RETRACTED ARTICLE: An assessment of transgenomics as a tool for gene discovery in Populus euphratica Oliv. - Jing Zhou; Xin Liu; Shu-Tang Zhao; Jian-Jun Hu; Jie-Wei Zhang; Jie-Hua Wang; Xiao-Peng Peng; Xiao-Li Qi; Tie-Long Cheng; Meng-Zhu Lu (Plant Molecular Biology, 2018)

Response of the wheat rhizosphere soil nematode community in wheat/walnut intercropping system in Xinjiang, Northwest China - Peng-hua Bai; Qi-Zhi Liu; Xing-yue Li; Yan-bin Liu; Lin-lin Zhang (Applied Entomology and Zoology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Genome-wide analysis and expression profiling of the HMA gene family in Brassica napus under cd stress - Nannan Li; Hua Xiao; Juanjuan Sun; Shufeng Wang; Jingchao Wang; Peng Chang; Xinbin Zhou; Bo Lei; Kun Lu; Feng Luo; Xiaojun Shi; Jiana Li (Plant and Soil, 2018)

Glyphosate application increased catabolic activity of gram-negative bacteria but impaired soil fungal community - Yehao Liu; Yongchun Li; Xiaomei Hua; Karin Müller; Hailong Wang; Tongyi Yang; Qiong Wang; Xin Peng; Mengcheng Wang; Yanjun Pang; Jinliang Qi; Yonghua Yang (Environmental Science and Pollution Research, 2018)

Cell shape can be uncoupled from formononetin induction in a novel cell line from Callerya speciosa - Fei Qiao; Xue-fei Jiang; Han-qing Cong; Hua-peng Sun; Li Li; Peter Nick (Plant Cell Reports, 2018)

Effects of Boron Supplementation on Expression of Hsp70 in the Spleen of African Ostrich - Khaliq Haseeb; Jing Wang; Ke Xiao; Ke-li Yang; Peng-peng Sun; Xing-tong Wu; You Luo; Hui Song; Hua-zhen Liu; Ju-ming Zhong; Ke-mei Peng (Biological Trace Element Research, 2018)

Development and validation of SSR markers based on transcriptome sequencing of Casuarina equisetifolia - Nan Li; Yong-Qi Zheng; Hong-Mei Ding; He-Peng Li; Hua-Zheng Peng; Bo Jiang; Hai-Bo Li (Trees, 2018)

Short hairpin RNA interference targeting interleukin 1 receptor type I in the paraventricular nucleus attenuates hypertension in rats - Peng Lu; Shu-jun Jiang; Hong Pan; Ai-li Xu; Gui-hua Wang; Chun-lei Ma; Zhen Shi (Pflügers Archiv - European Journal of Physiology, 2018)

Minimally Toxic Dose of Lipopolysaccharide and α-Synuclein Oligomer Elicit Synergistic Dopaminergic Neurodegeneration: Role and Mechanism of Microglial NOX2 Activation - Wei Zhang; Jun-hua Gao; Zhao-fen Yan; Xi-yan Huang; Peng Guo; Li Sun; Zhuo Liu; Yang Hu; Li-jun Zuo; Shu-yang Yu; Chen-Jie Cao; Xiao-min Wang; et al. (Molecular Neurobiology, 2018)

Mevastatin promotes neuronal survival against Aβ-induced neurotoxicity through AMPK activation - Edy Kornelius; Hsin-Hua Li; Chiung-Huei Peng; Hui-Wen Hsiao; Yi-Sun Yang; Chien-Ning Huang; Chih-Li Lin (Metabolic Brain Disease, 2017)

Effects of vermicompost amendment as a basal fertilizer on soil properties and cucumber yield and quality under continuous cropping conditions in a greenhouse - Hai-Tao Zhao; Tian-Peng Li; Yang Zhang; Jian Hu; Yan-Chao Bai; Yu-Hua Shan; Feng Ke (Journal of Soils and Sediments, 2017)

Protective effect of proanthocyanidin on mice Sertoli cell apoptosis induced by zearalenone via the Nrf2/ARE signalling pathway - Miao Long; Shu-Hua Yang; Wei Shi; Peng Li; Yang Guo; Jiayi Guo; Jian-Bin He; Yi Zhang (Environmental Science and Pollution Research, 2017)

Improved application of tribenuron-methyl as a chemical hybridizing agent with forchlorfenuron for rapeseed hybrid breeding - Yong-Hong Li; Dian-Rong Li; Wu-Sheng Liang; Jian-Hua Tian; Jian-Chang Li; Hao Wang; Mao-Teng Li; Xu-Peng Guo; Wen-Jie Chen; Zhen-Lan Zhang; Fei Mao; Wei-Guo Zhao (Euphytica, 2017)

Neuronal nitric oxide synthase modulation of intracellular Ca2+ handling overrides fatty acid potentiation of cardiac inotropy in hypertensive rats - Chun Li Jin; Ming Zhe Yin; Jin Chul Paeng; Seunggyun Ha; Jeong Hoon Lee; Peng Jin; Chun Zi Jin; Zai Hao Zhao; Yue Wang; Keon Wook Kang; Chae Hun Leem; Jong-Wan Park; et al. (Pflügers Archiv - European Journal of Physiology, 2017)

A method for alpine wetland delineation and features of border: Zoigê Plateau, China - Yaomin Zheng; Zhenguo Niu; Peng Gong; Mengna Li; Lile Hu; Lei Wang; Yuxiang Yang; Haijun Gu; Jinrong Mu; Gejia Dou; Hui Xue; Lin Wang; et al. (Chinese Geographical Science, 2017)

Transcriptomic insights into the alternative splicing‐mediated adaptation of the entomopathogenic fungus Beauveria bassiana to host niches: autophagy‐related gene 8 as an example - Wei‐Xia Dong; Jin‐Li Ding; Yang Gao; Yue‐Jin Peng; Ming‐Guang Feng; Sheng‐Hua Ying (Environmental Microbiology, 2017)
Summary Alternative splicing (AS) regulates various biological processes in fungi by extending the cellular proteome. However, comprehensive studies investigating AS in entomopathogenic fungi are lacking. Based on transcriptome data obtained via dual RNA‐seq, the first overview of AS events was developed for Beauveria bassiana growing in an insect haemocoel. The AS was demonstrated for 556 of 8840 expressed genes, accounting for 5.4% of the total genes in B. bassiana . Intron retention was the most abundant type of AS, accounting for 87.1% of all splicing events and exon skipping events were rare, only accounting for 2.0% of all events. Functional distribution analysis indicated an association between alternatively spliced genes and several physiological processes. Notably, B. bassiana autophagy‐related gene 8 ( BbATG8 ), an indispensable gene for autophagy, was spliced at an alternative 5′ splice site to generate two transcripts ( BbATG8‐α and BbATG8‐β ). The BbATG8‐α transcript was necessary for fungal autophagy and oxidation tolerance, while the BbATG8‐β transcript was not. These two transcripts differentially contributed to the formation of conidia or blastospores as well as fungal virulence. Thus, AS acts as a powerful post‐transcriptional regulatory strategy in insect mycopathogens and significantly mediates fungal transcriptional adaption to host niches.

Neuroglobin Protects Rats from Sepsis-Associated Encephalopathy via a PI3K/Akt/Bax-Dependent Mechanism - Songyun Deng; Yuhang Ai; Hua Gong; Caixia Chen; Qianyi Peng; Li Huang; Long Wu; Lemeng Zhang; Lina Zhang (Journal of Molecular Neuroscience, 2017)

Modelling the response of shallow groundwater levels to combined climate and water-diversion scenarios in Beijing-Tianjin-Hebei Plain, China - Xue Li; Si-Yuan Ye; Ai-Hua Wei; Peng-Peng Zhou; Li-Heng Wang (Hydrogeology Journal, 2017)

Determination of dissolved nitric oxide in coastal waters of the Yellow Sea off Qingdao - Chun-Ying Liu; Wei-Hua Feng; Ye Tian; Gui-Peng Yang; Pei-Feng Li; Hermann W. Bange (Ocean Science, 2017)
We developed a new method for the determination of dissolved nitric oxide (NO) in discrete seawater samples based on the combination of a purge-and-trap setup and a fluorometric detection of NO. 2,3-diaminonaphthalene (DAN) reacts with NO in seawater to form the highly fluorescent 2,3-naphthotriazole (NAT). The fluorescence intensity was linear for NO concentrations in the range from 0.14 to 19 nmol L−1. We determined a detection limit of 0.068 nmol L−1, an average recovery coefficient of 83.8 % (80.2–90.0 %), and a relative standard deviation of ±7.2 %. With our method we determined for the first time the temporal and spatial distributions of NO surface concentrations in coastal waters of the Yellow Sea off Qingdao and in Jiaozhou Bay during a cruise in November 2009. The concentrations of NO varied from below the detection limit to 0.50 nmol L−1 with an average of 0.26 ± 0.14 nmol L−1. NO surface concentrations were generally enhanced significantly during daytime, implying that NO formation processes such as NO2− photolysis are much higher during daytime than chemical NO consumption, which, in turn, lead to a significant decrease in NO concentrations during nighttime. In general, NO surface concentrations and measured NO production rates were higher compared to previously reported measurements. This might be caused by the high NO2− surface concentrations encountered during the cruise. Moreover, additional measurements of NO production rates implied that the occurrence of particles and a temperature increase can enhance NO production rates. With the method introduced here, we have a reliable and comparably easy to use method at hand to measure oceanic NO surface concentrations, which can be used to decipher both its temporal and spatial distributions as well as its biogeochemical pathways in the oceans.

Geochemistry and geochronology of the mafic dikes in the Taipusi area, northern margin of North China Craton: Implications for Silurian tectonic evolution of the Central Asian Orogen - Jing-Hua Wu; Huan Li; Xiao-Shuang Xi; Hua Kong; Qian-Hong Wu; Neng-Li Peng; Xi-Ming Wu; Jing-Ya Cao; Jillian Aira S Gabo-Ratio (Journal of Earth System Science, 2017)

Endogenously generated amyloid-β increases stiffness in human neuroblastoma cells - Zhuoyang Lu; Hua Li; Chen Hou; Yunhua Peng; Jiangang Long; Jiankang Liu (European Biophysics Journal, 2017)

A Point Mutation in SCN1A 5′ Genomic Region Decreases the Promoter Activity and Is Associated with Mild Epilepsy and Seizure Aggravation Induced by Antiepileptic Drug - Qu-Wen Gao; Li-Dong Hua; Jie Wang; Cui-Xia Fan; Wei-Yi Deng; Bin Li; Wen-Jun Bian; Chuan-Xing Shao; Na He; Peng Zhou; Wei-Ping Liao; Yi-Wu Shi (Molecular Neurobiology, 2017)

Elevated Serum and Cerebrospinal Fluid Free Fatty Acid Levels Are Associated with Unfavorable Functional Outcome in Subjects with Acute Ischemic Stroke - Xiao-Xia Duan; Guan-Peng Zhang; Xiao-Bin Wang; Hua Yu; Jia-Li Wu; Ke-Zhi Liu; Lin Wang; Xiang Long (Molecular Neurobiology, 2017)

Effect of nitrogen additions on root morphology and chemistry in a subtropical bamboo forest - Guan-tao Chen; Li-hua Tu; Yong Peng; Hong-ling Hu; Ting-xing Hu; Zhen-feng Xu; Li Liu; Yi Tang (Plant and Soil, 2017)

Phosphate and ammonium adsorption of the modified biochar based on Phragmites australis after phytoremediation - Yu-Peng Gong; Zhi-Yi Ni; Zhao-Zhao Xiong; Li-Hua Cheng; Xin-Hua Xu (Environmental Science and Pollution Research, 2017)

The formation of porphyry copper deposits - Weidong Sun; Jin-tuan Wang; Li-peng Zhang; Chan-chan Zhang; He Li; Ming-xing Ling; Xing Ding; Cong-ying Li; Hua-ying Liang (Acta Geochimica, 2017)

Transcriptomic analysis of Casuarina equisetifolia L. in responses to cold stress - Hai-Bo Li; Nan Li; Shao-Zong Yang; Hua-Zheng Peng; Li-Ling Wang; Yong Wang; Xiao-Mian Zhang; Zhi-Hui Gao (Tree Genetics & Genomes, 2017)

Mice lacking myotubularin-related protein 14 show accelerated high-fat diet-induced lipid accumulation and inflammation - Lv Yin; Peng Yong-bo; Yu Meng-Fei; Chen Weiwei; Zhao Ping; Xue Lu; Ma Li-Qun; Cai Congli; Liu Qing-hua; Shen Jinhua (Journal of Physiology and Biochemistry, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Three-Dimensional Reconstruction and Visualization of Human Enamel Ex Vivo Using High-Frequency Ultrasound - Juan Du; Xue-Li Mao; Peng-Fei Ye; Qing-Hua Huang (Journal of Medical and Biological Engineering, 2017)

Assessment the Exposure Level of Rare Earth Elements in Workers Producing Cerium, Lanthanum Oxide Ultrafine and Nanoparticles - Yan Li; Hua Yu; Peng Li; Ying Bian (Biological Trace Element Research, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Serum uric acid levels in patients with infections of central nervous system - Jia Liu; Min Li; Xuan Wang; Huan Yi; Li Xu; Xiu-feng Zhong; Fu-hua Peng (Acta Neurologica Belgica, 2016)

Influence of Washing and Cold Storage on Lipid and Protein Oxidation in Catfish ( Clarias lazera ) Surimi - Peng Li; Hua Yang; Yingchun Zhu; Yang Wang; Dongqing Bai; Ruitong Dai; Xiaoqing Ren; Hongshun Yang; Lizhen Ma (Journal of Aquatic Food Product Technology, 2016)

Signaling Mechanism of Cannabinoid Receptor-2 Activation-Induced β-Endorphin Release - Fang Gao; Ling-Hong Zhang; Tang-Feng Su; Lin Li; Rui Zhou; Miao Peng; Cai-Hua Wu; Xiao-Cui Yuan; Ning Sun; Xian-Fang Meng; Bo Tian; Jing Shi; et al. (Molecular Neurobiology, 2016)

Identification and characterization of differentially expressed miRNAs between bamboo shoot and rhizome shoot - Qun-Ying Jin; Hua-Zheng Peng; Er-Pei Lin; Nan Li; Dan-Ni Huang; Yan-Li Xu; Xi-Qi Hua; Kui-Hong Wang; Tang-Jun Zhu (Journal of Plant Biology, 2016)

Advances on Bioactive Polysaccharides from Medicinal Plants - Jian-Hua Xie; Ming-Liang Jin; Gordon A. Morris; Xue-Qiang Zha; Han-Qing Chen; Yang Yi; Jing-En Li; Zhi-Jun Wang; Jie Gao; Shao-Ping Nie; Peng Shang; Ming-Yong Xie (Critical Reviews in Food Science and Nutrition, 2016)

Seroprevalence and risk factors of severe fever with thrombocytopenia syndrome virus infection in endemic areas - Yong Lyu; Fan Ding; Jie Sun; Peng-Peng Xu; Jie-Ying Hu; Shao-Yu Xie; Kai-Chun Li; Hong-Wei Chang; Wei Qin; Liang Yu; Hua Xie; Guang-Jiang Li; et al. (Infectious Diseases, 2016)

Can the Tibetan Plateau snow cover influence the interannual variations of Eurasian heat wave frequency? - Zhiwei Wu; Peng Zhang; Hua Chen; Yun Li (Climate Dynamics, 2016)

Seismic dynamic monitoring in CO2 flooding based on characterization of frequency-dependent velocity factor - Jun-Hua Zhang; Jun Li; Wen Xiao; Ming-You Tan; Yun-Ying Zhang; Shi-Ling Cui; Zhi-Peng Qu (Applied Geophysics, 2016)

SMAD7, an antagonist of TGF-beta signaling, is a candidate of prenatal skeletal muscle development and weaning weight in pigs - Chaoju Hua; Zishuai Wang; Jianbing Zhang; Xing Peng; Xinhua Hou; Yalan Yang; Kui Li; Zhonglin Tang (Molecular Biology Reports, 2016)

MicroRNA-25 Negatively Regulates Cerebral Ischemia/Reperfusion Injury-Induced Cell Apoptosis Through Fas/FasL Pathway - Jun-feng Zhang; Li-li Shi; Li Zhang; Zhao-hua Zhao; Fei Liang; Xi Xu; Ling-yu Zhao; Peng-bo Yang; Jian-shui Zhang; Ying-fang Tian (Journal of Molecular Neuroscience, 2016)

Oral administration of Anabaena-expressed VP28 for both drug and food against white spot syndrome virus in shrimp - Xiao-Hui Jia; Chun-Li Zhang; Ding-Ji Shi; Min-Min Zhuang; Xiang Wang; Rui Jia; Zheng-Yang Zhang; Jie Huang; Yi-Hua Sun; Wen-Yi Qian; Guo-Hong Peng; Pei-Min He (Journal of Applied Phycology, 2016)

Hydrochemical characteristics and quality assessment of deep groundwater from the coal-bearing aquifer of the Linhuan coal-mining district, Northern Anhui Province, China - Man-li Lin; Wei-hua Peng; He-rong Gui (Environmental Monitoring and Assessment, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Fluorescence quenching effects of antibiotics on the main components of dissolved organic matter - Peng-Fei Yan; Zhen-Hu Hu; Han-Qing Yu; Wei-Hua Li; Li Liu (Environmental Science and Pollution Research, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Clinical, biochemical, neuroimaging and molecular findings of X-linked Adrenoleukodystrophy patients in South China - Min-yan Jiang; Yan-na Cai; Cui-li Liang; Min-zhi Peng; Hui-ying Sheng; Li-ping Fan; Rui-zhu Lin; Hua Jiang; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2015)

The effects of phylogenetic relatedness on invasion success and impact: deconstructing Darwin's naturalisation conundrum - Shao‐peng Li; Marc W. Cadotte; Scott J. Meiners; Zheng‐shuang Hua; Hao‐yue Shu; Jin‐tian Li; Wen‐sheng Shu (Ecology Letters, 2015)
Darwin's naturalisation conundrum describes the paradox that the relatedness of exotic species to native residents could either promote or hinder their success through opposing mechanisms: niche pre‐adaptation or competitive interactions. Previous studies focusing on single snapshots of invasion patterns have provided support to both sides of the conundrum. Here, by examining invasion dynamics of 480 plots over 40 years, we show that exotic species more closely related to native species were more likely to enter, establish and dominate the resident communities, and that native residents more closely related to these successful exotics were more likely to go locally extinct. Therefore, non‐random displacement of natives during invasion could weaken or even reverse the negative effects of exotic–native phylogenetic distances on invasion success. The scenario that exotics more closely related to native residents are more successful, but tend to eliminate their closely related natives, may help to reconcile the 150‐year‐old conundrum.

Genome-wide identification of allele-specific expression in response to Streptococcus suis 2 infection in two differentially susceptible pig breeds - Huayu Wu; Uma Gaur; Supamit Mekchay; Xianwen Peng; Lianghua Li; Hua Sun; Zhongxu Song; Binke Dong; Mingbo Li; Klaus Wimmers; Siriluck Ponsuksili; Kui Li; et al. (Journal of Applied Genetics, 2015)

Associations of hypoxia inducible factor-1α gene polymorphisms with susceptibility to digestive tract cancers: a case–control study and meta-analysis - Zhi-Hai Ni; Xian-Jun Liang; Jing-Gang Mo; Yi Zhang; Jian-Hua Liang; Yu-Sha Yang; Yong Zhou; Zhao-Hua Li; Jian-Liang Zhang; Yin-Lu Ding; Peng Zhang; Jin-Qing Wang (Genes & Genomics, 2015)

A two‐domain protein triggers heat shock pathway and necrosis pathway both in model plant and nematode - Lifang Ruan; Huihui Wang; Ge Cai; Donghai Peng; Hua Zhou; Jinshui Zheng; Lei Zhu; Xixi Wang; Haoquan Yu; Seng Li; Ce Geng; Ming Sun (Environmental Microbiology, 2015)
Summary The entomopathogen B acillus thuringiensis is equipped with multiple virulent factors. The genome sequence of B . thuringiensis YBT 1520 revealed the presence of a two‐domain protein named Nel which is composed of a necrosis‐inducing phytophthora protein 1‐like domain found in phytopathogens and a ricin B ‐like lectin domain. The merging of two distantly related domains is relatively rare. Nel induced necrosis and pathogen‐triggered immunity ( PTI ) on model plants. The Nel also exhibited inhibition activity to nematode. Microscopic observation showed that the toxicity of Nel to nematodes targets the intestine. Quantitative proteomics revealed that Nel stimulated the host defence. The Nel thus possesses dual roles, as both toxin and elicitor. Remarkably, the Nel protein triggered a similar response, induction of the heat shock pathway and the necrosis pathway, in both model plants and nematodes. The unusual ability of Nel to function across kingdom suggests a highly conserved mechanism in eukaryotes that predates the divergence of plants and animal. It is also speculated that the two‐domain protein is the result of horizontal gene transfer ( HGT) between phytopathogens and entomopathogens. Our results provide an example that HGT occurs between members of different species or even genera with lower frequency are particularly important for evolution of new bacterial pathogen lineages with new virulence. B acillus thuringiensis occupies the same ecological niches, plant and soil, as phytopathogens, providing the opportunity for gene exchange.

Antigenic variation of the human influenza A (H3N2) virus during the 2014–2015 winter season - Sha Hua; XiYan Li; Mi Liu; YanHui Cheng; YouSong Peng; WeiJuan Huang; MinJu Tan; HeJiang Wei; JunFeng Guo; DaYan Wang; AiPing Wu; YueLong Shu; et al. (Science China Life Sciences, 2015)

Species colonisation, not competitive exclusion, drives community overdispersion over long‐term succession - Shao‐peng Li; Marc W. Cadotte; Scott J. Meiners; Zheng‐shuang Hua; Lin Jiang; Wen‐sheng Shu (Ecology Letters, 2015)
Ecological communities often transition from phylogenetic and functional clustering to overdispersion over succession as judged by space‐for‐time substitution studies. Such a pattern has been generally attributed to the increase in competitive exclusion of closely related species with similar traits through time, although colonisation and extinction have rarely been examined. Using 44 years of uninterrupted old‐field succession in New Jersey, USA , we confirmed that phylogenetic and functional clustering decreased as succession unfolded, but the transition was largely driven by colonisation. Early colonists were closely related and functionally similar to residents, while later colonists became less similar to the species present. Extirpated species were generally more distantly related to residents than by chance, or exhibited random phylogenetic/functional patterns, and their relatedness to residents was not associated with time. These results provide direct evidence that the colonisation of distant relatives, rather than extinction of close relatives, drives phylogenetic and functional overdispersion over succession.

Investigating the MicroRNAomes of Two Developmental Phases of Dendrocalamus latiflorus (Poaceae: Bambusoideae) Inflorescences - Xu-Yao Zhao; Xiao-Yan Wang; Lei Zhao; Xue-Mei Zhang; Si-Yun Chen; Peng-Fei Ma; Xiang-Yang Hu; De-Zhu Li; Zhen-Hua Guo (Plant Molecular Biology Reporter, 2015)

Patients with type 2 diabetes exhibit cognitive impairment with changes of metabolite concentration in the left hippocampus - Yue Wang; Xiao-yun Xu; Chun-hua Feng; Yuan-ling Li; Xia Ge; Gen-lin Zong; Yi-bin Wang; Bo Feng; Peng Zhang (Metabolic Brain Disease, 2015)

Effects of hydrodynamic conditions on the sorption behaviors of aniline on sediment with coexistence of nitrobenzene - Peng Wang; Zulin Hua; Yunjie Cai; Xia Shen; Qiongqiong Li; Xiaoyuan Liu (Environmental Science and Pollution Research, 2015)

Experimental studies on the Danxia landscape morphogenesis in Mt. Danxiashan, South China - Cheng Zhu; Li Wu; Tongxin Zhu; Rongfeng Hou; Zhinong Hu; Yan Tan; Wei Sun; Tianjiao Jia; Hua Peng (Journal of Geographical Sciences, 2015)

A new caffeoylgluconic acid derivative from the nearly ripe fruits of Evodia rutaecarpa - Ying He; Jie Li; Hong-Hua Wu; Xin Chai; Jing Yang; Yue-Fei Wang; Peng Zhang; Yan Zhu; Xiu-Mei Gao (Natural Product Research, 2015)

Potent CDC25B and PTP1B phosphatase inhibitors: 2′,4′,6′-trihydroxylchalcone derivatives - Shui-Lian Zhao; Zhou Peng; Xing-Hua Zhen; Hong-Guo Jin; Yan Han; You-Le Qu; Li-Ping Guan (Medicinal Chemistry Research, 2015)

QTL mapping for salt tolerance based on snp markers at the seedling stage in maize (Zea mays L.) - Dezhou Cui; Dandan Wu; Yamuna Somarathna; Chunyan Xu; Song Li; Peng Li; Hua Zhang; Huabang Chen; Li Zhao (Euphytica, 2015)

Direct and indirect effects of nitrogen additions on fine root decomposition in a subtropical bamboo forest - Li-hua Tu; Yong Peng; Gang Chen; Hong-ling Hu; Yin-long Xiao; Ting-xing Hu; Li Liu; Yi Tang (Plant and Soil, 2015)

Association between the CYP2E1 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Liang Song; Ling Peng; Zhibin Bu; Sen-Xiang Yan; Jie Feng; Xin-Li Zhu; Xin-Biao Liao; Xue-Lin Yu; Danfang Yan (Molecular Genetics and Genomics, 2015)

Evaluation of pedotransfer functions for estimating saturated hydraulic conductivity in coastal salt-affected mud farmland - Rong-Jiang Yao; Jing-Song Yang; Dan-Hua Wu; Fu-Rong Li; Peng Gao; Xiang-Ping Wang (Journal of Soils and Sediments, 2015)

Identification of a new maize inflorescence meristem mutant and association analysis using SLAF-seq method - Chao Xia; Li-li Chen; Ting-zhao Rong; Rui Li; Yong Xiang; Peng Wang; Chun-hua Liu; Xiao-qiu Dong; Bing Liu; Dan Zhao; Ru-jun Wei; Hai Lan (Euphytica, 2015)

Cloning of a caffeoyl-coenzyme A O-methyltransferase from Camellia sinensis and analysis of its catalytic activity - Yue Zhang; Hai-peng Lv; Cheng-ying Ma; Li Guo; Jun-feng Tan; Qun-hua Peng; Zhi Lin (Journal of Zhejiang University-SCIENCE B, 2015)

Inducible and constitutive expression of an elicitor gene Hrip1 from Alternaria tenuissima enhances stress tolerance in Arabidopsis - Xue-Cong Peng; De-Wen Qiu; Hong-Mei Zeng; Li-Hua Guo; Xiu-Fen Yang; Zheng Liu (Transgenic Research, 2015)

Characterization of regulatory regions involved in the inducible expression of chiB in Bacillus thuringiensis - Chi-Chu Xie; Jin Shi; Hai-Yun Jia; Peng-Fei Li; Yang Luo; Jun Cai; Yue-Hua Chen (Archives of Microbiology, 2015)

MiR-218-targeting-Bmi-1 mediates the suppressive effect of 1,6,7-trihydroxyxanthone on liver cancer cells - Wei-Ming Fu; Li-Peng Tang; Xiao Zhu; Ying-Fei Lu; Yan-Ling Zhang; Wayne Yuk-Wai LEE; Hua Wang; Yang Yu; Wei-Cheng Liang; Chun-Hay Ko; Hong-Xi Xu; Hsiang-Fu Kung; et al. (Apoptosis, 2015)

Icaritin ameliorates carbon tetrachloride-induced acute liver injury mainly because of the antioxidative function through estrogen-like effects - Peng Liu; Xiang Jin; Hao Lv; Jing Li; Wen Xu; Hai-hua Qian; Zhengfeng Yin (In Vitro Cellular & Developmental Biology - Animal, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Arbutin, an intracellular hydroxyl radical scavenger, protects radiation-induced apoptosis in human lymphoma U937 cells - Li-Hua Wu; Peng Li; Qing-Li Zhao; Jin-Lan Piao; Yu-Fei Jiao; Makoto Kadowaki; Takashi Kondo (Apoptosis, 2014)

Plasmid-encoding vasostatin inhibited the growth and metastasis of human hepatocellular carcinoma cells - Xing-chen Peng; Ming Wang; Xu-xia Chen; Jing Liu; Gui-hua Xiao; Hong-li Liao (Molecular and Cellular Biochemistry, 2014)

Double Transgenesis of Humanized fat1 and fat2 Genes Promotes Omega-3 Polyunsaturated Fatty Acids Synthesis in a Zebrafish Model - Shao-Chen Pang; Hou-Peng Wang; Kuo-Yu Li; Zuo-Yan Zhu; Jing X. Kang; Yong-Hua Sun (Marine Biotechnology, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Development of proteomic technology of shotgun and label free combined with multiple reaction monitoring to simultaneously detect southern rice black-streaked dwarf virus and rice ragged stunt virus - Zhuo Chen; Qin Guo; Bing-Hua Chen; Xiang-Yang Li; Zhen-Chao Wang; Peng He; Fei Yan; De-Yu Hu; Song Yang (VirusDisease, 2014)

Potential for Bioenergy Production from Sugarcane in China - Ling Peng; Phillip A. Jackson; Qi-wei Li; Hai-hua Deng (BioEnergy Research, 2014)

An adaptive noise attenuation method for edge and amplitude preservation - Han-Peng Cai; Zhen-Hua He; Ya-Lin Li; Guang-Ming He; Wen Zou; Dong-Jun Zhang; Pu Liu (Applied Geophysics, 2014)

A field study of the relationship between sulfide-bound metals and bioaccumulation by Limnodrilus sp. in a heavily polluted river - Feng Li; Xiang-yun Zeng; Yun-jun Yu; Chang-hua Wu; Ge Mai; Wei-wei Song; Yan-mao Wen; Zhi-peng Duan; Jia-yu Yang (Environmental Monitoring and Assessment, 2014)

Accumulated Deformation Behavior and Computational Model of Water-Rich Mudstone Under Cyclic Loading - Cheng-hua Shi; Zu-de Ding; Ming-feng Lei; Li-min Peng (Rock Mechanics and Rock Engineering, 2014)

Bioactive Equivalence of Combinatorial Components Identified in Screening of an Herbal Medicine - Peng Liu; Hua Yang; Fang Long; Hai-Ping Hao; Xiaojun Xu; Ying Liu; Xiao-Wei Shi; Dan-Dan Zhang; Hao-Chuan Zheng; Qian-Ying Wen; Wen-Wen Li; Hui Ji; et al. (Pharmaceutical Research, 2014)

Rhizosphere effect has no effect on marker genes related to autotrophic CO2 fixation in paddy soils? - Ke-Qing Xiao; San-An Nie; Peng Bao; Feng-Hua Wang; Qiong-Li Bao; Yong-Guan Zhu (Journal of Soils and Sediments, 2014)

Isofraxidin, a potent reactive oxygen species (ROS) scavenger, protects human leukemia cells from radiation-induced apoptosis via ROS/mitochondria pathway in p53-independent manner - Peng Li; Qing-Li Zhao; Li-Hua Wu; Paras Jawaid; Yu-Fei Jiao; Makoto Kadowaki; Takashi Kondo (Apoptosis, 2014)

Temporal and spatial variations of global deep cloud systems based on CloudSat and CALIPSO satellite observations - Jie Peng; Hua Zhang; Zhanqing Li (Advances in Atmospheric Sciences, 2014)

Mapping and candidate gene identification defining BnChd1-1, a locus involved in chlorophyll biosynthesis in Brassica napus - Hua Zhao; Lei Yu; Zexun Huai; Xiaohua Wang; Guangda Ding; Shuisen Chen; Peng Li; Fangsen Xu (Acta Physiologiae Plantarum, 2014)

Xanthoceraside attenuates tau hyperphosphorylation and cognitive deficits in intracerebroventricular-streptozotocin injected rats - Peng Liu; Li-Bo Zou; Li-Hua Wang; Qing Jiao; Tian-Yan Chi; Xue-Fei Ji; Ge Jin (Psychopharmacology, 2014)

Association between the TP53 polymorphisms and lung cancer risk: a meta-analysis - Xiang-Hua Ye; Zhi-Bin Bu; Jie Feng; Ling Peng; Xin-Biao Liao; Xin-Li Zhu; Xiao-li Sun; Hao-Gang Yu; Dan-Fang Yan; Sen-Xiang Yan (Molecular Biology Reports, 2014)

Changes in some soil properties induced by re-conversion of cropland into grassland in the semiarid steppe zone of Inner Mongolia, China - Zhi-Hua Zhang; Xiao-Yan Li; Zhi-Yun Jiang; Hai-Ying Peng; Liu Li; Guo-Qin Zhao (Plant and Soil, 2013)

Discovery of indeno[1,2- $$c$$ c ]quinoline derivatives as dual topoisomerases I/II inhibitors: Part 3 - Chih-Hua Tseng; Cherng-Chyi Tzeng; Chiao-Li Yang; Pei-Jung Lu; Yu-Peng Liu; Hui-Ling Chen; Chien-Yu Chen; Chia-Ning Yang; Yeh-Long Chen (Molecular Diversity, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Population persistence of a Tertiary relict tree Tetracentron sinense on the Ailao Mountains, Yunnan, China - Cindy Q. Tang; Ming-Chun Peng; Long-Yuan He; Masahiko Ohsawa; Chong-Yun Wang; Tian-Hua Xie; Wen-Shun Li; Jia-Ping Li; Hong-Yu Zhang; Yong Li; Xian-Ming Yang; Guo-Song Li (Journal of Plant Research, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Verapamil reverses cardiac iron overload in streptozocin-induced diabetic rats - Hong-li Shan; Yan Wang; Jian-wei Wu; Peng-zhou Hang; Xin Li; Li-hua Sun; Jian-cui Qi; Yu-ying Mao; Zhi-dan Sun; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Lack of association between SLCO1B1 polymorphism and the lipid-lowering effects of atorvastatin and simvastatin in Chinese individuals - Qiang Fu; Yan-Peng Li; Yuan Gao; Song-Hua Yang; Pei-Qi Lu; Min Jia; Li-Rong Zhang (European Journal of Clinical Pharmacology, 2013)

Transplantation of bone-marrow-derived mesenchymal and epidermal stem cells contribute to wound healing with different regenerative features - Li-Hua Peng; Zu-Yao Mao; Xiao-Tian Qi; Xi Chen; Ni Li; Yasuhiko Tabata; Jian-Qing Gao (Cell and Tissue Research, 2013)

The features of cloud overlapping in Eastern Asia and their effect on cloud radiative forcing - Hua Zhang; Jie Peng; XianWen Jing; JiangNan Li (Science China Earth Sciences, 2013)

Antibacterial nanostructured composite films for biomedical applications: microstructural characteristics, biocompatibility, and antibacterial mechanisms - Fei-Peng Lee; Duen-Jeng Wang; Li-Kai Chen; Chun-Ming Kung; Yi-Chien Wu; Keng-Liang Ou; Chih-Hua Yu (Biofouling, 2013)

Erratum to: Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Triterpenoids from Ganoderma lucidum and their cytotoxic activities - Peng Li; Yan-Ping Deng; Xiao-Xia Wei; Jian-Hua Xu (Natural Product Research, 2013)

Atorvastatin suppresses oxidized LDL-induced dendritic cell-like differentiation of RAW264.7 cells regulated by the p38 MAPK pathway - Liu-hua Hu; Tuo Zhang; Qin Shao; Dan-dan Li; Shu-xuan Jin; Peng Nie; Jing Yi; Ben He; Ling-hong Shen (Molecular and Cellular Biochemistry, 2012)

Phylogenetic analysis of the bovine parainfluenza virus type 3 from cattle herds revealing the existence of a genotype A strain in China - Yong-Jun Wen; Xin-Chuan Shi; Feng-Xue Wang; Wei Wang; Shu-Qin Zhang; Guo Li; Ni Song; Li-Zhi Chen; Shi-Peng Cheng; Hua Wu (Virus Genes, 2012)

Boron distribution and mobility in navel orange grafted on citrange and trifoliate orange - Gui-Dong Liu; Rui-Dong Wang; Li-Shu Wu; Shu-Ang Peng; Yun-Hua Wang; Cun-Cang Jiang (Plant and Soil, 2012)

DEL RBC transfusion should be avoided in particular blood recipient in East Asia due to allosensitization and ineffectiveness - Chao-peng Shao; Bao-yan Wang; Shi-hui Ye; Wen-li Zhang; Hua Xu; Nai-bao Zhuang; Xiao-ying Wu; Heng-gui Xu (Journal of Zhejiang University-SCIENCE B, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Pseudomonas nitritireducens sp. nov., a nitrite reduction bacterium isolated from wheat soil - Ya-Nan Wang; Wei-Hong He; Hua He; Xun Du; Bin Jia; Zhi-Peng Zeng; Ming-Li An; Guo-Can Chen (Archives of Microbiology, 2012)

Metabonomics Approaches and the Potential Application in Foodsafety Evaluation - Hua Kuang; Zhe Li; Chifang Peng; Liqiang Liu; Liguang Xu; Yingyue Zhu; Libing Wang; Chuanlai Xu (Critical Reviews in Food Science and Nutrition, 2012)

Choline inhibits angiotensin II-induced cardiac hypertrophy by intracellular calcium signal and p38 MAPK pathway - Shu Wang; Hong-mei Han; Zhen-wei Pan; Peng-zhou Hang; Li-hua Sun; Ya-nan Jiang; Hao-xin Song; Zhi-min Du; Yan Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Enzymatic fingerprints of polysaccharides of Dendrobium officinale and their application in identification of Dendrobium species - Xue-Qiang Zha; Li-Hua Pan; Jian-Ping Luo; Jun-Hui Wang; Peng Wei; Vibha Bansal (Journal of Natural Medicines, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Dissection of genetic overlap of drought and low-temperature tolerance QTLs at the germination stage using backcross introgression lines in soybean - Wen Bo Zhang; Peng Cheng Qiu; Hong Wei Jiang; Chun Yan Liu; Da Wei Xin; Can Dong Li; Guo Hua Hu; Qing Shan Chen (Molecular Biology Reports, 2012)

Cyclic fluid shear stress promotes osteoblastic cells proliferation through ERK5 signaling pathway - Peng Li; Yan-chao Ma; Xiao-yun Sheng; Hai-tao Dong; Hua Han; Jing Wang; Ya-yi Xia (Molecular and Cellular Biochemistry, 2012)

Simulation of direct radiative forcing of aerosols and their effects on East Asian climate using an interactive AGCM-aerosol coupled system - Hua Zhang; Zhili Wang; Zaizhi Wang; Qianxia Liu; Sunling Gong; Xiaoye Zhang; Zhongping Shen; Peng Lu; Xiaodong Wei; Huizheng Che; Laurent Li (Climate Dynamics, 2012)

miR-29a and miR-142-3p downregulation and diagnostic implication in human acute myeloid leukemia - Fang Wang; Xiao-Shuang Wang; Gui-Hua Yang; Peng-Fei Zhai; Zhen Xiao; Liang-Yu Xia; Li-Rong Chen; Yu Wang; Xiao-Zhong Wang; Lai-Xi Bi; Nian Liu; Yang Yu; et al. (Molecular Biology Reports, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Bufalin enhances the anti-proliferative effect of sorafenib on human hepatocellular carcinoma cells through downregulation of ERK - Yang Gao; Hua-Xing Li; Li-Tao Xu; Peng Wang; Li-Yan Xu; Lorenzo Cohen; Pei-Ying Yang; Ke Gu; Zhi-Qiang Meng (Molecular Biology Reports, 2012)

Quantitative structure-activity relationships of antimicrobial fatty acids and derivatives against Staphylococcus aureus - Hui Zhang; Lu Zhang; Li-juan Peng; Xiao-wu Dong; Di Wu; Vivian Chi-Hua Wu; Feng-qin Feng (Journal of Zhejiang University-SCIENCE B, 2012)

Human tissue kallikrein 1 gene delivery inhibits PDGF-BB-induced vascular smooth muscle cells proliferation and upregulates the expressions of p27Kip1 and p2lCip1 - Hui-Zhen Yu; Liang-di Xie; Peng-li Zhu; Chang-sheng Xu; Hua-jun Wang (Molecular and Cellular Biochemistry, 2012)

Central nervous system regulation of food intake and energy expenditure: role of galanin-mediated feeding behavior - Peng-Hua Fang; Mei Yu; Yin-Ping Ma; Jian Li; Yu-Mei Sui; Ming-Yi Shi (Neuroscience Bulletin, 2011)

Seed size is determined by the combinations of the genes controlling different seed characteristics in rice - Song Yan; Guihua Zou; Sujuan Li; Hua Wang; Heqin Liu; Guowei Zhai; Peng Guo; Hongmiao Song; Changjie Yan; Yuezhi Tao (Theoretical and Applied Genetics, 2011)

TP53 codon 72 polymorphism and colorectal cancer susceptibility: a meta-analysis - Jing-Jun Wang; Yuan Zheng; Liang Sun; Li Wang; Peng-Bo Yu; Jian-Hua Dong; Lei Zhang; Jing Xu; Wei Shi; Yu-Chun Ren (Molecular Biology Reports, 2011)

A recessive gene controlling male sterility sensitive to short daylength/low temperature in wheat (Triticum aestivum L.) - Xiao-dong Chen; Dong-fa Sun; De-fu Rong; Jun-hua Peng; Cheng-dao Li (Journal of Zhejiang University-SCIENCE B, 2011)

Expression of Trichoderma viride endoglucanase III in the larvae of silkworm, Bombyx mori L. and characteristic analysis of the recombinant protein - Xing-hua Li; Peng Zhang; Mei-xian Wang; Fang Zhou; Firdose Ahmad Malik; Hua-jun Yang; Roy Bhaskar; Jia-biao Hu; Chun-guang Sun; Yun-gen Miao (Molecular Biology Reports, 2011)

PI3K/Akt signaling pathway is involved in the pathogenesis of ulcerative colitis - Xiao Li Huang; Jin Xu; Xiao Hui Zhang; Bo Yun Qiu; Lan Peng; Meng Zhang; Hua Tian Gan (Inflammation Research, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Naturalization of alien plants in China - Hua Jiang; Qiang Fan; Jin-Tian Li; Shi Shi; Shao-Peng Li; Wen-Bo Liao; Wen-Sheng Shu (Biodiversity and Conservation, 2011)

Neuroprotection of Interleukin-6 Against NMDA-Induced Apoptosis and Its Signal-Transduction Mechanisms - Zhan Liu; Yi-Hua Qiu; Bing Li; Song-Hua Ma; Yu-Ping Peng (Neurotoxicity Research, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

Protection of CHO cells by transfer of survivin driven by ovarian-specific promoter OSP-2 - Chun-Hua Tu; Wei-Peng Liu; Mei Dong; Li-Ping Cai; Ya-Qin Mo; Dong-Zi Yang (Molecular Biology Reports, 2011)

Analysis of correlation between blood biochemical indicators and bone mineral density of post-menopausal women - Shun-zhi Liu; Li-fang Tian; Peng Xu; Gui-hua Zhuang; Fang Zheng; Juan Tian; Qi-Lan Ning; Bo-Feng Zhu; She-Min Lu; Hong Yan (Molecular Biology Reports, 2011)

Silica-supported sulfonic acid-functionalized ionic liquid coated with [bmim][PF6] as a scavenger for the synthesis of amides - Li-Qin Kang; Yue-Qin Cai; Yan-Qing Peng; Xi-Li Ying; Gong-Hua Song (Molecular Diversity, 2011)

osa-MIR393: a salinity- and alkaline stress-related microRNA gene - Peng Gao; Xi Bai; Liang Yang; Dekang Lv; Xin Pan; Yong Li; Hua Cai; Wei Ji; Qin Chen; Yanming Zhu (Molecular Biology Reports, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

The −159C/T polymorphism in the CD14 gene and the risk of asthma: a meta-analysis - Yonggang Zhang; Can Tian; Jie Zhang; Xiaobo Li; Hua Wan; Chao He; Liang Guo; Quocuo Meilang; Chunhong Peng; Lina Duo; Jin Huang; Hong Fan (Immunogenetics, 2011)

Over-expression of osa-MIR396c decreases salt and alkali stress tolerance - Peng Gao; Xi Bai; Liang Yang; Dekang Lv; Yong Li; Hua Cai; Wei Ji; Dianjing Guo; Yanming Zhu (Planta, 2010)

Molecular analysis of an actin gene, CarACT1, from chickpea (Cicer arietinum L.) - Hui Peng; Huiying Cheng; Xingwang Yu; Qinghua Shi; Hua Zhang; Jiangui Li; Hao Ma (Molecular Biology Reports, 2010)

Exercise benefits cardiovascular health in hyperlipidemia rats correlating with changes of the cardiac vagus nerve - You-Hua Wang; Hao Hu; Sheng-Peng Wang; Zhen-Jun Tian; Quan-Jiang Zhang; Qiu-Xia Li; You-You Li; Xiao-Jiang Yu; Lei Sun; Dong-Ling Li; Bing Jia; Bing-Hang Liu; et al. (European Journal of Applied Physiology, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Characterization and structural analysis of the coat protein from Chinese isolates of Cymbidium mosaic virus - Yun-Chao Liu; Lu-Bin Li; Yun-Liang Li; Qing-Hu Ma; Zhen-Hua Peng (Journal of Plant Diseases and Protection, 2009)

Correlation Analysis Between Bone Mineral Density and Serum Element Contents of Postmenopausal Women in Xi’an Urban Area - Shun-Zhi Liu; Hong Yan; Peng Xu; Jian-Ping Li; Gui-Hua Zhuang; Bo-Feng Zhu; She-Min Lu (Biological Trace Element Research, 2009)

Profiling Gene Expression During Gland Morphogenesis of a Glanded and a Glandless Upland Cotton - Ying-Fan Cai; Min Chen; Quan Sun; Yong-Fang Xie; Sheng-Wei Li; Ming-Feng Jiang; Jian-Chuan Mo; You-Lu Yuan; Yu-Zhen Shi; Huai-Zhong Jiang; Zheng Pan; Yun-Ling Gao; et al. (Journal of Plant Biology, 2009)

Reciprocal regulation between M3 muscarinic acetylcholine receptor and protein kinase C-ε in ventricular myocytes during myocardial ischemia in rats - Peng-zhou Hang; Jing Zhao; Yu-ping Wang; Li-hua Sun; Yong Zhang; Li-li Yang; Na Zhao; Zhi-dan Sun; Yu-ying Mao; Zhi-min Du (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Isolation of a malachite green-degrading Pseudomonas sp. MDB-1 strain and cloning of the tmr2 gene - Lian-tai Li; Qing Hong; Xin Yan; Gui-hua Fang; Shinawar Waseem Ali; Shun-peng Li (Biodegradation, 2009)

Types and spatial combinations of Danxia landform of Fangyan in Zhejiang Province - Jie Ouyang; Cheng Zhu; Hua Peng; Jinbiao Yu; Lan Li; Riliang Zhou; Guangsheng Zhang; Guangyao Zhu; Zhongxuan Li; Yishun Zhong; Qing Zhu; Wen Lv; et al. (Journal of Geographical Sciences, 2009)

Age and genesis of the Danxia landform on Jianglang Mountain, Zhejiang Province - Cheng Zhu; Hua Peng; Zhongxuan Li; Guangsheng Zhang; Lan Li; Jinbiao Yu; Guangyao Zhu; Jie Ouyang; Yishun Zhong; Qing Zhu; Shuqin Zhou; Chaogui Zheng; et al. (Journal of Geographical Sciences, 2009)

Improvement of arachidonic acid and eicosapentaenoic acid production by increasing the copy number of the genes encoding fatty acid desaturase and elongase into Pichia pastoris - Yun-Tao Li; Mao-Teng Li; Chu-Hua Fu; Peng-Peng Zhou; Jian-Min Liu; Long-Jiang Yu (Biotechnology Letters, 2009)

Cumulative effects of nitrogen additions on litter decomposition in three tropical forests in southern China - Hua Fang; Jiangming Mo; Shaolin Peng; Zhian Li; Hui Wang (Plant and Soil, 2009)

Estimating Long-Term Changes in China’s Village Landscapes - Erle Christopher Ellis; Nagaraj Neerchal; Kui Peng; Hong Sheng Xiao; Hongqing Wang; Yan Zhuang; Shou Cheng Li; Jun Xi Wu; Jia Guo Jiao; Hua Ouyang; Xu Cheng; Lin Zhang Yang (Ecosystems, 2009)

TM4SF3 promotes esophageal carcinoma metastasis via upregulating ADAM12m expression - Zhuan Zhou; Yu-Liang Ran; Hai Hu; Jian Pan; Zhi-Feng Li; Li-Zhao Chen; Li-Chao Sun; Liang Peng; Xi-Lu Zhao; Long Yu; Li-Xin Sun; Zhi-Hua Yang (Clinical & Experimental Metastasis, 2008)

Effects of pcDNA3-β-NGF Gene-modified BMSC on the Rat Model of Parkinson’s Disease - Ting-Hua Wang; Zhong-Tang Feng; Peng Wei; Hui Li; Zhen-Jiang Shi; Li-Yan Li (Journal of Molecular Neuroscience, 2008)

A novel two-step fermentation process for improved arachidonic acid production by Mortierella alpina - Ming-Jie Jin; He Huang; Ai-Hua Xiao; Kun Zhang; Xin Liu; Shuang Li; Chao Peng (Biotechnology Letters, 2008)

Microsatellite Analysis of Genetic Variation and Population Genetic Differentiation in Autotetraploid and Diploid Rice - Li Luan; Xing Wang; Wen-Bo Long; Yu-Hua Liu; Sheng-Bin Tu; Zhan-Peng Zhao; Fan-Lun Kong; Mao-Qun Yu (Biochemical Genetics, 2008)

Salinicoccus salitudinis sp. nov., a new moderately halophilic bacterium isolated from a saline soil sample - Yi-Guang Chen; Xiao-Long Cui; Wen-Jun Li; Li-Hua Xu; Meng-Liang Wen; Qian Peng; Cheng-Lin Jiang (Extremophiles, 2008)

Notch activation promotes cell proliferation and the formation of neural stem cell-like colonies in human glioma cells - Xue-Ping Zhang; Gang Zheng; Lian Zou; Hui-Ling Liu; Li-Hong Hou; Peng Zhou; Dan-Dan Yin; Qi-Jun Zheng; Liang Liang; Su-Zhen Zhang; Lei Feng; Li-Bo Yao; et al. (Molecular and Cellular Biochemistry, 2007)

Streptomyces tritolerans sp. nov., a novel actinomycete isolated from soil in Karnataka, India - Dastager G. Syed; Dayanand Agasar; Chang-Jin Kim; Wen-Jun Li; Jae-Chan Lee; Dong-Jin Park; Li-Hua Xu; Xin-Peng Tian; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2007)

Proteomic identification of differently expressed proteins responsible for osteoblast differentiation from human mesenchymal stem cells - Ai-Xia Zhang; Wei-Hua Yu; Bao-Feng Ma; Xin-Bing Yu; Frank Fuxiang Mao; Wei Liu; Jia-Qing Zhang; Xiu-Ming Zhang; Shu-Nong Li; Ming-Tao Li; Bruce T. Lahn; Andy Peng Xiang (Molecular and Cellular Biochemistry, 2007)

BRD7 suppresses the growth of Nasopharyngeal Carcinoma cells (HNE1) through negatively regulating β-catenin and ERK pathways - Cong Peng; Hua Ying Liu; Ming Zhou; Li Ming Zhang; Xiao Ling Li; Shou Rong Shen; Gui Yuan Li (Molecular and Cellular Biochemistry, 2007)

Cumulative effects of nitrogen additions on litter decomposition in three tropical forests in southern China - Hua Fang; Jiangming Mo; Shaolin Peng; Zhian Li; Hui Wang (Plant and Soil, 2007)

Unexpected effect of concomitantly administered curcumin on the pharmacokinetics of talinolol in healthy Chinese volunteers - He Juan; Bernd Terhaag; Zang Cong; Zhang Bi-Kui; Zhu Rong-Hua; Wang Feng; Su Fen-Li; Song Juan; Tang Jing; Peng Wen-Xing (European Journal of Clinical Pharmacology, 2007)

BRD2 is one of BRD7-interacting proteins and its over-expression could initiate apoptosis - Ming Zhou; Xiao-Jie Xu; Hou-De Zhou; Hua-Ying Liu; Jia-Jin He; Xiao-Ling Li; Cong Peng; Wei Xiong; Song-Qing Fan; Jian-Hong Lu; Jue Ouyang; Shou-Rong Shen; et al. (Molecular and Cellular Biochemistry, 2006)

Philinopsides E and F, two new sulfated triterpene glycosides from the sea cucumber Pentacta quadrangularis - Shi-Long Zhang; Ling Li; Yang-Hua Yi; Peng Sun (Natural Product Research, 2006)

Taxonomic significance of leaf anatomy of Aniselytron (Poaceae) as an evidence to support its generic validity against Calamagrostis s. l. - Hai-Ying Ma; Hua Peng; De-Zhu Li (Journal of Plant Research, 2005)

Association tests of interleukin-6 (IL-6) and type II tumor necrosis factor receptor (TNFR2) genes with bone mineral density in Caucasians using a re-sampling approach - Peng Xiao; Peng-Yuan Liu; Yan Lu; Yan-Fang Guo; Dong-Hai Xiong; Li-Hua Li; Robert R. Recker; Hong-Wen Deng (Human Genetics, 2005)

Surgical management of gastric stump cancer: a report of 37 cases - Li Chen; Hua Tian; Jian Chen; Zhi-gang He; Si-feng Tao; Gurung Lokesh; Shu-you Peng (Journal of Zhejiang University-SCIENCE B, 2005)

(R)-Oxynitrilase-catalysed synthesis of chiral silicon-containing aliphatic (R)-ketone-cyanohydrins - Ning Li; Min-Hua Zong; Chen Liu; Hua-Song Peng; Hua-Chang Wu (Biotechnology Letters, 2003)

Low Genetic Variation of the Yunnan Hare (Lepus comus G. Allen 1927) as Revealed by Mitochondrial Cytochrome b Gene Sequences - Chun-Hua Wu; Hai-Peng Li; Ying-Xiang Wang; Ya-Ping Zhang (Biochemical Genetics, 2000)